Evolutionary Prevalence of the Electrostatic Switch Mechanism in P-type ATPases - Nikita S. Badve; Alyssa V. Buda; Jonas A. Káral; Zhitong Li; Taylah L. Percival; Sofia Y. Wardman; Sophia G. Tran; Simon Y. W. Ho; Ronald J. Clarke (The Journal of Membrane Biology, 2026)

Spatial models cannot compensate for sampling designs unstructured relative to isotopic variation: implications for baseline isoscape development in the Mediterranean Sea - Sarah Magozzi; Clive N. Trueman; Matthew R.D. Cobain; Kirsteen M. MacKenzie; Katie St. John Glew; José A. Canseco; Eric Díaz-Delgado; Emanuela Fanelli; Paola Rumolo; Joan E. Cartes; Boris Espinasse; Davide Agnetta; et al. (Progress in Oceanography, 2026)

Opportunities to improve detection of genetic predisposition for ovarian cancer applying the Tumor-First workflow - Vera M. Witjes; Joanne A. de Hullu; Angela van Remortele; Lilian Vreede; Michiel Simons; Nicoline Hoogerbrugge; Marjolijn J. L. Ligtenberg (Familial Cancer, 2026)
Genetic testing in ovarian carcinoma (OC) patients is very important for patients and their relatives. The Tumor-First workflow uses a tumor DNA test to stratify germline testing for hereditary cancer predisposition as well as treatment options with PARP inhibitors. This workflow is adopted and successfully implemented nationwide. Here, we evaluated recent tumor DNA testing rates in the Netherlands to identify untested OC patient groups and optimize tumor DNA testing rates. OC patients diagnosed in 2023 or 2024 were selected from the Netherlands Cancer Registry. We analyzed patient characteristics associated with the likelihood of tumor DNA testing using multivariable logistic regression. Tumor-First testing was performed for 1765 out of the 2221 (79%) OC patients. Patients diagnosed with advanced stage OC were more likely to receive tumor DNA testing (OR = 2.5, p < 0.001) than those with low-stage disease. Compared with patients who underwent surgery as primary treatment, those who received chemotherapy or no primary treatment were less likely to be tested (OR = 0.21 and OR = 0.07, respectively, p < 0.001). Patients who died within 100 days were less likely to receive testing (OR = 0.57, p = 0.003). Patients without resection after diagnosis on biopsy/cytology had the lowest Tumor-First testing rates (58% vs. 87–95%, χ2 p < 0.001). Tumor-First testing rates are high. However, OC patients that do not undergo a resection are less likely to undergo testing. With these data strategies to identify hereditary cancer predisposition in patients and their relatives can be further improved.

Evolutionary spandrels in collective animal behaviour - Andrew J. King; Ella G. Henry; Simon Garnier; William L. Allen; Robert J.P. Heathcote; Marco Fele; Marina Papadopoulou; Daniel W.E. Sankey; Ines Fürtbauer (Trends in Ecology & Evolution, 2026)

Rich litter admixture effects on belowground carbon dynamics in temperate forests: From leaf litter input to molecular composition of soil organic matter - S.E. Nijdam; K. Vancampenhout; B. Jansen; E. Morriën; J. Schellekens; B. Leenders; J. Simons; L. Van den Berg; M. de Graaf; B. Nyssen; B. Muys; E. Desie (Forest Ecology and Management, 2026)

Community biocultural mapping reveals historical occupation and enables defense of African rainforests - Ibola Dja Bana Ba Massaha; Serge Ekazama Koto; Gretchen M. Walters; Honorine Asatsi Mabo; Fulbert Makala; Paulin Ndanga Azeon; Jean Mabo; Philippe N. Mandoumilele; Jean P. Hendje; Dieu-Donné Baza Djia; HB Betotobeya; Modeste Ndongoabendje; et al. (Ambio, 2026)
Global conservation maps often overlook community lands, impacting decision-making and reducing local agency. We focus on the high-profile and regionally important case of Massaha’s ancestral territory (Ibola Dja Bana Ba Massaha). In Gabon, the forest is largely gazetted into logging concessions and described as an Eden-like wilderness despite long-term human presence. We compare Massaha’s biocultural maps to global, colonial, and post-colonial maps, in a community peer review process. While these maps show Ibola Dja Bana Ba Massaha as devoid of logging and settlement, Massaha’s maps show long-term settlement, sacred areas and industrial logging. Massaha used their maps to request the government to protect their forest from logging and update the forestry code to enable community conserved areas, prompting a national debate on the legal recognition of “territories of life”, while revitalising ancestral practices. We show that “big data” conservation mapping must account for biocultural knowledge if it is to be effective in guiding conservation decisions.

Assessing the vulnerability of elasmobranchs to western and central Pacific tuna fisheries using an improved ecological risk assessment method - Nicholas J. Hill; Shane Griffiths; Valerie Allain; Simon Nicol; Joanne Potts; Naiten Bradley Phillip; Cassandra L. Rigby (Fisheries Research, 2026)

Intraoperative drug delivery to hindbrain tumours via an injectable hydrogel is well tolerated and confers survival benefit against atypical teratoid/rhabdoid xenografts - Cara Moloney; Phoebe McCrorie; Amr ElSherbeny; Harry Porter; Chiara Bastiancich; Hasan Slika; Aanya Shahani; Emre Derin; Esteban Velarde; Jackson Miller; John Theodore; Khushi Varshney; et al. (Drug Delivery and Translational Research, 2026)

Diet of juvenile skipjack herring Alosa chrysochloris : Ontogenetic shifts, predator–prey size ratios and mouth gape allometry - Joshua P. Egan; Peter J. Hundt; Neil P. Rude; Jason A. DeBoer; Benjamin J. Lubinski; Kristopher A. Maxson; Levi E. Solomon; Andrya L. Whitten Harris; Andrew M. Simons (Journal of Fish Biology, 2026)
The skipjack herring Alosa chrysochloris inhabits Gulf of Mexico drainages, primarily the Mississippi River Basin, and estuarine environments in the Gulf of Mexico. The trophic ecology of the skipjack herring is poorly understood, therefore we quantified the length, mouth gape and gut contents of juvenile skipjack herring from the Mississippi River (fish n = 6), Illinois River (fish n = 181) and Ohio River (fish n = 255) and tested for changes in diets and predator–prey size ratios during ontogeny. We identified statistically significant changes in prey type consumption during ontogeny. Aquatic insects dominated the diets of skipjack herring 40 mm SL were primarily composed of fishes. The most prevalent fish species consumed by skipjack herring were invasive bigheaded carps Hypophthalmichthys spp. and preliminary evidence indicated that inter‐annual variation in the consumption of bigheaded carps was driven by variation in juvenile bigheaded carp abundance. Additional research is needed to determine if the enhancement of native skipjack herring populations could be used as a tool to limit bigheaded carp population sizes. Skipjack herring SL and mouth gape were both significantly positively correlated with maximum, median and minimum sizes of prey consumed. There were allometric changes in the mouth gape of juvenile skipjack herring, with the ratio of mouth gape to SL increasing until ~80 mm SL, then gradually declining. Maximum mouth gape to SL ratios corresponded to substantial increases in the consumption of fishes, indicating that mouth gape allometry may facilitate the ontogenetic transition to piscivory in the skipjack herring. This study improves our understanding of skipjack herring ecology and provides data that can be incorporated into future ecological and evolutionary research, such as the development of food web models.

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Reconstructing one of the largest explosive eruptions of the Quaternary through high-resolution tephra geochemistry: the 349 ka Whakamaru supereruption - Anna L. Miller; Simon J. Barker; Colin J.N. Wilson (Journal of Volcanology and Geothermal Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Structural characterisation of a fucose-rich acidic extracellular polysaccharide produced by Lindavia intermedia in New Zealand lakes - Cara A. Luiten; Ian M. Sims; Tracey J. Bell; Peter T. Northcote; A. Jonathan Singh; Andrew R. Lewis; Guilherme L. Sassaki; Phil M. Novis; Marc Schallenberg; Simon F.R. Hinkley (Algal Research, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Genesis and structural evolution of the San Albino orogenic gold deposit, NW Nicaragua with implications for Mesozoic tectonic and metallogenic processes in Central America - Ben M. Frieman; Bradley L. Squires; Thomas Monecke; Richard J. Goldfarb; Joseph E. Andrew; Simon Kocher (Mineralium Deposita, 2026)

Impact of an online-guided physical activity intervention on cognition, resting-state brain connectivity, and the gut microbiome in healthy older adults—a randomized controlled trial - Simon J. Schrenk; Corinna Bang; Lena Best; Thomas Dost; Stefano Flor; Christiane Frahm; Christian Gaser; Rami Abou Hamdan; Marco Herbsleb; Christoph Kaleta; Fabian Kattlun; Hans-Josef Müller; et al. (GeroScience, 2026)
Introduction Physical activity may enhance cognition in older adults, yet evidence from randomized controlled trials (RCTs) on mechanistic pathways remains inconclusive. Methods This single-blinded RCT examined the effects of an 8-week, online-guided, multicomponent physical activity intervention on cognitive function, resting-state functional brain connectivity (rsFC), and the gut microbiome in 92 healthy older adults (M age = 66.35). Participants were randomized to a physical activity group performing moderate-to-vigorous-intensity aerobic, coordination, and balance exercises, or to an active control group engaging in progressive muscle relaxation and listening to aging-related podcasts. The primary outcome was change in visual processing speed (items/s) from pre- to post-assessment. Secondary outcomes included changes in additional cognitive measures, rsFC, cardiorespiratory fitness (CRF), and the gut microbiome. Results The primary outcome showed no significant between-group differences. However, exploratory analyses revealed potential improvements in inhibition ( η 2 = 0.061; p = 0.025) and visual memory ( η 2 = 0.047; p = 0.040) in the physical activity group. This group also showed a potential increase in rsFC between visual and dorsal attention networks ( η 2 = 0.101; p = 0.009). Visual memory gains correlated with improvements in rsFC ( p = 0.013). No between-group differences were observed in CRF or gut microbiome composition. Discussion While the primary outcome (visual processing speed) and predefined mechanistic pathways (e.g., gut microbiome composition) remained unaffected, this may partly reflect the sample’s high baseline fitness, which likely limited observable improvements. Exploratory findings suggest potential cognitive and associated rsFC benefits in memory and attention-related networks. The online format enabled a structured, scalable intervention while minimizing potential confounding from social interaction. Trial registration https://drks.de/search/de/trial/DRKS00028022 (date of registration: 14.02.2022).

Thermomechanics coupling to Monte Carlo particle transport on unstructured mesh geometries using Cardinal - Mahmoud Eltawila; Pierre-Clément A. Simon; Guillaume L. Giudicelli; Helen Brooks; Nicholas Wozniak; April J. Novak (Annals of Nuclear Energy, 2026)

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Origins and environmental impacts of distal rhyolitic tephra layers on Chatham Island, New Zealand - Anna L. Miller; Simon J. Barker; Katherine A. Holt; Stephen B. Piva; Colin J. N. Wilson (Journal of Quaternary Science, 2026)
Chatham Island, ~700 km east of mainland New Zealand, preserves several macroscopic tephra beds, sourced from the central Taupō Volcanic Zone (TVZ) some 850 km away. These layers, often enclosed within peat, provide insights into the eruptive characteristics, timing and paleoenvironmental impacts of large explosive rhyolitic eruptions in a distal setting. We report the nature, origins and impacts of these tephras by documenting bulk and centimetric‐scale stratigraphic changes in glass shard geochemistry and millimetric‐scale changes in pollen assemblages in the enclosing peats. Three layers are investigated: the ~25.5 ka Kawakawa–Ōruanui Tephra (KOT), the ~345 ka Rangitawa Tephra and one newly discovered tephra. The KOT shows no stratigraphic variability in glass composition throughout ~15 cm thickness. The Rangitawa Tephra contains three glass populations that were deposited sequentially throughout the eruption and further link this tephra to the Whakamaru supereruption. The new tephra has two glass populations and is matched to the ~322 ka Matahina caldera‐forming eruption. High‐resolution sampling of peat bracketing the KOT and Rangitawa Tephra reveals marked changes in local vegetation following the deposition of both tephras. The nature of the changes varies between events and can be explained by differing paleoenvironmental settings, climate and/or tephra thickness.

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Isolation and characterisation of cell wall polysaccharides from taewa (Māori potatoes; Solanum tuberosum L.) - Cara.A. Luiten; Simon F.R. Hinkley; Nick R. Roskruge; Saii A. Semese; Anne-Louise M. Heath; Tracy L. Perry; Nancy J. Rehrer; Ian M. Sims (Food Hydrocolloids, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

An initial map of European intertidal seagrass - Bede Ffinian Rowe Davies; Simon Oiry; Mar Roca; Philippe Rosa; Maria Laura Zoffoli; Dimitris Poursanidis; Tobias Dolch; Bárbara Ondiviela; Cristina Galván; Ana C. Brito; Richard J. Lilley; Laura L. Govers; et al. (Remote Sensing of Environment, 2026)

Phthalates, bisphenols, and childhood allergic Phenotypes: Findings from two birth cohort studies - Thomas Boissiere-O'Neill; Nina Lazarevic; Anne-Louise Ponsonby; Peter D. Sly; Aimin Chen; Tamara L. Blake; Jeffrey R. Brook; Cassidy Du Berry; Louise King; Piushkumar J. Mandhane; Theo J. Moraes; Elinor Simons; et al. (Environmental Pollution, 2026)

Correction to: Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2026)

Spaceborne estimates of canopy temperature and soil moisture predict daily and annual subalpine tree growth - Eli W. Estey; Jan U.H. Eitel; Lee A. Vierling; Grace L. Peven; Kerry A. Cawse-Nicholson; Simon J. Hook; Kevin L. Griffin (Agricultural and Forest Meteorology, 2026)

Changes to virus taxonomy, the international code of virus classification and nomenclature, and the ICTV statutes ratified by the International Committee on Taxonomy of Viruses (2025) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Juliana Freitas-Astúa; R. Curtis Hendrickson; Holly R. Hughes; Mart Krupovic; et al. (Archives of Virology, 2026)
The 56th meeting of the Executive Committee (EC) of the International Committee on Taxonomy of Viruses (ICTV) was held in Bari, Italy, in July/August, 2024, and 115 submitted taxonomy proposals were reviewed. A total of 112 were subsequently ratified by the ICTV membership. An additional 9 error correction proposals were also approved in August 2025. This article lists the taxonomy proposals that have now been incorporated into release 40 version v2 of the Master Species List ( https://ictv.global/msl ), the Virus Metadata Resource ( https://ictv.global/vmr ), and associated ICTV databases. In addition to the assignments of 1,563 new virus species, 243genera, 55 families, 11 orders, and 8 classes, there were substantial additions to higher taxonomic ranks. These include the creation of a new realm ( Singelaviria ), which is based on the recognition of a separate evolutionary origin for the hallmark capsid genes of members of the kingdom Helvetiavirae. These express capsid proteins forming a single jelly-roll fold that is structurally and evolutionarily distinct from those of members of the family Bamfordvirae , assigned to the realm Varidnaviria . Furthermore, the realm Varidnaviria underwent a major reorganization, including the addition of a new kingdom, Abadenavirae . Another notable change was the classification of the vertebrate-infecting single-stranded DNA anellovirids into a new phylum Commensaviricota (kingdom Shotokuvirae , realm Monodnaviria ). Archaeal viruses infecting the hyperthermophilic Archaeoglobi were assigned to a new phylum Calorviricota , in the kingdom Trapavirae (realm Monodnaviria ), whereas RNA viruses infecting hyperthermophilic bacteria were classified into a new phylum Artimaviricota (realm Riboviria ). In recognition of his extensive and valuable contributions to virus taxonomic developments in Study Groups and over the period of his EC membership, Stuart Siddell was honoured as a new life member of the ICTV. The ICTV has created a new strategy for disseminating information on taxonomy advances through annual open-access publication of citeable taxonomy proposal summaries from each ICTV Subcommittee. A collective total of 354 co-authors of the seven summaries were drawn from members of each Subcommittee, the EC, and a very large number of contributors from the wider virology community.

Longitudinal effects of cerebrovascular reactivity and cerebral pulsatility in cognitively intact older adults with APOE4: links with cognition - Zacharie Potvin-Jutras; Pierre-Luc Tremblay; Hanieh Mohammadi; Sylvia Villeneuve; R. Nathan Spreng; Claudine J. Gauthier; Sylvia Villeneuve; Judes Poirier; John C.S. Breitner; Jennifer Tremblay-Mercier; Jordana Remz; Jean-Michel Raoult; et al. (GeroScience, 2025)

Recycling of ash particles during highly explosive eruptions: multiple glass populations in the 1.8 ka Taupō tephra - Simon J. Barker; Stephen B. Piva; Colin J. N. Wilson; David J. Lowe; Bruce L. A. Charlier; Alan R. Orpin (Bulletin of Volcanology, 2025)

Two contrasting swamp forest succession pathways in central Congo Basin peatlands - Donna Hawthorne; Ian T. Lawson; Greta C. Dargie; Nicholas T. Girkin; Bart Crezee; William Hiles; George E. Biddulph; Yannick E. Bocko; Arnoud Boom; Corneille E.N. Ewango; Yannick Garcin; Pauline Gulliver; et al. (Quaternary Science Reviews, 2025)

Halogenated persistent organic pollutants in selected processed small fish species from Ghana - L. Uhr; J. Pucher; A. Atter; A. Jahnke; A. Jährmann; M. Kjellevold; K. Simon; L. Wessels; M. Yamamoto; A. Lüth (Food Chemistry, 2025)

Efficient synthetic natural gas production from direct air capture using titania-based dual function materials - Mathew J. Rasmussen; Sawyer Halingstad; Nathan C. Ellebracht; Melinda L. Jue; Alex Hill; Matthew M. Yung; Simon H. Pang (Chemical Engineering Journal, 2025)

Relocation of 3 April 2017 Moiyabana Earthquake in Botswana Using Seismological Data from Local Network of Autonomously Recording Seismographs and International Monitoring System Stations - Rapelang E. Simon; J. G. King; L. C. Moffat; M. D. Moidaki; M. T. O. Kwadiba; K. G. Jackson; O. Ntibinyane; R. T. Ranganai (Pure and Applied Geophysics, 2025)
On the 3rd April 2017 a widely felt Moiyabana earthquake shook Botswana and the rest of southern Africa. Previous Moiyabana earthquake locations used mainly teleseismic or regional seismograms; and/or non-seismic methods which include Synthetic Aperture Radar (InSAR), and magnetotelluric (MT). These results did not agree, as evidenced by the depth of the earthquake that ranged from zero to 30 km (i.e. indicating either a man-made event or a natural event); thus motivating us to re-assess the location parameters. Unfiltered seismic waveform data from the recent project of the Network of Autonomously Recording Seismographs (NARS) in Botswana was complimented with stations from the International Monitoring System (IMS) to relocate the event. Relocated parameters are origin time, epicentre, focal depth, and magnitude. Geotool software from the Comprehensive Nuclear Test Ban Treaty Organization (CTBTO), and the Regional Seismic Travel Time model (RSTT) were used to process vertical components waveforms from 9 NARS and 32 IMS stations. Geotool results are: earthquake epicentre (22.645 °S: 25.220 °E); origin time of 17:40:16.9 (UTC); hypocentral depth range of 22 to 24 km; body magnitude (mb) and local magnitude (ml) of 6.3 ± 0.6 and 6.0 ± 0.8, respectively. RSTT results are: earthquake epicentre (22.667 °S: 25.257 °E); origin time of 17:40:16.95 (UTC); hypocentral depth of 25 km; and mb of 6.65 ± 0.03. The seismological location parameters from Geotool and RSTT, agree very well within experimental uncertainties with the non-seismic geophysical methods.

Correction to: Effects of neonicotinoids and fipronil on non-target invertebrates - L. W. Pisa; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; C. A. Downs; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; M. McField; C. A. Morrissey; D. A. Noome; et al. (Environmental Science and Pollution Research, 2025)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Spheroidal carbonaceous particles and other black carbon from Crawford Lake, Ontario, Canada - Joshua M. Moraal; Francine M. G. McCarthy; Simon D. Turner; Michael F. J. Pisaric; Brian F. Cumming; Nicholas L. Riddick; Joseph I. Boyce (Palynology, 2025)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2025)
Barth syndrome (BTHS) is an X-linked recessive disorder characterized by cardiomyopathy, skeletal muscle myopathy and fatigue, growth restriction, and neutropenia. Neutropenia increases the risk of life-threatening bacterial infections, a major cause of death in individuals with BTHS. Currently, there is no curative treatment for BTHS or associated neutropenia. The development of therapeutic strategies to correct BTHS-associated neutropenia has been hindered by a limited understanding of the underlying molecular mechanisms involved. BTHS is caused by a mutation in the Tafazzin gene encoding a transacylase required for the maturation of cardiolipin, an inner mitochondrial membrane phospholipid crucial for mitochondrial structure and function. We introduced a BTHS patient’s point mutation ( TAZ D75H ) into the mouse Tafazzin enzyme’s critical acyltransferase site using CRISPR/Cas9 -mediated genome editing, resulting in a patient-tailored point mutant knock-in BTHS model ( Taz D75H ) that expresses a stable mutant Taz D75H protein lacking transacylase activity. Taz D75H mice were then used to investigate how loss of Tafazzin enzymatic activity impacts hematopoiesis. Male Taz D75H mice exhibited impaired granulopoiesis and neutropenia secondary to impaired function of hematopoietic progenitors. Furthermore, they demonstrated age-dependent neutrophil maturation impairment reflecting the variable neutropenia observed in BTHS patients. Additionally, male Taz D75H mice exhibit chronic lymphopenia that persists post Taz D75H bone marrow transplantation. Mechanistically, the TAZ D75H point mutation caused hematopoietic cell mitochondrial dysfunction in patient-derived immortalized TAZ D75H lymphoblasts, increasing reactive oxygen species production and mitochondrial membrane depolarization. Likewise, Cyclosporine A treatment rescued these mitochondrial phenotypes in vitro, confirming TAZ D75H mitochondrial dysfunction. Overall, our findings demonstrate that mitochondrial dysfunction secondary to TAFAZZIN loss of enzymatic function underlies BTHS-associated neutropenia and lymphopenia.

Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Aaron A. Skinner; Alicia M. Korpach; Susanne Åkesson; Marja H. Bakermans; Erin M. Bayne; Thomas J. Benson; Giovanni Boano; R. Mark Brigham; Simon S. Christiansen; Greg J. Conway; Christina M. Davy; Ruben Evens; et al. (Journal of Biogeography, 2025)
Aim To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location North and South America; Europe and Africa. Taxon Eastern whip‐poor‐will ( Antrostomus vociferus ), Common nighthawk ( Chordeiles minor ) and European nightjar ( Caprimulgus europaeus ). Methods We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding ( n = 3388) and wintering ( n = 189) locations. Results All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering‐site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding‐ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.

Forest Topsoil Organic Carbon Declines Under Ash Dieback - Fiona M. Seaton; David A. Robinson; Claire M. Wood; Clare M. H. Benskin; Rebecca L. Rowe; Karen Hornigold; Keith J. Kirby; Chris Nichols; Simon M. Smart (Global Change Biology, 2025)
Tree diseases are increasingly affecting woodland ecosystems across the world. However, the impact of these diseases upon the soil, and in particular soil carbon, is still poorly understood. Here we present the results of a field survey of ~100 woodlands across Great Britain measured in 1971, 2001 and 2022 and evaluate the fifty‐year trend in topsoil (0–15 cm) carbon based upon measurements of soil organic matter (SOM) and the impact of Hymenoscyphus fraxineus (ash dieback). To better represent the full SOM distribution, including the extremely high SOM measurements, we adopt a Beta mixture modelling approach within a Bayesian framework. Across all woodlands, comprising ~1,500 plots per survey, average SOM remained constant across the fifty‐year time series. However, the 311 plots with ash dieback had lower SOM in the most recent survey compared to the 328 plots with ash trees present but no dieback recorded, due to a slight decline in SOM under ash dieback. This resulted in plots with ash dieback having a modelled mean SOM of 12.2% compared to 13.4% in plots without ash dieback, a difference of 1.23 percentage points (95% CI 0.25–2.21). Ash dieback was more likely to be recorded in plots that had higher soil pH pre‐ash dieback invasion, but the decline in SOM under ash dieback was not explained by changes in soil pH or changes in the ground flora composition. Converting our results to soil C and extrapolating for broadleaved woodland across the entirety of Great Britain, the total amount of topsoil carbon lost to date due to ash dieback could be 6 MtCO 2 (± 4 s.d.). Our results show the importance of understanding the impacts of tree disease when considering current and future woodland carbon dynamics.

Range‐Wide Genomic Analysis Reveals Regional and Meta‐Population Dynamics of Decline and Recovery in the Grey Seal - Morgan L. McCarthy; Kristina M. Cammen; Sandra M. Granquist; Rune Dietz; Jonas Teilmann; Charlotte Bie Thøstesen; Simon Kjeldgaard; Mia Valtonen; Mervi Kunnasranta; Bjørn Munro Jenssen; Markus P. Ahola; Britt‐Marie Bäcklin; et al. (Molecular Ecology, 2025)
Wildlife populations globally have experienced widespread historical declines due to anthropogenic and environmental impacts, yet for some species, contemporary management and conservation programmes have enabled recent recovery. The impacts of decline and recovery on genomic diversity and, vice versa, the genetic factors that contribute to conservation success or failure are rich areas for inquiry, with implications for shaping how we manage species into the future. To comprehensively characterise these processes in natural systems requires range‐wide sampling and international collaboration, particularly for species with wide dispersal capabilities, broad geographic distributions, and complex regional metapopulation dynamics. Here, we present the first range‐ and genome‐wide population genomic analysis of grey seals based on 3812 nuclear SNPs genotyped in 188 samples from 17 localities. Our analyses support the existence of three main grey seal populations centred in the NW Atlantic, NE Atlantic and Baltic Sea, and point to the existence of previously unrecognised substructure within the NE Atlantic. We detected remarkably low levels of genetic diversity in the NW Atlantic population, and demographic analyses revealed a turbulent history of NE Atlantic and Baltic Sea grey seals, with bottlenecks in the Middle Ages and the 20th century due to hunting and habitat alterations. We found some localities deviated from isolation by distance patterns, likely reflecting wide‐scale metapopulation dynamics associated with recolonisation and recovery in regions where they were historically extirpated. We identify at least six grey seal genetic populations and reveal marked genetic effects of past declines and recent recovery across the species' range.

Decreasing Stem Growth in Common European Tree Species Despite Earlier Growth Onset - Arun K. Bose; Sophia Etzold; Katrin Meusburger; Arthur Gessler; Andri Baltensweiler; Sabine Braun; Nina Buchmann; J. Julio Camarero; Matthias Haeni; Ansgar Kahmen; Richard L. Peters; Frank J. Sterck; et al. (Global Change Biology, 2025)
Recent findings suggest that global warming is altering the timing of trees' phenological activities, including earlier emergence from winter dormancy. While early‐season warming can boost carbon uptake, tree growth does not seem to benefit. The underlying mechanisms and the altered intra‐ and inter‐annual growth dynamics, as well as their interaction with environmental factors, remain poorly understood. We analysed daily‐resolved dendrometer data from 228 trees across 48 Swiss forest sites over 2012–2022 to examine stem radial growth timing, intra‐ and inter‐annual dynamics, and environmental controls for five tree species. Our results showed that higher winter and spring temperatures induced an earlier accomplishment of annual growth—indicating earlier growth start—but did not increase the total annual growth in any of the species studied. In contrast, we found a significant negative growth trend for P. abies , A. alba , and F. sylvatica across a wide climatic gradient. The reduction in growth was associated with the decrease in the number of days with growth. The positive effect of higher temperatures in spring was canceled out by a negative effect towards the end of the growth period. Overall, such a negative effect of increased temperature at an annual scale was strongest in P. sylvestris and persisted over 2012–2022. The effect size of temperature was larger in explaining weekly growth compared to the effect sizes of precipitation or of soil water potential. This indicates that temperature, as an integrating indicator of growing conditions, can capture the variability of growth on a weekly time scale, which is less the case on a daily or hourly resolution. Overall, our results challenge the expectation that climate warming will offset carbon losses caused by heat and drought with a longer growing season. Our findings from five of the most common tree species in Central Europe do not support this assumption.

Indoor air sampling for detection of viral nucleic acids - Lennart J. Justen; Simon L. Grimm; Kevin M. Esvelt; William J. Bradshaw (Journal of Aerosol Science, 2025)

Antiviral siRNA delivered using attenuated, anthrax toxin protects cells from the cytopathic effects of Zika virus - Benedita K. L. Feron; Timothy Gomez; Natalie C. Youens; Nourhan A. M. Mahmoud; Hadeer K. S. Abdelrahman; Joachim J. Bugert; Simon C. W. Richardson (Virus Genes, 2025)
Curative drugs are needed for the treatment of viral infections. Small interfering (si)RNA offer such a prospect but require the development of safe, effective and non-hepatotropic subcellular delivery systems. Here, 5 candidate siRNA molecules targeting defined sequences within the Zika Virus (ZIKV) genome were assayed for their ability to reduce ZIKV induced cytopathic effects in vitro. The protection of Huh-7 cells from ZIKV cytopathic effects was recorded after electroporation and the siRNA Feron-Zv2, resulting in 122.7 ± 5.3% cell viability ( n = 3 ± standard error of the mean (SEM), 100 nM siRNA) after exposure to ZIKV relative to a virus treated control (35.2 ± 7.1% cell viability ( n = 3 ± SEM)). Protection of BHK-21 cells was recorded after transfection with an attenuated anthrax toxin containing an RNA binding domain. Treatment with Feron-Zv4 resulted in 75.1 ± 2.9% cell viability ( n = 3 ± SEM, 25 nM siRNA) after exposure to ZIKV. This protection was mirrored by a system containing octameric PA where a maximum of 86.2 ± 4.4% cell viability was reported ( n = 3 ± SEM, 75 nM siRNA) after treatment with Feron-Zv2. Scrambled siRNA afforded no measurable protection. Here we report for the first time that siRNA delivered by either attenuated anthrax toxin or octamer forming ATx can protect mammalian cells from ZIKV cytopathic effects.

Genomic Analysis Reveals a New Cryptic Taxon Within the Anopheles gambiae Complex With a Distinct Insecticide Resistance Profile in the Coast of East Africa - Sophia H. Mwinyi; Kelly L. Bennett; Sanjay C. Nagi; Bilali Kabula; Johnson Matowo; David Weetman; Francesco Baldini; Simon A. Babayan; Martin J. Donnelly; Chris S. Clarkson; Fredros O. Okumu; Alistair Miles (Molecular Ecology, 2025)
Anopheles mosquitoes are major malaria vectors, encompassing several species complexes with diverse life histories, transmission risks and insecticide resistance profiles that challenge malaria control efforts. This study investigated the genetic structure and insecticide resistance profiles of Anopheles gambiae complex mosquitoes in Tanzania. We analysed whole‐genome sequence data of 300 mosquitoes collected between 2012 and 2015 across four regions in northern Tanzania and identified An. gambiae s.s., An. arabiensis and a distinct taxonomic group that was previously unknown. This distinct taxon has a unique profile of genetic diversity and appears restricted to the coastal region, and we refer to it as the Pwani molecular form. Analysis of insecticide resistance based on target‐site mutations and copy number variations (CNV) showed that these markers were strikingly absent from the Pwani molecular form in contrast to other taxa. Our analysis also revealed a pattern of geographical isolation in the An. gambiae s.s. populations, with samples from the north‐western site (Muleba) clustering separately from those collected in the north‐eastern site (Muheza). These geographically isolated subpopulations also had differing resistance and selection profiles, with An. gambiae s.s. from the north‐western site showing genomic evidence of higher resistance to pyrethroids compared with the north‐eastern population. Conversely, An. arabiensis showed no geographical population structuring, with a similar insecticide resistance profile across all sampling locations, suggesting unrestricted gene flow. Our findings underscore the need to incorporate genetic data into malaria vector surveillance and control decisions and could inform the development and deployment of new interventions.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Earth's most needed uncultivated aquatic prokaryotes - Sophie A. Simon; Vera Aschmann; Annika Behrendt; Michael Hügler; Lisa M. Engl; Marion Pohlner; Sönke Rolfes; Thorsten Brinkhoff; Bert Engelen; Martin Könneke; Luis M. Rodriguez-R; Till L.V. Bornemann; et al. (Water Research, 2025)

Correction to: Persistent declines in sightings of manta and devil rays (mobulidae) at a global hotspot in southern mozambique - Stephanie K. Venables; Christoph A. Rohner; Anna L. Flam; Simon J. Pierce; Andrea D. Marshall (Environmental Biology of Fishes, 2025)

Persistent declines in sightings of manta and devil rays (Mobulidae) at a global hotspot in southern Mozambique - Stephanie K. Venables; Christoph A. Rohner; Anna L. Flam; Simon J. Pierce; Andrea D. Marshall (Environmental Biology of Fishes, 2025)
Mobulid rays are among the most vulnerable of chondrichthyans to overexploitation by fisheries due to their low population growth rates. In locations where catch data are lacking, long-term sightings data can provide valuable insight to infer population trends and status. We recorded underwater sighting data of reef manta rays ( Mobula alfredi ), oceanic manta rays ( M. birostris ), and shorthorned pygmy devil rays ( M. kuhlii ) between 2003 and 2023 in the waters off Praia do Tofo in the Inhambane Province, southern Mozambique, one of the major global hotspots for these rays. We modelled sightings data using a hierarchical generalised linear mixed model framework to account for a suite of environmental variables when examining temporal trends. Raw trend models including only ‘year’ as a predictor showed a 99% decline in sightings of reef manta rays, a 92.5% decline in oceanic manta ray sightings, and an 81.3% decline in devil ray sightings over the 20-year study period. The declining trends persisted for reef and oceanic manta rays once a suite of temporal and environmental variables were accounted for, indicating that the declines were driven by external factors not tested in the models. For shorthorned pygmy devil rays, models that incorporated environmental variables did not retain year as a significant predictor and showed a reduced overall decline in sightings of 36.5%. This indicates that the tested predictors were responsible for approximately half of the observed decline. Anthropogenic factors, particularly fisheries mortality, are likely to have played a significant role in the declining sightings of these three Threatened species. Improved conservation and management measures at a national and international level are critical to prevent further declines, which may otherwise lead to localised extinction.

Adaptive capacities of inland fisheries facing anthropogenic pressures - Gretchen L. Stokes; Samuel J. Smidt; Emily L. Tucker; Matteo Cleary; Simon Funge-Smith; John Valbo‐Jørgensen; Benjamin S. Lowe; Abigail J. Lynch (Global Environmental Change, 2025)

Postglacial Recolonization of the Southern Ocean by Elephant Seals Occurred From Multiple Glacial Refugia - Andrew A. Berg; Megan Askew; Frederik V. Seersholm; Alexander J. F. Verry; A. Rus Hoelzel; Andreanna Welch; Karen Greig; Richard Walter; Michael Knapp; Axel Barlow; Johanna L. A. Paijmans; Jonathan M. Waters; et al. (Global Change Biology, 2025)
The Southern Ocean is warming more rapidly than other parts of our planet. How this region's endemic biodiversity will respond to such changes can be illuminated by studying past events through genetic analyses of time‐series data sets, including historic and fossil remains. Archaeological and subfossil remains show that the southern elephant seal ( Mirounga leonina ) was common along the coasts of Australia and New Zealand in the recent past. This species is now mostly confined to sub‐Antarctic islands and the southern tip of South America. We analyzed ancient seal samples from Australia (Tasmania), New Zealand and the Antarctic mainland to examine how southern elephant seals have responded to a changing climate and anthropogenic pressures during the Holocene. Our analyses show that these seals formed part of a broader Australasian lineage, comprising seals from all sampled locations from the south Pacific sector of the Southern Ocean. Our study demonstrates that southern elephant seal populations have dynamically altered both range and population sizes under climatic and human pressures over surprisingly short evolutionary timeframes for such a large, long‐lived mammal.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Effect of short-term dopamine reduction on insulin sensitivity and post-prandial insulin and glucose responses in Standardbred horses - Nicolas C. Galinelli; Nicholas J. Bamford; Madison L. Erdody; Tobias Warnken; Melody A. de Laat; Martin N. Sillence; Patricia A. Harris; Simon R. Bailey (Domestic Animal Endocrinology, 2025)

Physiological and metabolic effects of short-term dopamine reduction in healthy horses using a tyrosine hydroxylase inhibitor (alpha-methyl-para-tyrosine) - Nicolas C. Galinelli; Nicholas J. Bamford; Madison L. Erdody; Tobias Warnken; Melody A. de Laat; Martin N. Sillence; Patricia A. Harris; Simon R. Bailey (Domestic Animal Endocrinology, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Escaping the cohort of concern: in vitro experimental evidence supports non-mutagenicity of N-nitroso-hydrochlorothiazide - R. D. Gandhi; S. Hickert; Y. Hoevelmann; C. D. Mee; J. Schlingemann; A. Adams; A. Blanazs; S. Simon; J. Elloway; L. Rigger; A. Teasdale; C. V. Beaumont; et al. (Archives of Toxicology, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Effects of climate warming on energetics and habitat of the world's largest marine ectotherm - Samantha D. Reynolds; Craig E. Franklin; Bradley M. Norman; Anthony J. Richardson; Jason D. Everett; David S. Schoeman; Craig R. White; Christopher L. Lawson; Simon J. Pierce; Christoph A. Rohner; Steffen S. Bach; Francesco G. Comezzi; et al. (Science of The Total Environment, 2024)

Increasing oil content in Brassica oilseed species - Randall J. Weselake; David A. Fell; Xiaoyu Wang; Simon Scofield; Guanqun Chen; John L. Harwood (Progress in Lipid Research, 2024)

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2024) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Stuart G. Siddell; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Bas E. Dutilh; Juliana Freitas-Astúa; María Laura García; et al. (Archives of Virology, 2024)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2024. The entire ICTV membership was invited to vote on 203 taxonomic proposals that had been approved by the ICTV Executive Committee (EC) in July 2023 at the 55th EC meeting in Jena, Germany, or in the second EC vote in November 2023. All proposals were ratified by online vote. Taxonomic additions include one new phylum ( Ambiviricota ), one new class, nine new orders, three new suborders, 51 new families, 18 new subfamilies, 820 new genera, and 3547 new species (excluding taxa that have been abolished). Proposals to complete the process of species name replacement to the binomial (genus + species epithet) format were ratified. Currently, a total of 14,690 virus species have been established.

Malnutrition Risk Among Older Americans Act (OAA) Nutrition Program Participants in 2022 - L. McGrath; J. Gahche; J. Dwyer; M. Arensberg; S. Chao; J. Simon; L. Borth (Journal of the Academy of Nutrition and Dietetics, 2024)

Random and systematic uncertainty in ship‐based seawater carbonate chemistry observations - Brendan R. Carter; Jonathan D. Sharp; Maribel I. García‐Ibáñez; Ryan J. Woosley; Michael B. Fong; Marta Álvarez; Leticia Barbero; Simon L. Clegg; Regina Easley; Andrea J. Fassbender; Xinyu Li; Katelyn M. Schockman; et al. (Limnology and Oceanography, 2024)
Seawater carbonate chemistry observations are increasingly necessary to study a broad array of oceanographic challenges such as ocean acidification, carbon inventory tracking, and assessment of marine carbon dioxide removal strategies. The uncertainty in a seawater carbonate chemistry observation comes from unknown random variations and systematic offsets. Here, we estimate the magnitudes of these random and systematic components of uncertainty for the discrete open‐ocean carbonate chemistry measurements in the Global Ocean Data Analysis Project 2022 update (GLODAPv2.2022). We use both an uncertainty propagation approach and a carbonate chemistry measurement “inter‐consistency” approach that quantifies the disagreement between measured carbonate chemistry variables and calculations of the same variables from other carbonate chemistry measurements. Our inter‐consistency analysis reveals that the seawater carbonate chemistry measurement community has collected and released data with a random uncertainty that averages about 1.7 times the uncertainty estimated by propagating the desired “climate‐quality” random uncertainties. However, we obtain differing random uncertainty estimates for subsets of the available data, with some subsets seemingly meeting the climate‐quality criteria. We find that seawater pH measurements on the total scale do not meet the climate‐quality criteria, though the inter‐consistency of these measurements improves (by 38%) when limited to the subset of measurements made using purified indicator dyes. We show that GLODAPv2 adjustments improve inter‐consistency for some subsets of the measurements while worsening it for others. Finally, we provide general guidance for quantifying the random uncertainty that applies for common combinations of measured and calculated values.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Exposing illegal hunting and wildlife depletion in the world's largest tropical country through social media data - Hani R. El Bizri; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Lauren Coad; Thais Queiroz Morcatty; Gabriel Favero Massocato; Arnaud L. J. Desbiez; João Vitor Campos‐Silva; Daniel Zani La Laina; José Maurício Barbanti Duarte; et al. (Conservation Biology, 2024)
Globally, illegal sport hunting can threaten prey populations when unregulated. Due to its covert nature, illegal sport hunting poses challenges for data collection, hindering efforts to understand the full extent of its impacts. We gathered social media data to analyze patterns of illegal sport hunting and wildlife depletion across Brazil. We collected data for 2 years (2018–2020) across 5 Facebook groups containing posts depicting pictures of illegal sport hunting events of native fauna. We described and mapped these hunting events by detailing the number of hunters involved, the number of species, the mean body mass of individuals, and the number and biomass of individuals hunted per unit area, stratified by Brazilian biome. We also examined the effects of defaunation on hunting yield and composition via regression models, rank–abundance curves, and spatial interpolation. We detected 2046 illegal sport hunting posts portraying the hunting of 4658 animals (∼29 t of undressed meat) across all 27 states and 6 natural biomes of Brazil. Of 157 native species targeted by hunters, 19 are currently threatened with extinction. We estimated that 1414 hunters extracted 3251 kg/million km 2 . Some areas exhibited more pronounced wildlife depletion, in particular the Atlantic Forest and Caatinga biomes. In these areas, there was a shift from large mammals and reptiles to small birds as the main targeted taxa, and biomass extracted per hunting event and mean body mass across all taxonomic groups were lower than in other areas. Our results highlight that illegal sport hunting adds to the pressures of subsistence hunting and the wild meat trade on Brazil's wildlife populations. Enhanced surveillance efforts are needed to reduce illegal sport hunting levels and to develop well‐managed sustainable sport hunting programs. These can support wildlife conservation and offer incentives for local communities to oversee designated sport hunting areas.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Synthesis of results for Brine Availability Test in Salt (BATS) DECOVALEX-2023 Task E - Kristopher L. Kuhlman; Jeroen Bartol; Steven J. Benbow; Michelle Bourret; Oliver Czaikowski; Eric Guiltinan; Kyra Jantschik; Richard Jayne; Simon Norris; Jonny Rutqvist; Hua Shao; Philip H. Stauffer; et al. (Geomechanics for Energy and the Environment, 2024)

Mutant PTPMT1 disrupts cardiolipin metabolism and mitochondrial bioenergetics leading to a neurodevelopmental syndrome - Micol Falabella; Chiara Pizzamiglio; Luis Carlos Tabara; Benjamin Munro; Mohamed S. Abdel-Hamid; Ece Sonmezler; William L. Macken; Shanti Lu; Lisa Tilokani; Padraig J. Flannery; Simon A.S. Pope; Simon J.R. Heales; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Every breath you take: High concentration of breathable microplastics in indoor environments - L. Maurizi; L. Simon-Sánchez; A. Vianello; A.H. Nielsen; J. Vollertsen (Chemosphere, 2024)

Marine eDNA sampling from submerged surfaces with paint rollers - Simon Jarman; Jason B. Alexander; Kathryn L. Dawkins; Sherralee S. Lukehurst; Georgia M. Nester; Shaun Wilkinson; Michael J. Marnane; Justin I. McDonald; Travis S. Elsdon; Euan S. Harvey (Marine Genomics, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Adult telomere length is positively correlated with survival and lifetime reproductive success in a wild passerine - Heung Ying Janet Chik; Maria‐Elena Mannarelli; Natalie dos Remedios; Mirre J. P. Simons; Terry Burke; Julia Schroeder; Hannah L. Dugdale (Molecular Ecology, 2024)
Explaining variation in individual fitness is a key goal in evolutionary biology. Recently, telomeres, repeating DNA sequences capping chromosome ends, have gained attention as a biomarker for body state, physiological costs, and senescence. Existing research has provided mixed evidence for whether telomere length correlates with fitness, including survival and reproductive output. Moreover, few studies have examined how the rate of change in telomere length correlates with fitness in wild populations. Here, we intensively monitored an insular population of house sparrows, and collected longitudinal telomere and life history data (16 years, 1225 individuals). We tested whether telomere length and its rate of change predict fitness measures, namely survival, lifespan and annual and lifetime reproductive effort and success. Telomere length positively predicted short‐term survival, independent of age, but did not predict lifespan, suggesting either a diminishing telomere length—survival correlation with age or other extrinsic factors of mortality. The positive association of telomere length with survival translated into reproductive benefits, as birds with longer telomeres produced more genetic recruits, hatchlings and reared more fledglings over their lifetime. In contrast, there was no association between telomere dynamics and annual reproductive output, suggesting telomere dynamics might not reflect the costs of reproduction in this population, potentially masked by variation in individual quality. The rate of change of telomere length did not correlate with neither lifespan nor lifetime reproductive success. Our results provide further evidence that telomere length correlates with fitness, and contribute to our understanding of the selection on, and evolution of, telomere dynamics.

Enhancing Assessments of Coastal Wetland Migration Potential with Sea-level Rise: Accounting for Uncertainty in Elevation Data, Tidal Data, and Future Water Levels - Nicholas M. Enwright; Michael J. Osland; Hana R. Thurman; Claire E. McHenry; William C. Vervaeke; Brett A. Patton; Davina L. Passeri; Jason M. Stoker; Richard H. Day; Bethanie M. Simons (Estuaries and Coasts, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Drone-based photogrammetry reveals differences in humpback whale body condition and mass across North Atlantic foraging grounds - Chelsi Napoli; Nathan Hirtle; Julia Stepanuk; Fredrik Christiansen; Eleanor I. Heywood; Thomas J. Grove; Alyssa Stoller; Flordespina Dodds; Maria Glarou; Marianne H. Rasmussen; Gina L. Lonati; Kimberley T.A. Davies; et al. (Frontiers in Marine Science, 2024)
Baleen whales are key consumers in marine ecosystems and can serve as ecosystem sentinels. Body condition, defined as an individual’s energy stores relative to its structural size, can provide a useful proxy for health in baleen whales. As capital breeders, important life history events in baleen whales such as seasonal migrations and reproduction depend on having sufficient energy stores. Spatiotemporal variability of body condition of baleen whales can reflect differences in energy accumulated during the foraging season. Here we assess and compare the body condition and mass of humpback whales ( Megaptera novaeangliae) across four different foraging areas from the West Indies distinct population segment in the Northwest Atlantic. Morphometric measurements of humpback whales were obtained using unoccupied aerial systems (UAS, or drones) from the New York Bight, the Gulf of Maine, Iceland, and Greenland. Uncertainty in morphometric estimates was incorporated and propagated using a bootstrapping approach. Measurements were used to estimate body volume and calculate a body condition index (BCI) for each individual whale. Since body mass is a key parameter for understanding animal physiology and bioenergetics, we further compared whale body mass to body size between foraging areas by converting body volume to body mass using estimates of tissue density from tagging studies. BCI showed significant differences between foraging areas with a large effect size (ANCOVA: mean η 2 = 0.168; all p< 0.001) when incorporating day of year and year as covariates. Humpback whales in the Gulf of Maine showed significantly higher BCI than those in the New York Bight, Iceland, and Greenland. Standardized Major Axis (SMA) regressions comparing log-log relationships of both body volume and body mass, respectively, to total length reinforced these results. Humpback whales in the Gulf of Maine showed significantly higher elevation in the SMAs than those in the other study regions (p<0.001), implying that humpback whales foraging in the Gulf of Maine accumulated greater energy reserves for a given body size. Estimates of body mass indicate that for a given body length, humpback whales in the Gulf of Maine have an 18% greater body mass than those in the New York Bight, Iceland, or Greenland. Regional differences in prey availability or anthropogenic threats could contribute to the observed patterns in body condition. Our findings highlight the importance of regional environmental factors to the nutritional health of baleen whales.

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Effect of crustal stress state on magmatic stalling and ascent: case study from Puyehue-Cordón Caulle, Chile - Katy J. Chamberlain; Daniel J. Morgan; Luis E. Lara; Richard Walshaw; Joe Gardner; Simon Chenery; Ian L. Millar; Doris Wagner (Bulletin of Volcanology, 2024)
The Southern Volcanic Zone (SVZ) in Chile is an active continental arc with a complex history of volcanism, where a range of magmatic compositions have been erupted in a variety of styles. In the Central SVZ, both monogenetic and polygenetic volcanoes exist, in close proximity to the Liquiñe-Ofqui Fault System (LOFS), but with variable local stress states. Previous studies have inferred varying crustal storage timescales, controlled by the orientation of volcanic centres relative to the N-S striking LOFS and σ HMax in this region. To assess the relationship between volcanism and crustal stress states affected by large-scale tectonic structures and edifice controls, we present whole rock geochemical data, to ensure consistency in source dynamics and crustal processing, mineral-specific compositional data, thermobarometry, and Fe–Mg diffusion modelling in olivine crystals from mafic lavas, to assess ascent timescales, from the stratovolcanic edifice of Puyehue-Cordón Caulle and proximal small eruptive centres. Textural observations highlight differences in crystal maturation timescales between centres in inferred compression, transpression, and extension, yet source melting dynamics remain constant. Only samples from the stratovolcanic edifice (in regional compression) preserve extensive zonation in olivine macrocrysts; these textures are generally absent from proximal small eruptive centres in transtension or extension. The zonation in olivines from stratovolcanic lavas yields timescales on the order of a few days to a few weeks, suggesting that even in environments which inhibit ascent, timescales between unrest and eruption of mafic magmas may be short. Significantly, high-resolution compositional profiles from olivine grains in the studied samples record evidence for post-eruptive growth and diffusion, highlighting the importance of careful interpretation of diffusion timescales from zoned minerals in more slowly cooled lavas when compared with tephra samples.

Oscillation rheology, calorimetry and computed tomography: A practical toolkit combination of qualification for real poly(ethylene terephthalate) waste - L. Simon-Stőger; A. Kovács; M. Szigeti; J. Bobek-Nagy; R. Kurdi; Cs. Varga (Journal of Cleaner Production, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Effect of early peptide diets on European sea bass (Dicentrarchus labrax) skeletal development - A. Printzi; S. Jodet; V. Fournier; S. Collet; L. Madec; V. Simon; J.-L. Zambonino-Infante; G. Koumoundouros; D. Mazurais (Aquaculture, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

The impact of changing the cut-off threshold of the interferon-gamma (IFN-γ) assay for diagnosing bovine tuberculosis in Ireland - Jamie M. Madden; Jim O’Donovan; Miriam Casey-Bryars; James Sweeney; Locksley L. Messam; Conor G. McAloon; Simon J. More; Kevin Kenny; Eoin Ryan; Eamonn Gormley (Preventive Veterinary Medicine, 2024)

Denitrification, anammox, and DNRA in oligotrophic continental shelf sediments - Henry L. S. Cheung; Jenny R. Hillman; Conrad A. Pilditch; Candida Savage; Isaac R. Santos; Ronnie N. Glud; Francisco J. A. Nascimento; Simon F. Thrush; Stefano Bonaglia (Limnology and Oceanography, 2024)
Continental shelf sediments are considered hotspots for nitrogen (N) removal. While most investigations have quantified denitrification in shelves receiving large amounts of anthropogenic nutrient supply, we lack insight into the key drivers of N removal on oligotrophic shelves. Here, we measured rates of N removal through denitrification and anammox by the revised‐isotope pairing technique (r‐IPT) along the Northeastern New Zealand shelf. Denitrification dominated total N 2 production at depths between 30 and 128 m with average rates (± SE) ranging from 65 ± 28 to 284 ± 72 μ mol N m −2 d −1 . N 2 production by anammox ranged from 3 ± 1 to 28 ± 11 μ mol N m −2 d −1 and accounted for 2–19% of total N 2 production. DNRA was negligible in these oligotrophic settings. Parallel microbial community analysis showed that both Proteobacteria and Planctomycetota were key taxa driving denitrification. Denitrification displayed a negative correlation with oxygen penetration depth, and a positive correlation with macrofauna abundance. Our denitrification rates were comparable to oligotrophic shelves from the Arctic, but were lower than those from nutrient‐rich Pacific and Atlantic shelves. Based on our results and existing IPT measurements, the global shelf denitrification rate was reassessed to be 53.5 ± 8.1 Tg N yr −1 , equivalent to 20 ± 2% of marine N removal. We suggest that previous estimates of global shelf N loss might have been overestimated due to sampling bias toward areas with high N loads in the Northern Hemisphere.

Experiences of emotional eating in an Acceptance and Commitment Therapy based weight management intervention (SWiM): A qualitative study - Laura Kudlek; Rebecca A. Jones; Carly Hughes; Robbie Duschinsky; Andrew Hill; Rebecca Richards; Megan Thompson; Ann Vincent; Simon J. Griffin; Amy L. Ahern (Appetite, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Mean reef fish body size decreases towards warmer waters - Amy Rose Coghlan; Julia L. Blanchard; Simon Wotherspoon; Rick D. Stuart‐Smith; Graham J. Edgar; Neville Barrett; Asta Audzijonyte (Ecology Letters, 2024)
Aquatic ectotherms often attain smaller body sizes at higher temperatures. By analysing ~15,000 coastal‐reef fish surveys across a 15°C spatial sea surface temperature (SST) gradient, we found that the mean length of fish in communities decreased by ~5% for each 1°C temperature increase across space, or 50% decrease in mean length from 14 to 29°C mean annual SST. Community mean body size change was driven by differential temperature responses within trophic groups and temperature‐driven change in their relative abundance. Herbivores, invertivores and planktivores became smaller on average in warmer temperatures, but no trend was found in piscivores. Nearly 25% of the temperature‐related community mean size trend was attributable to trophic composition at the warmest sites, but at colder temperatures, this was

Habitat structure shapes temperate reef assemblages across regional environmental gradients - Tim Jackson-Bué; Ally J. Evans; Peter J. Lawrence; Paul R. Brooks; Sophie L. Ward; Stuart R. Jenkins; Pippa J. Moore; Tasman P. Crowe; Simon P. Neill; Andrew J. Davies (Science of The Total Environment, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Uncertainty sources for measurable ocean carbonate chemistry variables - Brendan R. Carter; Jonathan D. Sharp; Andrew G. Dickson; Marta Álvarez; Michael B. Fong; Maribel I. García‐Ibáñez; Ryan J. Woosley; Yuichiro Takeshita; Leticia Barbero; Robert H. Byrne; Wei‐Jun Cai; Melissa Chierici; et al. (Limnology and Oceanography, 2024)
The ocean carbonate system is critical to monitor because it plays a major role in regulating Earth's climate and marine ecosystems. It is monitored using a variety of measurements, and it is commonly understood that all components of seawater carbonate chemistry can be calculated when at least two carbonate system variables are measured. However, several recent studies have highlighted systematic discrepancies between calculated and directly measured carbonate chemistry variables and these discrepancies have large implications for efforts to measure and quantify the changing ocean carbon cycle. Given this, the Ocean Carbonate System Intercomparison Forum (OCSIF) was formed as a working group through the Ocean Carbon and Biogeochemistry program to coordinate and recommend research to quantify and/or reduce uncertainties and disagreements in measurable seawater carbonate system measurements and calculations, identify unknown or overlooked sources of these uncertainties, and provide recommendations for making progress on community efforts despite these uncertainties. With this paper we aim to (1) summarize recent progress toward quantifying and reducing carbonate system uncertainties; (2) advocate for research to further reduce and better quantify carbonate system measurement uncertainties; (3) present a small amount of new data, metadata, and analysis related to uncertainties in carbonate system measurements; and (4) restate and explain the rationales behind several OCSIF recommendations. We focus on open ocean carbonate chemistry, and caution that the considerations we discuss become further complicated in coastal, estuarine, and sedimentary environments.

Combining multiple investigative approaches to unravel functional responses to global change in the understorey of temperate forests - Dries Landuyt; Michael P. Perring; Haben Blondeel; Emiel De Lombaerde; Leen Depauw; Eline Lorer; Sybryn L. Maes; Lander Baeten; Laurent Bergès; Markus Bernhardt‐Römermann; Guntis Brūmelis; Jörg Brunet; et al. (Global Change Biology, 2024)
Plant communities are being exposed to changing environmental conditions all around the globe, leading to alterations in plant diversity, community composition, and ecosystem functioning. For herbaceous understorey communities in temperate forests, responses to global change are postulated to be complex, due to the presence of a tree layer that modulates understorey responses to external pressures such as climate change and changes in atmospheric nitrogen deposition rates. Multiple investigative approaches have been put forward as tools to detect, quantify and predict understorey responses to these global‐change drivers, including, among others, distributed resurvey studies and manipulative experiments. These investigative approaches are generally designed and reported upon in isolation, while integration across investigative approaches is rarely considered. In this study, we integrate three investigative approaches (two complementary resurvey approaches and one experimental approach) to investigate how climate warming and changes in nitrogen deposition affect the functional composition of the understorey and how functional responses in the understorey are modulated by canopy disturbance, that is, changes in overstorey canopy openness over time. Our resurvey data reveal that most changes in understorey functional characteristics represent responses to changes in canopy openness with shifts in macroclimate temperature and aerial nitrogen deposition playing secondary roles. Contrary to expectations, we found little evidence that these drivers interact. In addition, experimental findings deviated from the observational findings, suggesting that the forces driving understorey change at the regional scale differ from those driving change at the forest floor (i.e., the experimental treatments). Our study demonstrates that different approaches need to be integrated to acquire a full picture of how understorey communities respond to global change.

Global responses to the COVID-19 pandemic by recreational anglers: considerations for developing more resilient and sustainable fisheries - J. Robert Britton; Adrian C. Pinder; Josep Alós; Robert Arlinghaus; Andy J. Danylchuk; Wendy Edwards; Kátia M. F. Freire; Casper Gundelund; Kieran Hyder; Ivan Jarić; Robert Lennox; Wolf-Christian Lewin; et al. (Reviews in Fish Biology and Fisheries, 2023)
The global COVID-19 pandemic resulted in many jurisdictions implementing orders restricting the movements of people to inhibit virus transmission, with recreational angling often either not permitted or access to fisheries and/or related infrastructure being prevented. Following the lifting of restrictions, initial angler surveys and licence sales suggested increased participation and effort, and altered angler demographics, but with evidence remaining limited. Here, we overcome this evidence gap by identifying temporal changes in angling interest, licence sales, and angling effort in world regions by comparing data in the ‘pre-pandemic’ (up to and including 2019); ‘acute pandemic’ (2020) and ‘COVID-acclimated’ (2021) periods. We then identified how changes can inform the development of more resilient and sustainable recreational fisheries. Interest in angling (measured here as angling-related internet search term volumes) increased substantially in all regions during 2020. Patterns in licence sales revealed marked increases in some countries during 2020 but not in others. Where licence sales increased, this was rarely sustained in 2021; where there were declines, these related to fewer tourist anglers due to movement restrictions. Data from most countries indicated a younger demographic of people who participated in angling in 2020, including in urban areas, but this was not sustained in 2021. These short-lived changes in recreational angling indicate efforts to retain younger anglers could increase overall participation levels, where efforts can target education in appropriate angling practices and create more urban angling opportunities. These efforts would then provide recreational fisheries with greater resilience to cope with future global crises, including facilitating the ability of people to access angling opportunities during periods of high societal stress.

Northerly range expansion and first confirmed records of the smalltooth sand tiger shark, Odontaspis ferox , in the United Kingdom and Ireland - David J. Curnick; Rob Deaville; Jenny R. Bortoluzzi; Luke Cameron; Jeanette E. L. Carlsson; Jens Carlsson; Haley R. Dolton; Cat A. Gordon; Phil Hosegood; Alicia Nilsson; Matthew W. Perkins; Kevin J. Purves; et al. (Journal of Fish Biology, 2023)
Three Odontaspis ferox (confirmed by mtDNA barcoding) were found in the English Channel and Celtic Sea in 2023 at Lepe, UK (50.7846, −1.3508), Kilmore Quay, Ireland (52.1714, −6.5937), and Lyme Bay, UK (50.6448, −2.9302). These are the first records of O. ferox in either country, and extend the species' range by over three degrees of latitude, to >52° N. They were ~275 (female), 433 (female), and 293 cm (male) total length, respectively. These continue a series of new records, possibly indicative of a climate change−induced shift in the species' range.

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Resource selection by New York City deer reveals the effective interface between wildlife, zoonotic hazards and humans - Meredith C. VanAcker; Vickie L. DeNicola; Anthony J. DeNicola; Sarah Grimké Aucoin; Richard Simon; Katrina L. Toal; Maria A. Diuk‐Wasser; Francesca Cagnacci (Ecology Letters, 2023)
Although the role of host movement in shaping infectious disease dynamics is widely acknowledged, methodological separation between animal movement and disease ecology has prevented researchers from leveraging empirical insights from movement data to advance landscape scale understanding of infectious disease risk. To address this knowledge gap, we examine how movement behaviour and resource utilization by white‐tailed deer ( Odocoileus virginianus ) determines blacklegged tick ( Ixodes scapularis ) distribution, which depend on deer for dispersal in a highly fragmented New York City borough. Multi‐scale hierarchical resource selection analysis and movement modelling provide insight into how deer's movements contribute to the risk landscape for human exposure to the Lyme disease vector– I. scapularis . We find deer select highly vegetated and accessible residential properties which support blacklegged tick survival. We conclude the distribution of tick‐borne disease risk results from the individual resource selection by deer across spatial scales in response to habitat fragmentation and anthropogenic disturbances.

Feasibility and acceptability of an acceptance-based guided self-help programme for weight loss maintenance - Julia Mueller; Rebecca A. Jones; Rebecca Richards; Jennifer Woolston; Fiona Whittle; Andrew J. Hill; Carly A. Hughes; Robbie Duschinsky; Stephen J. Sharp; Clare Boothby; Jennifer Bostock; Penny Breeze; et al. (Appetite, 2023)

Strengthening global-change science by integrating aeDNA with paleoecoinformatics - John W. Williams; Trisha L. Spanbauer; Peter D. Heintzman; Jessica Blois; Eric Capo; Simon J. Goring; Marie-Eve Monchamp; Laura Parducci; Jordan M. Von Eggers; Inger Greve Alsos; Chris Bowler; Marco J.L. Coolen; et al. (Trends in Ecology & Evolution, 2023)

A reduced potential for lameness bacterial transmission by Lucilia sericata larvae and flies through metamorphosis - Alice E. Curwen; Rebecca L. Still; Joseph W. Angell; Paul E. Eady; Stefan H. Millson; Gareth J. Staton; Nicholas J. Evans; Jennifer S. Duncan; Sheena C. Cotter; Simon R. Clegg (Research in Veterinary Science, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

DNA methylation markers of age(ing) in non‐model animals - Marianthi Tangili; Annabel J. Slettenhaar; Joanna Sudyka; Hannah L. Dugdale; Ido Pen; Per J. Palsbøll; Simon Verhulst (Molecular Ecology, 2023)
Inferring the chronological and biological age of individuals is fundamental to population ecology and our understanding of ageing itself, its evolution, and the biological processes that affect or even cause ageing. Epigenetic clocks based on DNA methylation (DNAm) at specific CpG sites show a strong correlation with chronological age in humans, and discrepancies between inferred and actual chronological age predict morbidity and mortality. Recently, a growing number of epigenetic clocks have been developed in non‐model animals and we here review these studies. We also conduct a meta‐analysis to assess the effects of different aspects of experimental protocol on the performance of epigenetic clocks for non‐model animals. Two measures of performance are usually reported, the R 2 of the association between the predicted and chronological age, and the mean/median absolute deviation (MAD) of estimated age from chronological age, and we argue that only the MAD reflects accuracy. R 2 for epigenetic clocks based on the HorvathMammalMethylChip4 was higher and the MAD scaled to age range lower, compared with other DNAm quantification approaches. Scaled MAD tended to be lower among individuals in captive populations, and decreased with an increasing number of CpG sites. We conclude that epigenetic clocks can predict chronological age with relatively high accuracy, suggesting great potential in ecological epigenetics. We discuss general aspects of epigenetic clocks in the hope of stimulating further DNAm‐based research on ageing, and perhaps more importantly, other key traits.

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Apatite evidence for a fluid-saturated, crystal-rich magma reservoir forming the Quellaveco porphyry copper deposit (Southern Peru) - Chetan L. Nathwani; Simon J. E. Large; Emily R. Brugge; Jamie J. Wilkinson; Yannick Buret (Contributions to Mineralogy and Petrology, 2023)
Large volume, intermediate-felsic magma reservoirs are the source of melt and mineralising fluids which generate porphyry copper deposits. Cooling and crystallisation of hydrous magmas drives the exsolution and expulsion of a magmatic volatile phase—a process which remains challenging to constrain in porphyry Cu systems where the record of magma volatile compositions is rarely preserved. Here, we use the halogen compositions of apatite inclusions shielded as inclusions within zircon to constrain volatile evolution in magma reservoirs which pre-date and are synchronous with porphyry Cu mineralisation at Quellaveco, Southern Peru. Geochemical and textural data confirm that the zircon-included apatites escaped re-equilibration with hydrothermal fluids, unlike apatites found in the groundmass of the same rocks. We, therefore, recommend that future studies attempting to reconcile magmatic volatile budgets using apatite in porphyry Cu systems should focus on apatite inclusions in zircon. By combining the apatite inclusion data with numerical modelling, we find evidence that the magma reservoir sourcing porphyry Cu mineralisation remained fluid-saturated for the entire period recorded by apatite crystallisation. By contrast, the pre-mineralisation batholith shows more variable, potentially fluid-undersaturated behaviour. Our modelling suggests that in order to attain the porphyry melt volatile compositions inferred from apatite, the magma reservoir must have exsolved a large proportion of its volatile budget, consistent with having been held at high crystallinity (40–60% crystals). This crystallisation interval coincides with peak chlorine and copper extraction from intermediate-felsic magmas, and would have permitted efficient fluid migration and accumulation at the roof of the system. We suggest that the storage of large-volume, long-lived, crystal-rich magma reservoirs in magmatic arcs may be a critical step in generating world-class porphyry copper deposits.

The mantle transition zone beneath eastern North America: Receiver functions and tomographic velocity models - Alexander L. Burky; Jessica C.E. Irving; Frederik J. Simons (Physics of the Earth and Planetary Interiors, 2023)

Insights from an AIMBE Workshop: Diversifying Paths to Academic Leadership - Beth L. Pruitt; Naomi C. Chesler; Rena Seltzer; Omolola Eniola-Adefeso; Susan S. Margulies; Maritza Salazar Campo; Scott I. Simon; Michele J. Grimm; Sarah Mandell; Andrew Alleyne; Jennifer L. West; Tejal A. Desai (Biomedical Engineering Education, 2023)
The American Institute for Medical and Biological Engineering (AIMBE) hosted a virtual symposium titled “Diversifying Paths to Academic Leadership” on January 27 and 28, 2022. The symposium sought to educate the community on the opportunities for and impact of leadership by biomedical engineering faculty, to encourage and invite women faculty, especially women of color, to consider and prepare to pursue leadership roles, to educate faculty on the expectations and duties of these roles, and to highlight experiences and paths to leadership of women engineering leaders. Here we review the main outcomes of the symposium to provide perspective on (1) personal visioning and positioning for leadership, (2) negotiating for success in leadership positions, and (3) leadership strategies for success specific to women faculty and where applicable, faculty of color.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Towards achieving circularity and sustainability in feeds for farmed blue foods - Stefanie M. Colombo; Koushik Roy; Jan Mraz; Alex H. L. Wan; Simon J. Davies; Sean M. Tibbetts; Margareth Øverland; David S. Francis; Melissa M. Rocker; Laura Gasco; Emma Spencer; Marc Metian; et al. (Reviews in Aquaculture, 2023)
The aims of this review are to describe the role of ‘blue‐food production’ (animals, plants and algae harvested from freshwater and marine environments) within a circular bioeconomy, discuss how such a framework can help the sustainability and resilience of aquaculture and to summarise key examples of novel nutrient sources that are emerging in the field of fed‐aquaculture species. Aquaculture now provides >50% of the global seafood supply, a share that is expected to increase to at least 60% within the next decade. Aquaculture is an important tool for reducing resource consumption in global protein production and increasing resilience to climate change and other global disruptions (i.e. pandemics, geo‐political instability). Importantly, blue foods also provide essential nutrition for a growing human population. Blue foods are helping to help the global goal of ‘zero hunger’ (United Nation's Sustainable Development Goal 2) while reducing the dependency on finite natural resources but further refinement and new solutions are needed to make the industry more ‘circular’ and sustainable, particularly with respect to sourcing raw materials for aquafeeds. This review describes the feed resources that are available or may be created within a circular bioeconomy framework, their role within the framework and in aquaculture and ultimately, how these resources contribute to de‐risking and establishing a resilient aquaculture production chain.

Prevalence of effective fisheries management in a developed nation and its link to stock sustainability - Nicholas J. Hill; Malcolm Haddon; Klaas Hartmann; L. Richard Little; Jeremy M. Lyle; Bradley R. Moore; Simon Nicol (Marine Policy, 2023)

Ocean circulation and biological processes drive seasonal variations of dissolved Al, Cd, Ni, Cu, and Zn on the Northeast Atlantic continental margin - Xue-Gang Chen; Dagmara Rusiecka; Martha Gledhill; Angela Milne; Amber L. Annett; Antony J. Birchill; Maeve C. Lohan; Simon Ussher; E. Malcolm S. Woodward; Eric P. Achterberg (Marine Chemistry, 2023)

Physical and biogeochemical controls on seasonal iron, manganese, and cobalt distributions in Northeast Atlantic shelf seas - Xue-Gang Chen; Dagmara Rusiecka; Martha Gledhill; Angela Milne; Amber L. Annett; Aaron Joseph Beck; Antony J. Birchill; Maeve C. Lohan; Simon Ussher; Eric P. Achterberg (Geochimica et Cosmochimica Acta, 2023)

The Anthropocene as an epoch is distinct from all other concepts known by this term: a reply to Swindles et al. (2023) - Martin J. Head; Colin N. Waters; Jan A. Zalasiewicz; Anthony D. Barnosky; Simon D. Turner; Alejandro Cearreta; Reinhold Leinfelder; Francine M.G. McCarthy; Daniel de B. Richter; Neil L. Rose; Yoshiki Saito; Davor Vidas; et al. (Journal of Quaternary Science, 2023)

Federated Analysis in COINSTAC Reveals Functional Network Connectivity and Spectral Links to Smoking and Alcohol Consumption in Nearly 2,000 Adolescent Brains - Harshvardhan Gazula; Kelly Rootes-Murdy; Bharath Holla; Sunitha Basodi; Zuo Zhang; Eric Verner; Ross Kelly; Pratima Murthy; Amit Chakrabarti; Debasish Basu; Subodh Bhagyalakshmi Nanjayya; Rajkumar Lenin Singh; et al. (Neuroinformatics, 2023)

Pre-eruptive rhyolite magma ascent rate is rapid and independent of eruption size: a case study from Ōkataina Volcanic Centre, Aotearoa New Zealand - Hannah C. Elms; Madison L. Myers; Alexander R. L. Nichols; Paul J. Wallace; Colin J. N. Wilson; Simon J. Barker; Bruce L. A. Charlier (Bulletin of Volcanology, 2023)
Volatile measurements in mineral-hosted sealed melt inclusions, and open-ended embayments, have previously been used to study magma ascent dynamics in large rhyolitic eruptions. However, despite occurring more frequently, smaller-volume explosive events remain under-studied. We present magmatic volatile data from quartz-hosted melt inclusions and embayments for eight post-25.4 ka rhyolitic eruptions at Ōkataina Volcanic Centre, Aotearoa New Zealand. Seven originated from within the main caldera, and the other erupted from the associated Ōkareka Structural Embayment. Melt inclusions preserve volatile contents of 2.92–5.82 wt% H 2 O and 13–126 ppm CO 2 , indicating pre-eruptive storage depths of 4.5–7.4 km, with younger eruptions being more shallow. The lack of correlation between H 2 O, CO 2 , inclusion size or distance to the crystal rim suggests magma bodies experienced variable degrees of degassing during magma storage, with some amount of post-entrapment volatile modification prior to and concurrent with final magma ascent. Diffusion modelling of measured H 2 O gradients in melt embayments indicates ascent rates of 0.10–1.67 m.s −1 over time spans of 20–230 min for the intra-caldera events. In contrast, ascent rates for the eruption from the Ōkareka Structural Embayment may be more rapid, at 1.59–4.4 m.s −1 over a time span of 22–34 min. Our findings imply that the final, pre-eruptive magma movement towards the surface could be less than a few hours. Comparisons with published data for caldera-forming explosive events reveal no clear relationships between final ascent rate, eruption size or initial volatile content, implying that other factors besides eruption volume control rhyolite magma ascent.

Response to Merritts et al. (2023): The Anthropocene is complex. Defining it is not - Colin N. Waters; Martin J. Head; Jan Zalasiewicz; Francine M.G. McCarthy; Scott L. Wing; Peter K. Haff; Mark Williams; Anthony D. Barnosky; Barbara Fiałkiewicz-Kozieł; Reinhold Leinfelder; J.R. McNeill; Neil L. Rose; et al. (Earth-Science Reviews, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Seafloor Terrain Shapes the Three-dimensional Nursery Value of Mangrove and Seagrass Habitats - Hayden P. Borland; Ben L. Gilby; Christopher J. Henderson; Rod M. Connolly; Bob Gorissen; Nicholas L. Ortodossi; Ashley J. Rummell; Ivan Nagelkerken; Simon J. Pittman; Marcus Sheaves; Andrew D. Olds (Ecosystems, 2023)
Mangroves and seagrasses are important nurseries for many marine species, and this function is linked to the complexity and context of these habitats in coastal seascapes. It is also connected to bathymetric features that influence habitat availability, and the accessibility of refuge habitats, but the significance of terrain variation for nursery function is unknown. To test whether seafloor terrain influences nursery function, we surveyed fish assemblages from mangrove and seagrass habitats in 29 estuaries in eastern Australia with unbaited underwater cameras and quantified the surrounding three-dimensional terrain with a set of complementary surface metrics (that is, depth, aspect, curvature, slope, roughness) applied to sonar-derived bathymetric maps. Terrain metrics explained variability in assemblages in both mangroves and seagrasses, with differing effects for the entire fish assemblage and nursery species composition, and between habitats. Higher depth, plan curvature (concavity or convexity) and roughness (backscatter) were negatively correlated with abundance and diversity in mangroves and positively linked to abundance and diversity in seagrass. Mangrove nursery species (6 species) were most abundant in forests adjacent to flats with concave holes, rough substrates and low-moderate depths, whereas seagrass nursery species (3 species) were most abundant in meadows adjacent to deep channels with soft mounds and ledges. These findings indicate that seafloor terrain influences nursery function and demonstrate contrasting effects of terrain variation in mangroves and seagrass. We suggest that incorporating three-dimensional terrain into coastal conservation and restoration plans could help to improve outcomes for fisheries management, but contrasting strategies might be needed for different nursery habitats.

Depth and temperature profiles reflect individual differences in the daytime diving behaviours of pelagic thresher sharks - Simon P. Oliver; Thomas M. Grothues; Zoe J. Mayo; Amie L. Williams; Medel Silvosa; Gary Cases (Frontiers in Marine Science, 2023)
We used acoustic telemetry to investigate the roles of depth and temperature in the daytime foraging behaviours of 13 tagged pelagic thresher sharks by monitoring their fine scale vertical movements in the Philippines. Cumulatively, pelagic thresher shark dives traversed the entire water column where they encountered temperatures that ranged from 33°C at the surface to 12°C at 250 m depths throughout the day, but the movements of individuals varied in the extent of both their deep and shallow water limits. Dives were not synchronized to diurnal cycles, and periodicity reflected cycles of similar dives, the dives themselves, deviations, cruising, and individuality. Pelagic thresher shark movements between the warm surface layer and cooler waters below the thermocline (155 – 175 m) may reflect a common Alopiid strategy that balances maintaining tolerable ambient water temperatures with opportunities to search for and forage on spatially patchy distributions of prey.

Planktic foraminifera iodine/calcium ratios from plankton tows - Helge A. Winkelbauer; Babette A. A. Hoogakker; Rosie J. Chance; Catherine V. Davis; Christopher J. Anthony; Juliane Bischoff; Lucy J. Carpenter; Simon R. N. Chenery; Elliott M. Hamilton; Philip Holdship; Victoria L. Peck; Alex J. Poulton; et al. (Frontiers in Marine Science, 2023)
Planktic foraminifera test iodine to calcium ratios represent an emerging proxy method to assess subsurface seawater oxygenation states. Several core-top studies show lower planktic foraminifera I/Ca in locations with oxygen depleted subsurface waters compared to well oxygenated environments. The reasoning behind this trend is that only the oxidized species of iodine, iodate, is incorporated in foraminiferal calcite. The I/Ca of foraminiferal calcite is thought to reflect iodate contents in seawater. To test this hypothesis, we compare planktic foraminifera I/Ca ratios, obtained from plankton tows, with published and new seawater iodate concentrations from 1) the Eastern North Pacific with extensive oxygen depletion, 2) the Benguela Current System with moderately depleted oxygen concentrations, and 3) the well oxygenated North and South Atlantic. We find the lowest I/Ca ratios (0.07 µmol/mol) in planktic foraminifera retrieved from the Eastern North Pacific, and higher values for samples (up to 0.72 µmol/mol) obtained from the Benguela Current System and North and South Atlantic. The I/Ca ratios of plankton tow foraminifera from environments with well oxygenated subsurface waters, however, are an order of magnitude lower compared to core-tops from similarly well-oxygenated regions. This would suggest that planktic foraminifera gain iodine post-mortem, either when sinking through the water column, or during burial.

Resilience of ecosystem service delivery in grasslands in response to single and compound extreme weather events - Rosalind J. Dodd; David R. Chadwick; Paul W. Hill; Felicity Hayes; Antonio R. Sánchez-Rodríguez; Dylan Gwynn-Jones; Simon M. Smart; Davey L. Jones (Science of The Total Environment, 2023)

Dissecting the impact of environment, season and genotype on blackcurrant fruit quality traits - Delphine M. Pott; Sara Durán-Soria; J. William Allwood; Simon Pont; Sandra L. Gordon; Nikki Jennings; Ceri Austin; Derek Stewart; Rex M. Brennan; Agnieszka Masny; Anita Sønsteby; Erika Krüger; et al. (Food Chemistry, 2023)

A Novel Mitochondria-Targeting Iron Chelator Neuroprotects Multimodally via HIF-1 Modulation Against a Mitochondrial Toxin in a Dopaminergic Cell Model of Parkinson’s Disease - Belinda Fouché; Stephanie Turner; Rebecca Gorham; Eloise J. Stephenson; Simon Gutbier; Joanna L. Elson; Olimpo García-Beltrán; Francois H. Van Der Westhuizen; Ilse S. Pienaar (Molecular Neurobiology, 2023)

Distribution of the reef manta ray Mobula alfredi and the oceanic manta ray Mobula birostris in the Philippines: a collaborative effort for conservation - Joshua Rambahiniarison; Ariana Agustines; Konstantinos Alexopoulos; Gonzalo Araujo; Asia O. Armstrong; Shannon Arnold; Aldrin Barruga; Titus Cañete; Segundo Conales; Kymry Delijero; Nonie P. Enolva; Anna L. Flam; et al. (Journal of Fish Biology, 2023)
Little is known about manta ray population size, structure and connectivity in the Philippines. In collaboration with dive operators, non‐governmental organizations and authorities, sightings of manta rays were collated into a single national database. Using in‐water photographs and videos gathered through citizen science and dedicated research efforts, this study compiled sightings between 2004 and 2020, showing 22 separate sites throughout the archipelago with manta rays present. A total of 392 individual reef manta rays ( Mobula alfredi ) and 107 oceanic manta rays ( Mobula birostris ) were identified from the collected footage. Four specific sites in the provinces of Masbate and Palawan together hosted 89% of all identified individuals and accounted for 95% of sightings, highlighting these areas are key aggregation sites. This study also reports the movements of M. birostris within the Philippines, based on photo‐identification of three individuals moving 150 km between Cebu and Masbate. Despite the growing number of recreational divers in Daanbantayan and San Jacinto, an 80% decline in M. birostris sightings was observed at these sites. To ensure effective future conservation, it is recommended that efforts focus on the identification and protection of manta ray hotspots and migratory corridors, the creation of a sustainable tourism framework and, most important, the implementation of mitigation strategies to reduce fisheries interactions.

Potential for redistribution of post‐moult habitat for Eudyptes penguins in the Southern Ocean under future climate conditions - Cara‐Paige Green; David B. Green; Norman Ratcliffe; David Thompson; Mary‐Anne Lea; Alastair M. M. Baylis; Alexander L. Bond; Charles‐André Bost; Sarah Crofts; Richard J. Cuthbert; Jacob González‐Solís; Kyle W. Morrison; et al. (Global Change Biology, 2023)
Anthropogenic climate change is resulting in spatial redistributions of many species. We assessed the potential effects of climate change on an abundant and widely distributed group of diving birds, Eudyptes penguins, which are the main avian consumers in the Southern Ocean in terms of biomass consumption. Despite their abundance, several of these species have undergone population declines over the past century, potentially due to changing oceanography and prey availability over the important winter months. We used light‐based geolocation tracking data for 485 individuals deployed between 2006 and 2020 across 10 of the major breeding locations for five taxa of Eudyptes penguins. We used boosted regression tree modelling to quantify post‐moult habitat preference for southern rockhopper ( E. chrysocome ), eastern rockhopper ( E. filholi ), northern rockhopper ( E. moseleyi ) and macaroni/royal ( E. chrysolophus and E. schlegeli ) penguins. We then modelled their redistribution under two climate change scenarios, representative concentration pathways RCP4.5 and RCP8.5 (for the end of the century, 2071–2100). As climate forcings differ regionally, we quantified redistribution in the Atlantic, Central Indian, East Indian, West Pacific and East Pacific regions. We found sea surface temperature and sea surface height to be the most important predictors of current habitat for these penguins; physical features that are changing rapidly in the Southern Ocean. Our results indicated that the less severe RCP4.5 would lead to less habitat loss than the more severe RCP8.5. The five taxa of penguin may experience a general poleward redistribution of their preferred habitat, but with contrasting effects in the (i) change in total area of preferred habitat under climate change (ii) according to geographic region and (iii) the species (macaroni/royal vs. rockhopper populations). Our results provide further understanding on the regional impacts and vulnerability of species to climate change.

Toward a forest biomass reference measurement system for remote sensing applications - Nicolas Labrière; Stuart J. Davies; Mathias I. Disney; Laura I. Duncanson; Martin Herold; Simon L. Lewis; Oliver L. Phillips; Shaun Quegan; Sassan S. Saatchi; Dmitry G. Schepaschenko; Klaus Scipal; Plinio Sist; et al. (Global Change Biology, 2023)
Forests contribute to climate change mitigation through carbon storage and uptake, but the extent to which this carbon pool varies in space and time is still poorly known. Several Earth Observation missions have been specifically designed to address this issue, for example, NASA's GEDI, NASA‐ISRO's NISAR and ESA's BIOMASS. Yet, all these missions' products require independent and consistent validation. A permanent, global, in situ, site‐based forest biomass reference measurement system relying on ground data of the highest possible quality is therefore needed. Here, we have assembled a list of almost 200 high‐quality sites through an in‐depth review of the literature and expert knowledge. In this study, we explore how representative these sites are in terms of their coverage of environmental conditions, geographical space and biomass‐related forest structure, compared to those experienced by forests worldwide. This work also aims at identifying which sites are the most representative, and where to invest to improve the representativeness of the proposed system. We show that the environmental coverage of the system does not seem to improve after at least the 175 most representative sites are included, but geographical and structural coverages continue to improve as more sites are added. We highlight the areas of poor environmental, geographical, or structural coverage, including, but not limited to, Canada, the western half of the USA, Mexico, Patagonia, Angola, Zambia, eastern Russia, and tropical and subtropical highlands (e.g. in Colombia, the Himalayas, Borneo, Papua). For the proposed system to succeed, we stress that (1) data must be collected and processed applying the same standards across all countries and continents; (2) system establishment and management must be inclusive and equitable, with careful consideration of working conditions; and (3) training and site partner involvement in downstream activities should be mandatory.

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

A near-complete species-level phylogeny of uropeltid snakes harnessing historical museum collections as a DNA source - Filipa L. Sampaio; Julia J. Day; L.J. Mendis Wickramasinghe; Vivek P. Cyriac; Anna Papadopoulou; Selina Brace; Albert Rajendran; Cornelia Simon-Nutbrown; Tomas Flouris; Paschalia Kapli; Dulan Ranga Vidanapathirana; Ramachandran Kotharambath; et al. (Molecular Phylogenetics and Evolution, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Species delimitation in the Trichocentrum cepula (Oncidiinae, Orchidaceae) complex: a multidisciplinary approach - Antonio E. Camelo-Júnior; Alessandro W. C. Ferreira; Ivanilza M. Andrade; Simon J. Mayo; Felipe Nollet; José L. Silva; Maria C. Barros; Elmary Fraga; Edlley M. Pessoa (Systematics and Biodiversity, 2022)

Turning a lost reef ecosystem into a national restoration program - Dominic McAfee; Ian M. McLeod; Heidi K. Alleway; Melanie J. Bishop; Simon Branigan; Sean D. Connell; Craig Copeland; Christine M. Crawford; Ben K. Diggles; James A. Fitzsimons; Ben L. Gilby; Paul Hamer; et al. (Conservation Biology, 2022)
Achieving a sustainable socioecological future now requires large‐scale environmental repair across legislative borders. Yet, enabling large‐scale conservation is complicated by policy‐making processes that are disconnected from socioeconomic interests, multiple sources of knowledge, and differing applications of policy. We considered how a multidisciplinary approach to marine habitat restoration generated the scientific evidence base, community support, and funding needed to begin the restoration of a forgotten, functionally extinct shellfish reef ecosystem. The key actors came together as a multidisciplinary community of researchers, conservation practitioners, recreational fisher communities, and government bodies that collaborated across sectors to rediscover Australia's lost shellfish reefs and communicate the value of its restoration. Actions undertaken to build a case for large‐scale marine restoration included synthesizing current knowledge on Australian shellfish reefs and their historical decline, using this history to tell a compelling story to spark public and political interest, integrating restoration into government policy, and rallying local support through community engagement. Clearly articulating the social, economic, and environmental business case for restoration led to state and national funding for reef restoration to meet diverse sustainability goals (e.g., enhanced biodiversity and fisheries productivity) and socioeconomic goals (e.g., job creation and recreational opportunities). A key lesson learned was the importance of aligning project goals with public and industry interests so that projects could address multiple political obligations. This process culminated in Australia's largest marine restoration initiative and shows that solutions for large‐scale ecosystem repair can rapidly occur when socially valued science acts on political opportunities.

Circles in the sea: annual courtship “torus” behaviour of basking sharks Cetorhinus maximus identified in the eastern North Atlantic Ocean - David W. Sims; Simon D. Berrow; Ken M. O'Sullivan; Nicholas J. Pfeiffer; Richard Collins; Kev L. Smith; Brianna M. Pfeiffer; Paul Connery; Shane Wasik; Lois Flounders; Nuno Queiroz; Nicolas E. Humphries; et al. (Journal of Fish Biology, 2022)
Groups of basking sharks engaged in circling behaviour are rarely observed, and their function remains enigmatic in the absence of detailed observations. Here, underwater and aerial video recordings of multiple circling groups of basking sharks during late summer (August and September 2016–2021) in the eastern North Atlantic Ocean showed groups numbering between 6 and 23 non‐feeding individuals of both sexes. Sharks swam slowly in a rotating “torus” (diameter range: 17–39 m), with individuals layered vertically from the surface to a maximum depth of 16 m. Within a torus, sharks engaged in close‐following, echelon, close‐flank approach or parallel‐swimming behaviours. Measured shark total body lengths were 5.4–9.5 m (mean L T : 7.3 m ± 0.9 s.d. ; median: 7.2 m, n = 27), overlapping known lengths of sexually mature males and females. Males possessed large claspers with abrasions that were also observed on female pectoral fins. Female body colouration was paler than that of males, similar to colour changes observed during courtship and mating in other shark species. Individuals associated with most other members rapidly (within minutes), indicating toroidal behaviours facilitate multiple interactions. Sharks interacted through fin–fin and fin–body contacts, rolling to expose the ventral surfaces to following sharks, and breaching behaviour. Toruses formed in late summer when feeding aggregations in zooplankton‐rich thermal fronts switched to non‐feeding following and circling behaviours. Collectively, the observations explain a courtship function for toruses. This study highlights northeast Atlantic coastal waters as a critical habitat supporting courtship reproductive behaviour of endangered basking sharks, the first such habitat identified for this species globally.

How Machine Learning is Powering Neuroimaging to Improve Brain Health - Nalini M. Singh; Jordan B. Harrod; Sandya Subramanian; Mitchell Robinson; Ken Chang; Suheyla Cetin-Karayumak; Adrian Vasile Dalca; Simon Eickhoff; Michael Fox; Loraine Franke; Polina Golland; Daniel Haehn; et al. (Neuroinformatics, 2022)
This report presents an overview of how machine learning is rapidly advancing clinical translational imaging in ways that will aid in the early detection, prediction, and treatment of diseases that threaten brain health. Towards this goal, we aresharing the information presented at a symposium, “Neuroimaging Indicators of Brain Structure and Function - Closing the Gap Between Research and Clinical Application”, co-hosted by the McCance Center for Brain Health at Mass General Hospital and the MIT HST Neuroimaging Training Program on February 12, 2021. The symposium focused on the potential for machine learning approaches, applied to increasingly large-scale neuroimaging datasets, to transform healthcare delivery and change the trajectory of brain health by addressing brain care earlier in the lifespan. While not exhaustive, this overview uniquely addresses many of the technical challenges from image formation, to analysis and visualization, to synthesis and incorporation into the clinical workflow. Some of the ethical challenges inherent to this work are also explored, as are some of the regulatory requirements for implementation. We seek to educate, motivate, and inspire graduate students, postdoctoral fellows, and early career investigators to contribute to a future where neuroimaging meaningfully contributes to the maintenance of brain health.

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

Classification of new morbillivirus and jeilongvirus sequences from bats sampled in Brazil and Malaysia - Heather L. Wells; Elizabeth Loh; Alessandra Nava; Mónica Romero Solorio; Mei Ho Lee; Jimmy Lee; Jum R. A. Sukor; Isamara Navarrete-Macias; Eliza Liang; Cadhla Firth; Jonathan H. Epstein; Melinda K. Rostal; et al. (Archives of Virology, 2022)
As part of a broad One Health surveillance effort to detect novel viruses in wildlife and people, we report several paramyxovirus sequences sampled primarily from bats during 2013 and 2014 in Brazil and Malaysia, including seven from which we recovered full-length genomes. Of these, six represent the first full-length paramyxovirid genomes sequenced from the Americas, including two that are the first full-length bat morbillivirus genome sequences published to date. Our findings add to the vast number of viral sequences in public repositories, which have been increasing considerably in recent years due to the rising accessibility of metagenomics. Taxonomic classification of these sequences in the absence of phenotypic data has been a significant challenge, particularly in the subfamily Orthoparamyxovirinae , where the rate of discovery of novel sequences has been substantial. Using pairwise amino acid sequence classification (PAASC), we propose that five of these sequences belong to members of the genus Jeilongvirus and two belong to members of the genus Morbillivirus . We also highlight inconsistencies in the classification of Tupaia virus and Mòjiāng virus using the same demarcation criteria and suggest reclassification of these viruses into new genera. Importantly, this study underscores the critical importance of sequence length in PAASC analysis as well as the importance of biological characteristics such as genome organization in the taxonomic classification of viral sequences.

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

Barriers in European spiny lobster ( Palinurus elephas ) aquaculture: What we know so far? - Adam L. K. Yeap; Cecília de Souza Valente; Finnian Hartnett; Ellie‐Ann Conneely; Majbritt Bolton‐Warberg; Simon J. Davies; Mark P. Johnson; Alex H. L. Wan (Reviews in Aquaculture, 2022)
Palinurids, also known as spiny lobsters, are high‐value seafood, which is economically important for many European and Asian seafood trades. However, the reduction of wild European spiny lobster populations produces a need for developing alternative renewable strategies to meet current and future demands. Aquaculture of spiny lobsters has the potential to become of major economic importance in the coming years with growing markets in Asia, Europe, and America, with Palinurus elephas being a promising candidate species for use in the commercial culture and stock enhancement of natural fisheries. This is due to its shorter larval periods and rapid growth to the critical puerulus stage compared with other spiny lobster species. While we have a basic understanding of the lifecycle and biology of P. elephas , much of this is based on work undertaken on similar species globally. There are many gaps in our knowledge that need to be addressed to make its aquaculture viable with appropriate feeds being an immediate issue as well as many other husbandry‐related factors. Previous studies act as a platform providing a baseline for further research and highlighting constraints. Developments in the use of P. elephas are promising due to realistically bridgeable knowledge gaps, the likelihood of producing sustainable food and the high commercial value of spiny lobsters. This review identifies our present state of knowledge and outlines the scope for further research and necessary technological developments to make it a viable contribution towards crustacean aquaculture in Europe.

Association patterns and community structure among female bottlenose dolphins: environmental, genetic and cultural factors - Svenja M. Marfurt; Simon J. Allen; Manuela R. Bizzozzero; Erik P. Willems; Stephanie L. King; Richard C. Connor; Anna M. Kopps; Sonja Wild; Livia Gerber; Samuel Wittwer; Michael Krützen (Mammalian Biology, 2022)
Social structuring from assortative associations may affect individual fitness, as well as population-level processes. Gaining a broader understanding of social structure can improve our knowledge of social evolution and inform wildlife conservation. We investigated association patterns and community structure of female Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) in Shark Bay, Western Australia, assessing the role of kinship, shared culturally transmitted foraging techniques, and habitat similarity based on water depth. Our results indicated that associations are influenced by a combination of uni- and biparental relatedness, cultural behaviour and habitat similarity, as these were positively correlated with a measure of dyadic association. These findings were matched in a community level analysis. Members of the same communities overwhelmingly shared the same habitat and foraging techniques, demonstrating a strong homophilic tendency. Both uni- and biparental relatedness between dyads were higher within than between communities. Our results illustrate that intraspecific variation in sociality in bottlenose dolphins is influenced by a complex combination of genetic, cultural, and environmental aspects.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

New haplotypes found in stranded long‐finned pilot whales ( Globicephala melas ) in the eastern North Atlantic and adjacent waters - Rachel J. Ball; Ashleigh Kitchiner; Nicholas J. Davison; Andrew Brownlow; Simon Berrow; Niall J. McKeown; Lonneke L. IJsseldijk; Matthew Geary; Ian McDowall; Anna P. Muir (Marine Mammal Science, 2022)
Long‐finned pilot whale ( Globicephala melas ) mitochondrial (mtDNA) genetic diversity is considered low, especially in the North Atlantic, where only seven haplotypes have been recorded in previous studies using a 345 bp control region fragment. Such studies have not included samples from Ireland or the Netherlands. In this study we analyzed a longer sequence of the mtDNA control region (631 bp) from individuals stranded around Ireland, Scotland, and the Netherlands between 1995 and 2019 ( n = 180). Nine haplotypes were identified, of which five were newly described (haplotype diversity h = 0.511). Pairwise tests revealed significant differentiation between the Irish and Scottish samples. Potential confounding factors are discussed but given that failure to recognize population structure may compromise conservation efforts, the findings show the need for further investigation using nuclear markers. Six mass stranding events were included, of which one event reported two haplotypes among individuals confirming a mixing of matrilineal groups. Although the permanence of this combination cannot be determined, this is the first record of such an occurrence within the North Atlantic. This study shows that stranding sample databases are a useful resource for genetic studies and provides new insights into genetic diversity of long‐finned pilot whales in the eastern North Atlantic and adjacent waters.

Sympatric Seals, Satellite Tracking and Protected Areas: Habitat-Based Distribution Estimates for Conservation and Management - Matt I. D. Carter; Lars Boehme; Michelle A. Cronin; Callan D. Duck; W. James Grecian; Gordon D. Hastie; Mark Jessopp; Jason Matthiopoulos; Bernie J. McConnell; David L. Miller; Chris D. Morris; Simon E. W. Moss; et al. (Frontiers in Marine Science, 2022)
Marine predator populations are crucial to the structure and functioning of ecosystems. Like many predator taxa, pinnipeds face an increasingly complex array of natural and anthropogenic threats. Understanding the relationship between at-sea processes and trends in abundance at land-based monitoring sites requires robust estimates of at-sea distribution, often on multi-region scales. Such an understanding is critical for effective conservation management, but estimates are often limited in spatial extent by spatial coverage of animal-borne tracking data. Grey ( Halichoerus grypus ) and harbour seals ( Phoca vitulina ) are sympatric predators in North Atlantic shelf seas. The United Kingdom (UK) and Ireland represents an important population centre for both species, and Special Areas of Conservation (SACs) are designated for their monitoring and protection. Here we use an extensive high-resolution GPS tracking dataset, unprecedented in both size (114 grey and 239 harbour seals) and spatial coverage, to model habitat preference and generate at-sea distribution estimates for the entire UK and Ireland populations of both species. We found regional differences in environmental drivers of distribution for both species which likely relate to regional variation in diet and population trends. Moreover, we provide SAC-specific estimates of at-sea distribution for use in marine spatial planning, demonstrating that hotspots of at-sea density in UK and Ireland-wide maps cannot always be apportioned to the nearest SAC. We show that for grey seals, colonial capital breeders, there is a mismatch between SACs (where impacts are likely to be detected) and areas where impacts are most likely to occur (at sea). We highlight an urgent need for further research to elucidate the links between at-sea distribution during the foraging season and population trends observed in SACs. More generally, we highlight that the potential for such a disconnect needs to be considered when designating and managing protected sites, particularly for species that aggregate to breed and exhibit partial migration (e.g. grey seals), or spatial variation in migration strategies. We demonstrate the use of strategic tracking efforts to predict distribution across multiple regions, but caution that such efforts should be mindful of the potential for differences in species-environment relationships despite similar accessible habitats.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The utilisation of European processed animal proteins as safe, sustainable and circular ingredients for global aquafeeds - Stephen L. Woodgate; Alex H. L. Wan; Finnian Hartnett; Robert G. Wilkinson; Simon J. Davies (Reviews in Aquaculture, 2022)
The global increase in seafood demand has resulted in significant growth in aquaculture production in a wide range of aquatic species. Consequently, this has led to an industry‐wide need to find sustainable feed ingredients that would meet the nutritional requirements used in aquafeeds. The associated dependency on plant by‐products as the major alternatives has brought concerns to aquaculture through associated carbon footprint, increase deforestation and arable land use to meet the demands of plant proteins and oils, and the constraining effects of plant by‐products has on farmed aquatic animal growth and health. Animal by‐products (ABPs) are produced as a direct consequence of terrestrial animal production and the associated meat processing industries. The link between feeding meat and bone meal (MBM) and bovine spongiform encephalopathy (BSE) outbreak in Europe during the 1980s resulted in a ban of its use animal feeds. This led to a radical overhaul of the rendering industry, including the use of only low‐risk ABP and the development of rendering processes to reduce the risk of prions that causes BSE to enter the food chain. The resulting processed animal proteins (PAPs) are considered safe to be used in farmed animal feeds. This review examines how ABP production has changed due to the BSE outbreak, leading to the current commercially available PAP products for aquafeed use. We evaluated how these products can be effectively used as viable protein sources in aquaculture and examine their limitations and the potential advancements that could lead to a more circular food production system.

Long‐term decline in abundance of male sperm whales visiting Kaikōura, New Zealand - Tamlyn R. Somerford; Stephen M. Dawson; Elisabeth Slooten; Marta Guerra; Simon J. Childerhouse; Christoph F. Richter; Miranda L. van der Linde; William J. Rayment (Marine Mammal Science, 2022)
Kaikōura, New Zealand, is one of the few places worldwide where sperm whales can be routinely found close to the coast. Although whales are present nearly all year round, no individuals are truly resident. In this study, we analyzed photo‐identification data collected over 27 years to investigate long‐term trends in inshore abundance. We contrasted two analytical approaches: Cormack‐Jolly‐Seber (CJS) mark‐recapture models, and the “Robust Design,” which can incorporate temporary emigration of individuals. CJS models for open populations showed a significant decline in the annual number of individual males, from 89, 95% CI [60, 133] in 1991, to 40, 95% CI [33–49] in 2017. The Robust Design models indicated that the trend was driven by a decline in abundance of whales using Kaikōura during summer, from 54, 95% CI [18, 156] in 1990, to 23, 95% CI [16, 33] in 2017. In contrast, there was no evidence for change in the numbers of whales using Kaikōura during winter. Incorporating temporary emigration had the most support, indicating Robust Design was more appropriate for estimating abundance. The results of Pradel recruitment models suggest that recruitment to the population using the study area during summer declined during the late 1990s/early 2000s, potentially explaining the decline in abundance.

Variation in δ 13 C and δ 15 N values of mothers and their calves across southern right whale nursery grounds: The effects of nutritional stress? - Emma L. Carroll; Glenn Dunshea; Paulo H. Ott; Luciano O. Valenzuela; C. Scott Baker; Simon J. Childerhouse; Oscar E. Gaggiotti; Paulo A. C. Flores; Karina Groch; Darren R. Gröcke; Mark A. Hindell; David Lundquist; et al. (Marine Mammal Science, 2022)
Southern right whales (SRW) are capital breeders that use stored energy reserves to sustain themselves and their calves on nursery areas. With successful calving events declining in some SRW populations, it has been hypothesized that nutritional stress in adult females causes reproductive failure or death of calves shortly after birth. Here we compared offsets in carbon and nitrogen isotope values of mothers and their offspring (Δ 13 C calf‐cow and Δ 15 N calf‐cow ) among three SRW populations. SRW from Aotearoa New Zealand, with high population growth rates and body conditions scores, have negative Δ 13 C calf‐cow suggesting calves are utilizing 13 C‐depleted lipid carbon in milk to fuel the synthesis of nonessential amino acids used to build new tissues and rapidly grow. In contrast, a significantly positive Δ 13 C calf‐cow offset previously reported for SRW from Argentina during a mass die‐off event was hypothesized to be due to calves consuming milk with low lipid content. Patterns in Δ 15 N calf‐cow were more difficult to interpret and highlight the complexity in nitrogen transfer between mother and offspring. When combined with similar data collected from Brazil and during a low mortality year in Argentina, we hypothesize this approach provides a way to retrospectively compare nutritional condition of breeding adult female SRW across nursery areas.

Rifting and recharge as triggers of the mixed basalt–rhyolite Halarauður ignimbrite eruption (Krafla, Iceland) - Shane M. Rooyakkers; John Stix; Kim Berlo; Daniele Morgavi; Maurizio Petrelli; Monika K. Rusiecka; Simon J. Barker; Bruce L. A. Charlier; David A. Neave; Francesco P. Vetere; Diego Perugini (Contributions to Mineralogy and Petrology, 2022)

Origin and expansion of the world’s most widespread pinniped: Range‐wide population genomics of the harbour seal ( Phoca vitulina ) - Xiaodong Liu; Suzanne Rønhøj Schjøtt; Sandra M. Granquist; Aqqalu Rosing‐Asvid; Rune Dietz; Jonas Teilmann; Anders Galatius; Kristina Cammen; Greg O’Corry‐Crowe; Karin Harding; Tero Härkönen; Ailsa Hall; et al. (Molecular Ecology, 2022)
The harbour seal ( Phoca vitulina ) is the most widely distributed pinniped, occupying a wide variety of habitats and climatic zones across the Northern Hemisphere. Intriguingly, the harbour seal is also one of the most philopatric seals, raising questions as to how it colonized its current range. To shed light on the origin, remarkable range expansion, population structure and genetic diversity of this species, we used genotyping‐by‐sequencing to analyse ~13,500 biallelic single nucleotide polymorphisms from 286 individuals sampled from 22 localities across the species’ range. Our results point to a Northeast Pacific origin of the harbour seal, colonization of the North Atlantic via the Canadian Arctic, and subsequent stepping‐stone range expansions across the North Atlantic from North America to Europe, accompanied by a successive loss of genetic diversity. Our analyses further revealed a deep divergence between modern North Pacific and North Atlantic harbour seals, with finer‐scale genetic structure at regional and local scales consistent with strong philopatry. The study provides new insights into the harbour seal's remarkable ability to colonize and adapt to a wide range of habitats. Furthermore, it has implications for current harbour seal subspecies delineations and highlights the need for international and national red lists and management plans to ensure the protection of genetically and demographically isolated populations.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Assessment of Australian Sea Lion Bycatch Mortality in a Gillnet Fishery, and Implementation and Evaluation of an Effective Mitigation Strategy - Simon D. Goldsworthy; Brad Page; Derek J. Hamer; Andrew D. Lowther; Peter D. Shaughnessy; Mark A. Hindell; Paul Burch; Daniel P. Costa; Shannon L. Fowler; Kristian Peters; Rebecca R. McIntosh; Frederic Bailleul; et al. (Frontiers in Marine Science, 2022)
Globally, the bycatch of marine mammals in fisheries represents the greatest source of human-caused mortality that threatens the sustainability of many populations and species. The Australian sea lion ( Neophoca cinerea ) is an endangered species, whose populations off South Australia (SA) have been subject to bycatch in a demersal gillnet fishery targeting sharks since the 1960s. A comprehensive assessment was undertaken of sea lion bycatch mortality that combined independent fishery observer data with species distribution models (underpinned by satellite tracking, abundance data and population modeling) to model the relationship between at-sea foraging effort and bycatch rate. Combined with the distribution of fishing effort, these models enabled the overall level of bycatch mortality to be estimated by age, sex and subpopulation, facilitating population viability analyses that indicated most subpopulations were declining, and subject to unsustainable levels of bycatch mortality. To reduce this mortality, the Australian Fisheries Management Authority implemented an Australian Sea Lion Management Strategy that included an independent observer program (ultimately 100% electronic monitoring of gillnet fishing off SA), permanent spatial gillnet closures around all sea lion breeding sites, bycatch mortality limits that triggered temporal (18 months) spatial closures when zone-specific bycatch trigger limits were reached, and incentives for gillnet fishers to switch to an alternate fishing method (longlines). The Strategy had immediate impacts on the fishery: it resulted in significant reductions in gillnet fishing effort and on the reported bycatch of sea lions. In the next decade, there was an estimated 98% reduction in sea lion bycatch mortality from gillnet interactions and an apparent stabilization of the decline in sea lion pup abundances at some impacted breeding sites. There was an almost complete transition in the fishery from gillnets to longlines, and fishing catches returned to pre-management levels. The successful implementation of management measures to mitigate sea lion bycatch mortality in the gillnet fishery off SA was rapid, science informed, adaptive, comprehensive, and backed by strong compliance and monitoring of the fishery. It provides an important case study which demonstrates how management measures can be effectively applied to mitigate bycatch mortality of marine mammals and other marine protected species.

Trophic mediation and ecosystem stability: An assessment using qualitative network models - Delphi F. L. Ward; Jessica Melbourne‐Thomas; Craig R. Johnson; Simon J. Wotherspoon (Limnology and Oceanography, 2022)
Nontrophic interactions can contribute to negative and positive feedbacks within a community, thus affecting likelihood of regime shifts; however, assessing the nature and importance of these effects in a network remains challenging, especially for pelagic ecosystems. Here, we present a qualitative modeling approach for assessing the importance of different effects and resultant feedbacks for community stability, using a Southern Ocean example. A potentially important positive feedback in the Southern Ocean ecosystem involves production of a chemical cue, dimethyl sulfide (DMS), by some phytoplankton. Production of DMS can promote phytoplankton growth by attracting predators of phytoplankton‐grazers, and nutrients released as feces from those predators help fertilize the water column. We explored how uncertainties in the nature of this feedback affect community stability in a set of small, community models. We found that stability varied substantially depending on how the community was modeled, but that the interactions most important for determining stability were consistent across all models. Model stability was sensitive to the strength of phytoplankton competition, controls on phytoplankton, DMS production and release, and predator attraction to DMS, suggesting that the community could be destabilized by perturbation affecting these interactions. Incorporating DMS‐mediated feedbacks into a larger Southern Ocean network had a moderate impact on stability characteristics and altered the trophic level at which the system would be most vulnerable to perturbation.

Changes in tree drought sensitivity provided early warning signals to the California drought and forest mortality event - Rachel M. Keen; Steven L. Voelker; S.‐Y. Simon Wang; Barbara J. Bentz; Michael L. Goulden; Cody R. Dangerfield; Charlotte C. Reed; Sharon M. Hood; Adam Z. Csank; Todd E. Dawson; Andrew G. Merschel; Christopher J. Still (Global Change Biology, 2022)
Climate warming in recent decades has negatively impacted forest health in the western United States. Here, we report on potential early warning signals (EWS) for drought‐related mortality derived from measurements of tree‐ring growth (ring width index; RWI) and carbon isotope discrimination (∆ 13 C), primarily focused on ponderosa pine ( Pinus ponderosa ). Sampling was conducted in the southern Sierra Nevada Mountains, near the epicenter of drought severity and mortality associated with the 2012–2015 California drought and concurrent outbreak of western pine beetle ( Dendroctonus brevicomis ). At this site, we found that widespread mortality was presaged by five decades of increasing sensitivity (i.e., increased explained variation) of both tree growth and ∆ 13 C to Palmer Drought Severity Index (PDSI). We hypothesized that increasing sensitivity of tree growth and ∆ 13 C to hydroclimate constitute EWS that indicate an increased likelihood of widespread forest mortality caused by direct and indirect effects of drought. We then tested these EWS in additional ponderosa pine‐dominated forests that experienced varying mortality rates associated with the same California drought event. In general, drier sites showed increasing sensitivity of RWI to PDSI over the last century, as well as higher mortality following the California drought event compared to wetter sites. Two sites displayed evidence that thinning or fire events that reduced stand basal area effectively reversed the trend of increasing hydroclimate sensitivity. These comparisons indicate that reducing competition for soil water and/or decreasing bark beetle host tree density via forest management—particularly in drier regions—may buffer these forests against drought stress and associated mortality risk. EWS such as these could provide land managers more time to mitigate the extent or severity of forest mortality in advance of droughts. Substantial efforts at deploying additional dendrochronological research in concert with remote sensing and forest modeling will aid in forecasting of forest responses to continued climate warming.

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

The Role of Climate, Oceanography, and Prey in Driving Decadal Spatio-Temporal Patterns of a Highly Mobile Top Predator - Amaia Astarloa; Maite Louzao; Joana Andrade; Lucy Babey; Simon Berrow; Oliver Boisseau; Tom Brereton; Ghislain Dorémus; Peter G. H. Evans; Nicola K. Hodgins; Mark Lewis; Jose Martinez-Cedeira; et al. (Frontiers in Marine Science, 2021)
Marine mammals have been proposed as ecosystem sentinels due to their conspicuous nature, wide ranging distribution, and capacity to respond to changes in ecosystem structure and functioning. In southern European Atlantic waters, their response to climate variability has been little explored, partly because of the inherent difficulty of investigating higher trophic levels and long lifespan animals. Here, we analyzed spatio-temporal patterns from 1994 to 2018 of one of the most abundant cetaceans in the area, the common dolphin ( Delphinus delphis ), in order to (1) explore changes in its abundance and distribution, and (2) identify the underlying drivers. For that, we estimated the density of the species and the center of gravity of its distribution in the Bay of Biscay (BoB) and tested the effect of three sets of potential drivers (climate indices, oceanographic conditions, and prey biomasses) with a Vector Autoregressive Spatio Temporal (VAST) model that accounts for changes in sampling effort resulting from the combination of multiple datasets. Our results showed that the common dolphin significantly increased in abundance in the BoB during the study period. These changes were best explained by climate indices such as the North Atlantic Oscillation (NAO) and by prey species biomass. Oceanographic variables such as chlorophyll a concentration and temperature were less useful or not related. In addition, we found high variability in the geographic center of gravity of the species within the study region, with shifts between the inner (southeast) and the outer (northwest) part of the BoB, although the majority of this variability could not be attributed to the drivers considered in the study. Overall, these findings indicate that considering temperature alone for projecting spatio-temporal patterns of highly mobile predators is insufficient in this region and suggest important influences from prey and climate indices that integrate multiple ecological influences. Further integration of existing observational datasets to understand the causes of past shifts will be important for making accurate projections into the future.

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

First Assessment of the Impacts of the COVID-19 Pandemic on Global Marine Recreational Fisheries - Pablo Pita; Gillian B. Ainsworth; Bernardino Alba; Antônio B. Anderson; Manel Antelo; Josep Alós; Iñaki Artetxe; Jérôme Baudrier; José J. Castro; Belén Chicharro; Karim Erzini; Keno Ferter; et al. (Frontiers in Marine Science, 2021)
This work is the result of an international research effort to determine the main impacts of the COVID-19 pandemic on marine recreational fishing. Changes were assessed on (1) access to fishing, derived from lockdowns and other mobility restrictions; (2) ecosystems, because of alterations in fishing intensity and human presence; (3) the blue economy, derived from alterations in the investments and expenses of the fishers; and (4) society, in relation to variations in fishers’ health and well-being. For this, a consultation with experts from 16 countries was carried out, as well as an international online survey aimed at recreational fishers, that included specific questions designed to capture fishers’ heterogeneity in relation to behavior, skills and know-how, and vital involvement. Fishers’ participation in the online survey (5,998 recreational fishers in 15 countries) was promoted through a marketing campaign. The sensitivity of the fishers’ clustering procedure, based on the captured heterogeneity, was evaluated by SIMPER analysis and by generalized linear models. Results from the expert consultation highlighted a worldwide reduction in marine recreational fishing activity. Lower human-driven pressures are expected to generate some benefits for marine ecosystems. However, experts also identified high negative impacts on the blue economy, as well as on fisher health and well-being because of the loss of recreational fishing opportunities. Most (98%) of the fishers who participated in the online survey were identified as advanced , showing a much higher degree of commitment to recreational fishing than basic fishers (2%). Advanced fishers were, in general, more pessimistic about the impacts of COVID-19, reporting higher reductions in physical activity and fish consumption, as well as poorer quality of night rest, foul mood, and raised more concerns about their health status. Controlled and safe access to marine recreational fisheries during pandemics would provide benefits to the health and well-being of people and reduce negative socioeconomic impacts, especially for vulnerable social groups.

A comment on: magma residence and eruption at the Taupō Volcanic Center (Taupō Volcanic Zone, New Zealand)—insights from rhyolite-MELTS geobarometry, diffusion chronometry, and crystal textures, by AS Pamukçu et al., Contrib Mineral Petrol 175:48 (2020) - Colin J. N. Wilson; Simon J. Barker; Bruce L. A. Charlier; Madison L. Myers; Kristian F. Hansen (Contributions to Mineralogy and Petrology, 2021)

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

The novel vasopressin receptor (V1aR) antagonist SRX246 reduces anxiety in an experimental model in humans: a randomized proof-of-concept study - Tiffany R. Lago; Michael J. Brownstein; Emily Page; Emily Beydler; Adrienne Manbeck; Alexis Beale; Camille Roberts; Nicholas Balderston; Eve Damiano; Suzanne L. Pineles; Neal Simon; Monique Ernst; et al. (Psychopharmacology, 2021)

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.

Extensive human‐mediated jump dispersal within and across the native and introduced ranges of the invasive termite Reticulitermes flavipes - Pierre‐André Eyer; Alexander J. Blumenfeld; Laura N. L. Johnson; Elfie Perdereau; Phillip Shults; Shichen Wang; Franck Dedeine; Simon Dupont; Anne‐Geneviève Bagnères; Edward L. Vargo (Molecular Ecology, 2021)
As native ranges are often geographically structured, invasive species originating from a single source population only carry a fraction of the genetic diversity present in their native range. The invasion process is thus often associated with a drastic loss of genetic diversity resulting from a founder event. However, the fraction of diversity brought to the invasive range may vary under different invasion histories, increasing with the size of the propagule, the number of reintroduction events, and/or the total genetic diversity represented by the various source populations in a multiple‐introduction scenario. In this study, we generated a SNP data set for the invasive termite Reticulitermes flavipes from 23 native populations in the eastern United States and six introduced populations throughout the world. Using population genetic analyses and approximate Bayesian computation random forest, we investigated its worldwide invasion history. We found a complex invasion pathway with multiple events out of the native range and bridgehead introductions from the introduced population in France. Our data suggest that extensive long‐distance jump dispersal appears common in both the native and introduced ranges of this species, probably through human transportation. Overall, our results show that similar to multiple introduction events into the invasive range, admixture in the native range prior to invasion can potentially favour invasion success by increasing the genetic diversity that is later transferred to the introduced range.

Functional biogeography of Neotropical moist forests: Trait–climate relationships and assembly patterns of tree communities - Bruno X. Pinho; Marcelo Tabarelli; Cajo J. F. ter Braak; S. Joseph Wright; Víctor Arroyo‐Rodríguez; Maíra Benchimol; Bettina M. J. Engelbrecht; Simon Pierce; Peter Hietz; Bráulio A. Santos; Carlos A. Peres; Sandra C. Müller; et al. (Global Ecology and Biogeography, 2021)
Aim Here we examine the functional profile of regional tree species pools across the latitudinal distribution of Neotropical moist forests, and test trait–climate relationships among local communities. We expected opportunistic strategies (acquisitive traits, small seeds) to be overrepresented in species pools further from the equator, but also in terms of abundance in local communities in currently wetter, warmer and more seasonal climates. Location Neotropics. Time period Recent. Major taxa studied Trees. Methods We obtained abundance data from 471 plots across nine Neotropical regions, including c . 100,000 trees of 3,417 species, in addition to six functional traits. We compared occurrence‐based trait distributions among regional species pools, and evaluated single trait–climate relationships across local communities using community abundance‐weighted means (CWMs). Multivariate trait–climate relationships were assessed by a double‐constrained correspondence analysis that tests both how CWMs relate to climate and how species distributions, parameterized by niche centroids in climate space, relate to their traits. Results Regional species pools were undistinguished in functional terms, but opportunistic strategies dominated local communities further from the equator, particularly in the Northern Hemisphere. Climate explained up to 57% of the variation in CWM traits, with increasing prevalence of lower‐statured, light‐wooded and softer‐leaved species bearing smaller seeds in more seasonal, wetter and warmer climates. Species distributions were significantly but weakly related to functional traits. Main conclusions Neotropical moist forest regions share similar sets of functional strategies, from which local assembly processes, driven by current climatic conditions, select for species with different functional strategies. We can thus expect functional responses to climate change driven by changes in relative abundances of species already present regionally. Particularly, equatorial forests holding the most conservative traits and large seeds are likely to experience the most severe changes if climate change triggers the proliferation of opportunistic tree species.

The influence of seafloor terrain on fish and fisheries: A global synthesis - Hayden P. Borland; Ben L. Gilby; Christopher J. Henderson; Javier X. Leon; Thomas A. Schlacher; Rod M. Connolly; Simon J. Pittman; Marcus Sheaves; Andrew D. Olds (Fish and Fisheries, 2021)
The structure of seafloor terrain affects the distribution and diversity of animals in all seascapes. Effects of terrain on fish assemblages have been reported from most ecosystems, but it is unclear whether bathymetric effects vary among seascapes or change in response to seafloor modification by humans. We reviewed the global literature linking seafloor terrain to fish species and assemblages (96 studies) and determined that relief (e.g. depth), complexity (e.g. roughness), feature classes (e.g. substrate types) and morphology (e.g. curvature), have widespread effects on fish assemblages. Research on the ecological consequences of terrain have focused on coral reefs, rocky reefs, continental shelves and the deep sea ( n ≥ 20 studies), but are rarely tested in estuaries ( n = 7). Fish associate with a variety of terrain attributes, and assemblages change with variation in the depth and aspect of bathymetric features in reef and shelf seascapes, and in the deep sea. Fish from different seascapes also respond to distinct metrics, with fluctuations in slope of slope (coral reefs), rugosity (rocky reefs) and slope (continental shelves, deep sea) each linked to changes in assemblage composition. Terrain simplification from coastal urbanization (e.g. dredging) and resource extraction (e.g. trawling) can reduce fish diversity and abundance, but assemblages can also recover inside effective marine reserves. The consequences of these terrain changes for fish and fisheries are, however, rarely measured in most seascapes. The key challenge now is to examine how terrain modification and conservation combine to alter fish distributions and fisheries productivity across diverse coastal seascapes.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

From long-lived batholith construction to giant porphyry copper deposit formation: petrological and zircon chemical evolution of the Quellaveco District, Southern Peru - Chetan L. Nathwani; Adam T. Simmons; Simon J. E. Large; Jamie J. Wilkinson; Yannick Buret; Christian Ihlenfeld (Contributions to Mineralogy and Petrology, 2021)
Porphyry Cu ore deposits are a rare product of arc magmatism that often form spatiotemporal clusters in magmatic arcs. The petrogenetic evolution of igneous rocks that cover the temporal window prior to and during porphyry Cu deposit formation may provide critical insights into magmatic processes that are key in generating these systems. This study documents the magmatic evolution of the Palaeocene–Eocene Yarabamba Batholith, Southern Peru, that was incrementally assembled between ~ 67 and ~ 59 Ma and hosts three, nearly contemporaneous, giant porphyry Cu–Mo deposits that formed at 57–54 Ma (Quellaveco, Toquepala and Cuajone). Whole-rock geochemistry, U–Pb geochronology and zircon trace element chemistry are reported from Yarabamba rocks that span the duration of plutonic activity, and from six porphyry intrusions at Quellaveco that bracket mineralisation. A change in whole-rock chemistry in Yarabamba intrusive rocks to high Sr/Y, high La/Yb and high Eu/Eu* is observed at ~ 60 Ma which is broadly coincident with a change in vector of the converging Nazca plate and the onset of regional compression and crustal thickening during the first stage of the Incaic orogeny. The geochemical changes are interpreted to reflect a deepening of the locus of lower crustal magma evolution in which amphibole ± garnet are stabilised as early and abundant fractionating phases and plagioclase is suppressed. Zircons in these rocks show a marked change towards higher Eu/Eu* (> 0.3) and lower Ti (< 9 ppm) compositions after ~ 60 Ma. Numerical modelling of melt Eu systematics and zircon-melt partitioning indicates that the time series of zircon Eu/Eu* in these rocks can be explained by a transition from shallower, plagioclase-dominated fractionation to high-pressure amphibole-dominated fractionation at deep crustal levels from ~ 60 Ma. Our modelling suggests that any redox effects on zircon Eu/Eu* are subordinate compared to changes in melt composition controlled by the fractionating mineral assemblage. We suggest that growth and intermittent recharge of the lower crustal magma reservoir from ~ 60 Ma produced a significant volume of hydrous and metallogenically fertile residual melt which ascended to the upper crust and eventually generated the three giant porphyry Cu–Mo deposits at Quellaveco, Toquepala and Cuajone from ~ 57 Ma. Our study highlights the importance of high-pressure magma differentiation fostered by strongly compressive tectonic regimes in generating world-class porphyry Cu deposits.

Suspected Sunda clouded leopard (Neofelis diardi) predation attempts on two reintroduced Bornean orangutans (Pongo pygmaeus wurmbii) in Bukit Batikap Protection Forest, Central Kalimantan, Indonesia - Jacqueline L. Sunderland-Groves; Maryos V. Tandang; Fiet Hayu Patispathika; Anna Marzec; Andrea Knox; Anton Nurcahyo; Simon J. Husson; Jamartin Sihite (Primates, 2021)

Global Drivers on Southern Ocean Ecosystems: Changing Physical Environments and Anthropogenic Pressures in an Earth System - Simon A. Morley; Doris Abele; David K. A. Barnes; César A. Cárdenas; Cedric Cotté; Julian Gutt; Sian F. Henley; Juan Höfer; Kevin A. Hughes; Stephanie M. Martin; Carlos Moffat; Marilyn Raphael; et al. (Frontiers in Marine Science, 2020)
The manuscript assesses the current and expected future global drivers of Southern Ocean (SO) ecosystems. Atmospheric ozone depletion over the Antarctic since the 1970s, has been a key driver, resulting in springtime cooling of the stratosphere and intensification of the polar vortex, increasing the frequency of positive phases of the Southern Annular Mode (SAM). This increases warm air-flow over the East Pacific sector (Western Antarctic Peninsula) and cold air flow over the West Pacific sector. SAM as well as El Niño Southern Oscillation events also affect the Amundsen Sea Low leading to either positive or negative sea ice anomalies in the west and east Pacific sectors, respectively. The strengthening of westerly winds is also linked to shoaling of deep warmer water onto the continental shelves, particularly in the East Pacific and Atlantic sectors. Air and ocean warming has led to changes in the cryosphere, with glacial and ice sheet melting in both sectors, opening up new ice free areas to biological productivity, but increasing seafloor disturbance by icebergs. The increased melting is correlated with a salinity decrease particularly in the surface 100 m. Such processes could increase the availability of iron, which is currently limiting primary production over much of the SO. Increasing CO 2 is one of the most important SO anthropogenic drivers and is likely to affect marine ecosystems in the coming decades. While levels of many pollutants are lower than elsewhere, persistent organic pollutants (POPs) and plastics have been detected in the SO, with concentrations likely enhanced by migratory species. With increased marine traffic and weakening of ocean barriers the risk of the establishment of non-indigenous species is increased. The continued recovery of the ozone hole creates uncertainty over the reversal in sea ice trends, especially in the light of the abrupt transition from record high to record low Antarctic sea ice extent since spring 2016. The current rate of change in physical and anthropogenic drivers is certain to impact the Marine Ecosystem Assessment of the Southern Ocean (MEASO) region in the near future and will have a wide range of impacts across the marine ecosystem.

Sediment source fingerprinting: benchmarking recent outputs, remaining challenges and emerging themes - Adrian L. Collins; Martin Blackwell; Pascal Boeckx; Charlotte-Anne Chivers; Monica Emelko; Olivier Evrard; Ian Foster; Allen Gellis; Hamid Gholami; Steve Granger; Paul Harris; Arthur J. Horowitz; et al. (Journal of Soils and Sediments, 2020)
Purpose This review of sediment source fingerprinting assesses the current state-of-the-art, remaining challenges and emerging themes. It combines inputs from international scientists either with track records in the approach or with expertise relevant to progressing the science. Methods Web of Science and Google Scholar were used to review published papers spanning the period 2013–2019, inclusive, to confirm publication trends in quantities of papers by study area country and the types of tracers used. The most recent (2018–2019, inclusive) papers were also benchmarked using a methodological decision-tree published in 2017. Scope Areas requiring further research and international consensus on methodological detail are reviewed, and these comprise spatial variability in tracers and corresponding sampling implications for end-members, temporal variability in tracers and sampling implications for end-members and target sediment, tracer conservation and knowledge-based pre-selection, the physico-chemical basis for source discrimination and dissemination of fingerprinting results to stakeholders. Emerging themes are also discussed: novel tracers, concentration-dependence for biomarkers, combining sediment fingerprinting and age-dating, applications to sediment-bound pollutants, incorporation of supportive spatial information to augment discrimination and modelling, aeolian sediment source fingerprinting, integration with process-based models and development of open-access software tools for data processing. Conclusions The popularity of sediment source fingerprinting continues on an upward trend globally, but with this growth comes issues surrounding lack of standardisation and procedural diversity. Nonetheless, the last 2 years have also evidenced growing uptake of critical requirements for robust applications and this review is intended to signpost investigators, both old and new, towards these benchmarks and remaining research challenges for, and emerging options for different applications of, the fingerprinting approach.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Stronger influence of growth rate than severity of drought stress on mortality of large ponderosa pines during the 2012–2015 California drought - Rachel M. Keen; Steve L. Voelker; Barbara J. Bentz; S.-Y. Simon Wang; Ryan Ferrell (Oecologia, 2020)

Stream microbial communities and ecosystem functioning show complex responses to multiple stressors in wastewater - Francis J. Burdon; Yaohui Bai; Marta Reyes; Manu Tamminen; Philipp Staudacher; Simon Mangold; Heinz Singer; Katja Räsänen; Adriano Joss; Scott D. Tiegs; Jukka Jokela; Rik I. L. Eggen; et al. (Global Change Biology, 2020)
Multiple anthropogenic drivers are changing ecosystems globally, with a disproportionate and intensifying impact on freshwater habitats. A major impact of urbanization are inputs from wastewater treatment plants (WWTPs). Initially designed to reduce eutrophication and improve water quality, WWTPs increasingly release a multitude of micropollutants (MPs; i.e., synthetic chemicals) and microbes (including antibiotic‐resistant bacteria) to receiving environments. This pollution may have pervasive impacts on biodiversity and ecosystem services. Viewed through multiple lenses of macroecological and ecotoxicological theory, we combined field, flume, and laboratory experiments to determine the effects of wastewater (WW) on microbial communities and organic‐matter processing using a standardized decomposition assay. First, we conducted a mensurative experiment sampling 60 locations above and below WWTP discharges in 20 Swiss streams. Microbial respiration and decomposition rates were positively influenced by WW inputs via warming and nutrient enrichment, but with a notable exception: WW decreased the activation energy of decomposition, indicating a “slowing” of this fundamental ecosystem process in response to temperature. Second, next‐generation sequencing indicated that microbial community structure below WWTPs was altered, with significant compositional turnover, reduced richness, and evidence of negative MP influences. Third, a series of flume experiments confirmed that although diluted WW generally has positive influences on microbial‐mediated processes, the negative effects of MPs are “masked” by nutrient enrichment. Finally, transplant experiments suggested that WW‐borne microbes enhance decomposition rates. Taken together, our results affirm the multiple stressor paradigm by showing that different aspects of WW (warming, nutrients, microbes, and MPs) jointly influence ecosystem functioning in complex ways. Increased respiration rates below WWTPs potentially generate ecosystem “disservices” via greater carbon evasion from streams and rivers. However, toxic MP effects may fundamentally alter ecological scaling relationships, indicating the need for a rapprochement between ecotoxicological and macroecological perspectives.

Seasonal detections of bearded seal (Erignathus barbatus) vocalizations in Baffin Bay and Davis Strait in relation to sea ice concentration - Tenna K. Boye; Malene J. Simon; Kristin L. Laidre; Frank Rigét; Kathleen M. Stafford (Polar Biology, 2020)

Old growth Afrotropical forests critical for maintaining forest carbon - John R. Poulsen; Vincent P. Medjibe; Lee J. T. White; Zewei Miao; Ludovic Banak‐Ngok; Chris Beirne; Connie J. Clark; Aida Cuni‐Sanchez; Mathias Disney; Jean‐Louis Doucet; Michelle E. Lee; Simon L. Lewis; et al. (Global Ecology and Biogeography, 2020)
Aim Large trees [≥ 70 cm diameter at breast height (DBH)] contribute disproportionately to aboveground carbon stock (AGC) across the tropics but may be vulnerable to changing climate and human activities. Here we determine the distribution, drivers and threats to large trees and high carbon forest. Location Central Africa. Time period Current. Major taxa studied Trees. Methods Using Gabon's new National Resource Inventory of 104 field sites, AGC was calculated from 67,466 trees from 578 species and 97 genera. Power and Michaelis–Menten models assessed the contribution of large trees to AGC. Environmental and anthropogenic drivers of AGC, large trees, and stand variables were modelled using Akaike’s information criterion (AIC) weights to calculate average regression coefficients for all p ossible models. Results Mean AGC for trees ≥ 10 cm DBH in Gabonese forestlands was 141.7 Mg C/ha, with averages of 166.6, 171.3 and 96.6 Mg C/ha in old growth, concession and secondary forest. High carbon forests occurred where large trees are most abundant: 31% of AGC was stored in large trees (2.3% of all stems). Human activities largely drove variation in AGC and large trees, but climate and edaphic conditions also determined stand variables (basal area, tree height, wood density, stem density). AGC and large trees increased with distance from human settlements; AGC was 40% lower in secondary than primary and concession forests and 33% higher in protected than non‐managed areas. Main conclusions AGC and large trees were negatively associated with human activities, highlighting the importance of forest management. Redefining large trees as ≥ 50 cm DBH (4.3% more stems) would account for 20% more AGC. This study demonstrates that protecting relatively undisturbed forests can be disproportionately effective in conserving carbon and suggests that including sustainable forestry in programs like reduced emissions for deforestation and forest degradation could maintain carbon dense forests in logging concessions that are a large proportion of remaining Central African forests.

Facilitating Better Outcomes: How Positive Species Interactions Can Improve Oyster Reef Restoration - Simon E. Reeves; Julianna J. Renzi; Emily K. Fobert; Brian R. Silliman; Boze Hancock; Chris L. Gillies (Frontiers in Marine Science, 2020)

Heavy metals in urban road dusts from Kolkata and Bengaluru, India: implications for human health - Simon R. N. Chenery; Santosh K. Sarkar; Mousumi Chatterjee; Andrew L. Marriott; Michael J. Watts (Environmental Geochemistry and Health, 2020)

Combined Isoflurane-Remifentanil Anaesthesia Permits Resting-State fMRI in Children with Severe Epilepsy and Intellectual Disability - Aaron E. L. Warren; Andrew Davidson; Simon J. Vogrin; A. Simon Harvey; Catherine Bailey; Linda J. Dalic; David F. Abbott; John S. Archer (Brain Topography, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Short Sleep Duration is Associated with Central Arterial Stiffness in Children Independent of Other Lifestyle Behaviors - Lee Stoner; Simon Higgins; Katherine Black; Kim Boggess; Michelle L. Meyer; Andrea Chou; Barbara Galland; Jillian J. Haszard; Kim Meredith-Jones; Pouya Saeedi; Sheila Skeaff; Paula M. L. Skidmore (Journal of Science in Sport and Exercise, 2020)

There is no such thing as ‘undisturbed’ soil and sediment sampling: sampler-induced deformation of salt marsh sediments revealed by 3D X-ray computed tomography - Simon J. Carr; Lucy M. Diggens; Kate L. Spencer (Journal of Soils and Sediments, 2020)

Competition influences tree growth, but not mortality, across environmental gradients in Amazonia and tropical Africa - Danaë M. A. Rozendaal; Oliver L. Phillips; Simon L. Lewis; Kofi Affum‐Baffoe; Esteban Alvarez-Davila; Ana Andrade; Luiz E. O. C. Aragão; Alejandro Araujo‐Murakami; Timothy R. Baker; Olaf Bánki; Roel J. W. Brienen; José Luis C. Camargo; et al. (Ecology, 2020)
Competition among trees is an important driver of community structure and dynamics in tropical forests. Neighboring trees may impact an individual tree’s growth rate and probability of mortality, but large‐scale geographic and environmental variation in these competitive effects has yet to be evaluated across the tropical forest biome. We quantified effects of competition on tree‐level basal area growth and mortality for trees ≥10‐cm diameter across 151 ~1‐ha plots in mature tropical forests in Amazonia and tropical Africa by developing nonlinear models that accounted for wood density, tree size, and neighborhood crowding. Using these models, we assessed how water availability (i.e., climatic water deficit) and soil fertility influenced the predicted plot‐level strength of competition (i.e., the extent to which growth is reduced, or mortality is increased, by competition across all individual trees). On both continents, tree basal area growth decreased with wood density and increased with tree size. Growth decreased with neighborhood crowding, which suggests that competition is important. Tree mortality decreased with wood density and generally increased with tree size, but was apparently unaffected by neighborhood crowding. Across plots, variation in the plot‐level strength of competition was most strongly related to plot basal area (i.e., the sum of the basal area of all trees in a plot), with greater reductions in growth occurring in forests with high basal area, but in Amazonia, the strength of competition also varied with plot‐level wood density. In Amazonia, the strength of competition increased with water availability because of the greater basal area of wetter forests, but was only weakly related to soil fertility. In Africa, competition was weakly related to soil fertility and invariant across the shorter water availability gradient. Overall, our results suggest that competition influences the structure and dynamics of tropical forests primarily through effects on individual tree growth rather than mortality and that the strength of competition largely depends on environment‐mediated variation in basal area.

No Place Like Home? High Residency and Predictable Seasonal Movement of Whale Sharks Off Tanzania - Christoph A. Rohner; Jesse E. M. Cochran; E. Fernando Cagua; Clare E. M. Prebble; Stephanie K. Venables; Michael L. Berumen; Baraka L. Kuguru; Jason Rubens; Juerg M. Brunnschweiler; Simon J. Pierce (Frontiers in Marine Science, 2020)

Increased yield and CO 2 sequestration potential with the C 4 cereal Sorghum bicolor cultivated in basaltic rock dust‐amended agricultural soil - Mike E. Kelland; Peter W. Wade; Amy L. Lewis; Lyla L. Taylor; Binoy Sarkar; M. Grace Andrews; Mark R. Lomas; T. E. Anne Cotton; Simon J. Kemp; Rachael H. James; Christopher R. Pearce; Sue E. Hartley; et al. (Global Change Biology, 2020)
Land‐based enhanced rock weathering (ERW) is a biogeochemical carbon dioxide removal (CDR) strategy aiming to accelerate natural geological processes of carbon sequestration through application of crushed silicate rocks, such as basalt, to croplands and forested landscapes. However, the efficacy of the approach when undertaken with basalt, and its potential co‐benefits for agriculture, require experimental and field evaluation. Here we report that amending a UK clay‐loam agricultural soil with a high loading (10 kg/m 2 ) of relatively coarse‐grained crushed basalt significantly increased the yield (21 ± 9.4%, SE ) of the important C 4 cereal Sorghum bicolor under controlled environmental conditions, without accumulation of potentially toxic trace elements in the seeds. Yield increases resulted from the basalt treatment after 120 days without P‐ and K‐fertilizer addition. Shoot silicon concentrations also increased significantly (26 ± 5.4%, SE ), with potential benefits for crop resistance to biotic and abiotic stress. Elemental budgets indicate substantial release of base cations important for inorganic carbon removal and their accumulation mainly in the soil exchangeable pools. Geochemical reactive transport modelling, constrained by elemental budgets, indicated CO 2 sequestration rates of 2–4 t CO 2 /ha, 1–5 years after a single application of basaltic rock dust, including via newly formed soil carbonate minerals whose long‐term fate requires assessment through field trials. This represents an approximately fourfold increase in carbon capture compared to control plant–soil systems without basalt. Our results build support for ERW deployment as a CDR technique compatible with spreading basalt powder on acidic loamy soils common across millions of hectares of western European and North American agriculture.

Assessing ecological function in the context of species recovery - H. Resit Akçakaya; Ana S. L. Rodrigues; David A. Keith; E. J. Milner‐Gulland; Eric W. Sanderson; Simon Hedges; David P. Mallon; Molly K. Grace; Barney Long; Erik Meijaard; P. J. Stephenson (Conservation Biology, 2020)
Species interactions matter to conservation. Setting an ambitious recovery target for a species requires considering the size, density, and demographic structure of its populations such that they fulfill the interactions, roles, and functions of the species in the ecosystems in which they are embedded. A recently proposed framework for an International Union for Conservation of Nature Green List of Species formalizes this requirement by defining a fully recovered species in terms of representation, viability, and functionality. Defining and quantifying ecological function from the viewpoint of species recovery is challenging in concept and application, but also an opportunity to insert ecological theory into conservation practice. We propose 2 complementary approaches to assessing a species’ ecological functions: confirmation (listing interactions of the species, identifying ecological processes and other species involved in these interactions, and quantifying the extent to which the species contributes to the identified ecological process) and elimination (inferring functionality by ruling out symptoms of reduced functionality, analogous to the red‐list approach that focuses on symptoms of reduced viability). Despite the challenges, incorporation of functionality into species recovery planning is possible in most cases and it is essential to a conservation vision that goes beyond preventing extinctions and aims to restore a species to levels beyond what is required for its viability. This vision focuses on conservation and recovery at the species level and sees species as embedded in ecosystems, influencing and being influenced by the processes in those ecosystems. Thus, it connects and integrates conservation at the species and ecosystem levels.

The Role of Forest Elephants in Shaping Tropical Forest–Savanna Coexistence - Anabelle W. Cardoso; Yadvinder Malhi; Imma Oliveras; David Lehmann; Josué Edzang Ndong; Edmond Dimoto; Emma Bush; Kathryn Jeffery; Nicolas Labriere; Simon L. Lewis; Lee T. J. White; William Bond; et al. (Ecosystems, 2020)

Conservation assessment of cassava wild relatives in central Brazil - Marcelo F. Simon; Talita S. Reis; J. Moises Mendoza F.; Thalyssa K. M. Arquelão; João B. A. Bringel; Sérgio E. Noronha; Márcio L. L. Martins; Carlos A. S. Ledo; Marcos J. Silva; Alexandre B. Sampaio; Eraldo T. Matricardi; Aldicir Scariot (Biodiversity and Conservation, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Strong divergent selection at multiple loci in two closely related species of ragworts adapted to high and low elevations on Mount Etna - Edgar L. Y. Wong; Bruno Nevado; Owen G. Osborne; Alexander S. T. Papadopulos; Jon R. Bridle; Simon J. Hiscock; Dmitry A. Filatov (Molecular Ecology, 2020)
Recently diverged species present particularly informative systems for studying speciation and maintenance of genetic divergence in the face of gene flow. We investigated speciation in two closely related Senecio species, S. aethnensis and S. chrysanthemifolius , which grow at high and low elevations, respectively, on Mount Etna, Sicily and form a hybrid zone at intermediate elevations. We used a newly generated genome‐wide single nucleotide polymorphism (SNP) dataset from 192 individuals collected over 18 localities along an elevational gradient to reconstruct the likely history of speciation, identify highly differentiated SNPs, and estimate the strength of divergent selection. We found that speciation in this system involved heterogeneous and bidirectional gene flow along the genome, and species experienced marked population size changes in the past. Furthermore, we identified highly‐differentiated SNPs between the species, some of which are located in genes potentially involved in ecological differences between species (such as photosynthesis and UV response). We analysed the shape of these SNPs’ allele frequency clines along the elevational gradient. These clines show significantly variable coincidence and concordance, indicative of the presence of multifarious selective forces. Selection against hybrids is estimated to be very strong (0.16–0.78) and one of the highest reported in literature. The combination of strong cumulative selection across the genome and previously identified intrinsic incompatibilities probably work together to maintain the genetic and phenotypic differentiation between these species – pointing to the importance of considering both intrinsic and extrinsic factors when studying divergence and speciation.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Re-emergence of North Atlantic subsurface ocean temperature anomalies in a seasonal forecast system - Jeremy P. Grist; Bablu Sinha; Helene. T. Hewitt; Aurélie Duchez; Craig MacLachlan; Patrick Hyder; Simon A. Josey; Joël J.-M. Hirschi; Adam T. Blaker; Adrian. L. New; Adam A. Scaife; Chris D. Roberts (Climate Dynamics, 2019)

Review of Australian east coast low pressure systems and associated extremes - Andrew J. Dowdy; Acacia Pepler; Alejandro Di Luca; Leone Cavicchia; Graham Mills; Jason P. Evans; Simon Louis; Kathleen L. McInnes; Kevin Walsh (Climate Dynamics, 2019)

Boreal Forest Floor Greenhouse Gas Emissions Across a Pleurozium schreberi-Dominated, Wildfire-Disturbed Chronosequence - Kelly E. Mason; Simon Oakley; Lorna E. Street; María Arróniz-Crespo; David L. Jones; Thomas H. DeLuca; Nicholas J. Ostle (Ecosystems, 2019)

Projecting impacts of global climate and land‐use scenarios on plant biodiversity using compositional‐turnover modelling - Moreno Di Marco; Tom D. Harwood; Andrew J. Hoskins; Chris Ware; Samantha L. L. Hill; Simon Ferrier (Global Change Biology, 2019)
Nations have committed to ambitious conservation targets in response to accelerating rates of global biodiversity loss. Anticipating future impacts is essential to inform policy decisions for achieving these targets, but predictions need to be of sufficiently high spatial resolution to forecast the local effects of global change. As part of the intercomparison of biodiversity and ecosystem services models of the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, we present a fine‐resolution assessment of trends in the persistence of global plant biodiversity. We coupled generalized dissimilarity models, fitted to >52 million records of >254 thousand plant species, with the species–area relationship, to estimate the effect of land‐use and climate change on global biodiversity persistence. We estimated that the number of plant species committed to extinction over the long term has increased by 60% globally between 1900 and 2015 (from ~10,000 to ~16,000). This number is projected to decrease slightly by 2050 under the most optimistic scenario of land‐use change and to substantially increase (to ~18,000) under the most pessimistic scenario. This means that, in the absence of climate change, scenarios of sustainable socio‐economic development can potentially bring extinction risk back to pre‐2000 levels. Alarmingly, under all scenarios, the additional impact from climate change might largely surpass that of land‐use change. In this case, the estimated number of species committed to extinction increases by 3.7–4.5 times compared to land‐use‐only projections. African regions (especially central and southern) are expected to suffer some of the highest impacts into the future, while biodiversity decline in Southeast Asia (which has previously been among the highest globally) is projected to slow down. Our results suggest that environmentally sustainable land‐use planning alone might not be sufficient to prevent potentially dramatic biodiversity loss, unless a stabilization of climate to pre‐industrial times is observed.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Air-Sea Fluxes With a Focus on Heat and Momentum - Meghan F. Cronin; Chelle L. Gentemann; James Edson; Iwao Ueki; Mark Bourassa; Shannon Brown; Carol Anne Clayson; Chris W. Fairall; J. Thomas Farrar; Sarah T. Gille; Sergey Gulev; Simon A. Josey; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Ground Data are Essential for Biomass Remote Sensing Missions - Jérôme Chave; Stuart J. Davies; Oliver L. Phillips; Simon L. Lewis; Plinio Sist; Dmitry Schepaschenko; John Armston; Tim R. Baker; David Coomes; Mathias Disney; Laura Duncanson; Bruno Hérault; et al. (Surveys in Geophysics, 2019)

Breeding and wintering bird distributions in Britain and Ireland from citizen science bird atlases - Simon Gillings; Dawn E. Balmer; Brian J. Caffrey; Iain S. Downie; David W. Gibbons; Peter C. Lack; James B. Reid; J. Tim R. Sharrock; Robert L. Swann; Robert J. Fuller (Global Ecology and Biogeography, 2019)
Motivation We undertook large citizen science surveys of bird distributions (atlases) in Britain and Ireland, aimed at quantifying breeding bird distributions on a 20‐year cycle and wintering bird distributions on a c . 30‐year cycle. We use these to generate spatially referenced information on apparent changes in bird distributions over c . 40 years. Main type of variable contained Detection of breeding and wintering bird species in grid squares during five periods, and changes in detection between periods. The combined distribution dataset contains 1,410,938 records detailing detections of 465 bird species in 3,880 grid cells in different periods. The combined distribution change dataset contains 1,297,791 records describing stability, apparent colonization or apparent extinction of individual species in grid squares between pairs of atlases spanning up to c. 40 years. Spatial location and grain Grid squares (10 km × 10 km) containing land throughout Britain, Ireland, the Isle of Man and the Channel Islands. The majority of data are at 10‐km resolution, but data for rare species are summarized at 20‐ or 50‐km resolution to protect sensitive locations. Time period The data represent summarized detection information derived from fieldwork during five periods: the breeding seasons 1968–1972, 1988–1991 and 2008–2011, and the winters 1981/1982–1983/1984 and 2007/2008–2010/2011. Major taxa studied and level of measurement Birds; their distribution derived from citizen science surveys. Software format Data are supplied as comma‐separated text files.

Drier tropical forests are susceptible to functional changes in response to a long‐term drought - Jesús Aguirre‐Gutiérrez; Imma Oliveras; Sami Rifai; Sophie Fauset; Stephen Adu‐Bredu; Kofi Affum‐Baffoe; Timothy R. Baker; Ted R. Feldpausch; Agne Gvozdevaite; Wannes Hubau; Nathan J. B. Kraft; Simon L. Lewis; et al. (Ecology Letters, 2019)
Climatic changes have profound effects on the distribution of biodiversity, but untangling the links between climatic change and ecosystem functioning is challenging, particularly in high diversity systems such as tropical forests. Tropical forests may also show different responses to a changing climate, with baseline climatic conditions potentially inducing differences in the strength and timing of responses to droughts. Trait‐based approaches provide an opportunity to link functional composition, ecosystem function and environmental changes. We demonstrate the power of such approaches by presenting a novel analysis of long‐term responses of different tropical forest to climatic changes along a rainfall gradient. We explore how key ecosystem's biogeochemical properties have shifted over time as a consequence of multi‐decadal drying. Notably, we find that drier tropical forests have increased their deciduous species abundance and generally changed more functionally than forests growing in wetter conditions, suggesting an enhanced ability to adapt ecologically to a drying environment.

Congo Basin peatlands: threats and conservation priorities - Greta C. Dargie; Ian T. Lawson; Tim J. Rayden; Lera Miles; Edward T. A. Mitchard; Susan E. Page; Yannick E. Bocko; Suspense A. Ifo; Simon L. Lewis (Mitigation and Adaptation Strategies for Global Change, 2019)

Correction to: The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Arthur L. Beaudet; Steve D. M. Brown; Mary E. Dickinson; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Conservation Genetics, 2019)

Neural correlates of emotional valence processing in Parkinson’s disease: dysfunction in the subcortex - Peter T. Bell; Moran Gilat; James M. Shine; Katie L. McMahon; Simon J. G. Lewis; David A. Copland (Brain Imaging and Behavior, 2019)

Tools to Enrich Vulnerability Assessment and Adaptation Planning for Coastal Communities in Data-Poor Regions: Application to a Case Study in Madagascar - K. L. Cochrane; H. Rakotondrazafy; S. Aswani; T. Chaigneau; N. Downey-Breedt; A. Lemahieu; A. Paytan; G. Pecl; E. Plagányi; E. Popova; E. I. van Putten; Warwick H. H. Sauer; et al. (Frontiers in Marine Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Storylines: an alternative approach to representing uncertainty in physical aspects of climate change - Theodore G. Shepherd; Emily Boyd; Raphael A. Calel; Sandra C. Chapman; Suraje Dessai; Ioana M. Dima-West; Hayley J. Fowler; Rachel James; Douglas Maraun; Olivia Martius; Catherine A. Senior; Adam H. Sobel; et al. (Climatic Change, 2018)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Soil multifunctionality and drought resistance are determined by plant structural traits in restoring grassland - Ellen L. Fry; Joanna Savage; Amy L. Hall; Simon Oakley; W. J. Pritchard; Nicholas J. Ostle; Richard F. Pywell; James M. Bullock; Richard D. Bardgett (Ecology, 2018)
It is increasingly recognized that belowground responses to vegetation change are closely linked to plant functional traits. However, our understanding is limited concerning the relative importance of different plant traits for soil functions and of the mechanisms by which traits influence soil properties in the real world. Here we test the hypothesis that taller species, or those with complex rooting structures, are associated with high rates of nutrient and carbon (C) cycling in grassland. We further hypothesized that communities dominated by species with deeper roots may be more resilient to drought. These hypotheses were tested in a 3‐yr grassland restoration experiment on degraded ex‐arable land in southern England. We sowed three trait‐based plant functional groups, assembled using database derived values of plant traits, and their combinations into bare soil. This formed a range of plant trait syndromes onto which we superimposed a simulated drought 2 yr after initial establishment. We found strong evidence that community weighted mean ( CWM ) of plant height is negatively associated with soil nitrogen cycling and availability and soil multifunctionality. We propose that this was due to an exploitative resource capture strategy that was inappropriate in shallow chalk soils. Further, complexity of root architecture was positively related to soil multifunctionality throughout the season, with fine fibrous roots being associated with greater rates of nutrient cycling. Drought resistance of soil functions including ecosystem respiration, mineralization, and nitrification were positively related to functional divergence of rooting depth, indicating that, in shallow chalk soils, a range of water capture strategies is necessary to maintain functions. Finally, after 3 yr of the experiment, we did not detect any links between the plant traits and microbial communities, supporting the finding that traits based on plant structure and resource foraging capacity are the main variables driving soil function in the early years of grassland conversion. We suggest that screening recently restored grassland communities for potential soil multifunctionality and drought resilience may be possible based on rooting architecture and plant height. These results indicate that informed assembly of plant communities based on plant traits could aid in the restoration of functioning in degraded soil.

Nephrotoxicity and Kidney Transport Assessment on 3D Perfused Proximal Tubules - Marianne K. Vormann; Linda Gijzen; Simon Hutter; Lisette Boot; Arnaud Nicolas; Angelique van den Heuvel; Jelle Vriend; Chee Ping Ng; Tom T. G. Nieskens; Vincent van Duinen; Bjorn de Wagenaar; Rosalinde Masereeuw; et al. (The AAPS Journal, 2018)

Ocean warming has a greater effect than acidification on the early life history development and swimming performance of a large circumglobal pelagic fish - Sue‐Ann Watson; Bridie J. M. Allan; David E. McQueen; Simon Nicol; Darren M. Parsons; Stephen M. J. Pether; Stephen Pope; Alvin N. Setiawan; Neville Smith; Carly Wilson; Philip L. Munday (Global Change Biology, 2018)
Ocean warming and acidification are serious threats to marine life; however, their individual and combined effects on large pelagic and predatory fishes are poorly understood. We determined the effects of projected future temperature and carbon dioxide ( CO 2 ) levels on survival, growth, morphological development and swimming performance on the early life stages of a large circumglobal pelagic fish, the yellowtail kingfish Seriola lalandi . Eggs, larvae and juveniles were reared in cross‐factored treatments of temperature (21 and 25°C) and p CO 2 (500 and 985 μatm) from fertilisation to 25 days post hatching (dph). Temperature had the greatest effect on survival, growth and development. Survivorship was lower, but growth and morphological development were faster at 25°C, with surviving fish larger and more developed at 1, 11 and 21 dph. Elevated p CO 2 affected size at 1 dph, but not at 11 or 21 dph, and did not affect survival or morphological development. Elevated temperature and p CO 2 had opposing effects on swimming performance at 21 dph. Critical swimming speed ( U crit ) was increased by elevated temperature but reduced by elevated p CO 2 . Additionally, elevated temperature increased the proportion of individuals that responded to a startle stimulus, reduced latency to respond and increased maximum escape speed, potentially due to the more advanced developmental stage of juveniles at 25°C. By contrast, elevated p CO 2 reduced the distance moved and average speed in response to a startle stimulus. Our results show that higher temperature is likely to be the primary driver of global change impacts on kingfish early life history; however, elevated p CO 2 could affect critical aspects of swimming performance in this pelagic species. Our findings will help parameterise and structure fisheries population dynamics models and improve projections of impacts to large pelagic fishes under climate change scenarios to better inform adaptation and mitigation responses.

Sedimentary macrofossil records reveal ecological change in English lakes: implications for conservation - Helen Bennion; Carl D. Sayer; Stewart J. Clarke; Thomas A. Davidson; Neil L. Rose; Ben Goldsmith; Ruth Rawcliffe; Amy Burgess; Gina Clarke; Simon Turner; Emma Wiik (Journal of Paleolimnology, 2018)

Genetic diversity of a hitchhiker and prized food source in the Anthropocene: the Asian green mussel Perna viridis (Mollusca, Mytilidae) - P. Joana Dias; Matthew R. Gilg; Sherralee S. Lukehurst; W. Jason Kennington; Mareike Huhn; Hawis H. Madduppa; Simon J. McKirdy; Paul de Lestang; Serena L. M. Teo; Serina Siew Chen Lee; Justin I. McDonald (Biological Invasions, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Response of benthic fauna to experimental bottom fishing: A global meta‐analysis - Marija Sciberras; Jan Geert Hiddink; Simon Jennings; Claire L Szostek; Kathryn M Hughes; Brian Kneafsey; Leo J Clarke; Nick Ellis; Adriaan D Rijnsdorp; Robert A McConnaughey; Ray Hilborn; Jeremy S Collie; et al. (Fish and Fisheries, 2018)
Bottom‐contact fishing gears are globally the most widespread anthropogenic sources of direct disturbance to the seabed and associated biota. Managing these fishing disturbances requires quantification of gear impacts on biota and the rate of recovery following disturbance. We undertook a systematic review and meta‐analysis of 122 experiments on the effects‐of‐bottom fishing to quantify the removal of benthos in the path of the fishing gear and to estimate rates of recovery following disturbance. A gear pass reduced benthic invertebrate abundance by 26% and species richness by 19%. The effect was strongly gear‐specific, with gears that penetrate deeper into the sediment having a significantly larger impact than those that penetrate less. Sediment composition (% mud and presence of biogenic habitat) and the history of fishing disturbance prior to an experimental fishing event were also important predictors of depletion, with communities in areas that were not previously fished, predominantly muddy or biogenic habitats being more strongly affected by fishing. Sessile and low mobility biota with longer life‐spans such as sponges, soft corals and bivalves took much longer to recover after fishing (>3 year) than mobile biota with shorter life‐spans such as polychaetes and malacostracans (

Genetic diversity through time and space: diversity and demographic history from natural history specimens and serially sampled contemporary populations of the threatened Gouldian finch (Erythrura gouldiae) - Peri E. Bolton; Lee A. Rollins; James Brazill-Boast; Kimberley L. Maute; Sarah Legge; Jeremy J. Austin; Simon C. Griffith (Conservation Genetics, 2018)

Ocean acidification in New Zealand waters: trends and impacts - Cliff S. Law; James J. Bell; Helen C. Bostock; Chris E. Cornwall; Vonda J. Cummings; Kim Currie; Simon K. Davy; Malindi Gammon; Christopher D. Hepburn; Catriona L. Hurd; Miles Lamare; Sara E. Mikaloff‐Fletcher; et al. (New Zealand Journal of Marine and Freshwater Research, 2018)
The threat posed by ocean acidification (OA) to the diversity and productivity of New Zealand marine ecosystems is assessed in a synthesis of published trends and impacts. A 20‐year time series in Subantarctic water, and a national coastal monitoring programme, provide insight into pH variability, and context for experimental design, modelling and projections. A review of the potential impact of changes in the carbonate system on the major phyla in New Zealand waters confirms international observations that calcifying organisms, and particularly their early life‐history stages, are vulnerable. The synthesis considers ecosystem and socio‐economic impacts, and identifies current knowledge gaps and future research directions, including mechanistic studies of OA sensitivity. Advanced ecosystem models of OA, that incorporate the indirect effects of OA and interactions with other climate stressors, are required for robust projection of the future status of New Zealand marine ecosystems.

A cross‐continental comparison of assemblages of seed‐ and fruit‐feeding insects in tropical rain forests: Faunal composition and rates of attack - Yves Basset; Chris Dahl; Richard Ctvrtecka; Sofia Gripenberg; Owen T. Lewis; Simon T. Segar; Petr Klimes; Héctor Barrios; John W. Brown; Sarayudh Bunyavejchewin; Buntika A. Butcher; Anthony I. Cognato; et al. (Journal of Biogeography, 2018)
Aim Insects feeding on seeds and fruits represent interesting study systems, potentially able to lower the fitness of their host plants. In addition to true seed eaters, a suite of insects feed on the fleshy parts of fruits. We examined the likelihood of community convergence in whole insect assemblages attacking seeds/fruits in three tropical rain forests. Location Three Forest GEO permanent forest plots within different biogeographical regions: Barro Colorado Island (Panama), Khao Chong (Thailand) and Wanang (Papua New Guinea). Methods We surveyed 1,186 plant species and reared 1.1 ton of seeds/fruits that yielded 80,600 insects representing at least 1,678 species. We assigned seeds/fruits to predation syndromes on the basis of plant traits relevant to insects, seed/fruit appearance and mesocarp thickness. Results We observed large differences in insect faunal composition, species richness and guild structure between our three study sites. We hypothesize that the high species richness of insect feeding on seeds/fruits in Panama may result from a conjunction of low plant species richness and high availability of dry fruits. Insect assemblages were weakly influenced by seed predation syndromes, both at the local and regional scale, and the effect of host phylogeny varied also among sites. At the driest site (Panama), the probability of seeds of a plant species being attacked depended more on seed availability than on the measured seed traits of that plant species. However, when seeds were attacked, plant traits shaping insect assemblages were difficult to identify and not related to seed availability. Main conclusions We observed only weak evidence of community convergence at the intercontinental scale among these assemblages. Our study suggests that seed eaters may be most commonly associated with dry fruits at relatively dry tropical sites where fleshy fruits may be less prevalent.

Launching Environmental Microbiology : ‘The most effective way to do it, is to do it’ - Amanda J. L. McLean‐Inglis; Simon P. Rallison (Environmental Microbiology, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Childhood adversity associated with white matter alteration in the corpus callosum, corona radiata, and uncinate fasciculus of psychiatrically healthy adults - Simon McCarthy-Jones; Lena K. L. Oestreich; Amanda E. Lyall; Zora Kikinis; Dominick T. Newell; Peter Savadjiev; Martha E. Shenton; Marek Kubicki; Ofer Pasternak; Thomas J. Whitford (Brain Imaging and Behavior, 2018)

Plants eavesdrop on cues produced by snails and induce costly defenses that affect insect herbivores - John L. Orrock; Brian M. Connolly; Won-Gyu Choi; Peter W. Guiden; Sarah J. Swanson; Simon Gilroy (Oecologia, 2018)

Nutrients from salmon parents alter selection pressures on their offspring - Sonya K. Auer; Graeme J. Anderson; Simon McKelvey; Ronald D. Bassar; Darryl McLennan; John D. Armstrong; Keith H. Nislow; Helen K. Downie; Lynn McKelvey; Thomas A.J. Morgan; Karine Salin; Danielle L. Orrell; et al. (Ecology Letters, 2018)
Organisms can modify their surrounding environment, but whether these changes are large enough to feed back and alter their evolutionary trajectories is not well understood, particularly in wild populations. Here we show that nutrient pulses from decomposing Atlantic salmon ( Salmo salar ) parents alter selection pressures on their offspring with important consequences for their phenotypic and genetic diversity. We found a strong survival advantage to larger eggs and faster juvenile metabolic rates in streams lacking carcasses but not in streams containing this parental nutrient input. Differences in selection intensities led to significant phenotypic divergence in these two traits among stream types. Stronger selection in streams with low parental nutrient input also decreased the number of surviving families compared to streams with high parental nutrient levels. Observed effects of parent‐derived nutrients on selection pressures provide experimental evidence for key components of eco‐evolutionary feedbacks in wild populations.

Copeptin reflects physiological strain during thermal stress - Michael John Stacey; Simon K. Delves; Sophie E. Britland; Adrian J. Allsopp; Stephen J. Brett; Joanne L. Fallowfield; David R. Woods (European Journal of Applied Physiology, 2018)
Purpose To prevent heat-related illnesses, guidelines recommend limiting core body temperature ( T c ) ≤ 38 °C during thermal stress. Copeptin, a surrogate for arginine vasopressin secretion, could provide useful information about fluid balance, thermal strain and health risks. It was hypothesised that plasma copeptin would rise with dehydration from occupational heat stress, concurrent with sympathoadrenal activation and reduced glomerular filtration, and that these changes would reflect T c responses. Methods Volunteers ( n = 15) were recruited from a British Army unit deployed to East Africa. During a simulated combat assault (3.5 h, final ambient temperature 27 °C), T c was recorded by radiotelemetry to differentiate volunteers with maximum T c > 38 °C versus ≤ 38 °C. Blood was sampled beforehand and afterwards, for measurement of copeptin, cortisol, free normetanephrine, osmolality and creatinine. Results There was a significant ( P < 0.05) rise in copeptin from pre- to post-assault (10.0 ± 6.3 vs. 16.7 ± 9.6 pmol L −1 , P < 0.001). Although osmolality did not increase, copeptin correlated strongly with osmolality after the exposure ( r = 0.70, P = 0.004). In volunteers with maximum T c > 38 °C ( n = 8) vs ≤ 38 °C ( n = 7) there were significantly greater elevations in copeptin (10.4 vs. 2.4 pmol L −1 ) and creatinine (10 vs. 2 μmol L −1 ), but no differences in cortisol, free normetanephrine or osmolality. Conclusions Changes in copeptin reflected T c response more closely than sympathoadrenal markers or osmolality. Dynamic relationships with tonicity and kidney function may help to explain this finding. As a surrogate for integrated physiological strain during work in a field environment, copeptin assay could inform future measures to prevent heat-related illnesses.

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Contaminated sediment dynamics in peatland headwater catchments - Emma L. Shuttleworth; Gareth D. Clay; Martin G. Evans; Simon M. Hutchinson; James J. Rothwell (Journal of Soils and Sediments, 2017)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Cis ‐regulatory evolution in a wild primate: Infection‐associated genetic variation drives differential expression of MHC ‐ DQA 1 in vitro - Noah D. Simons; Geeta N. Eick; Maria J. Ruiz‐Lopez; Patrick A. Omeja; Colin A. Chapman; Tony L. Goldberg; Nelson Ting; Kirstin N. Sterner (Molecular Ecology, 2017)
Few studies have combined genetic association analyses with functional characterization of infection‐associated SNP s in natural populations of nonhuman primates. Here, we investigate the relationship between host genetic variation, parasitism and natural selection in a population of red colobus ( Procolobus rufomitratus tephrosceles ) in Kibale National Park, Uganda. We collected parasitological, cellular and genomic data to test the following hypotheses: (i) MHC ‐ DQA 1 regulatory genetic variation is associated with control of whipworm ( Trichuris ) infection in a natural population of red colobus; (ii) infection‐associated SNP s are functional in driving differential gene expression in vitro; and (iii) balancing selection has shaped patterns of variation in the MHC ‐ DQA 1 promoter. We identified two SNP s in the MHC ‐ DQA 1 promoter, both in transcription factor binding sites, and both of which are associated with decreased control of Trichuris infection. We characterized the function of both SNP s by testing differences in gene expression between the two alleles of each SNP in two mammalian cell lines. Alleles of one of the SNP s drove differential gene expression in both cell lines, while the other SNP drove differences in expression in one of the cell lines. Additionally, we found evidence of balancing selection acting on the MHC ‐ DQA 1 promoter, including extensive trans‐species polymorphisms between red colobus and other primates, and an excess of intermediate‐frequency alleles relative to genome‐wide, coding and noncoding RAD seq data. Our data suggest that balancing selection provides adaptive regulatory flexibility that outweighs the consequences of increased parasite infection intensity in heterozygotes.

Exome analysis of Smith–Magenis-like syndrome cohort identifies de novo likely pathogenic variants - Seth I. Berger; Carla Ciccone; Karen L. Simon; May Christine Malicdan; Thierry Vilboux; Charles Billington; Roxanne Fischer; Wendy J. Introne; Andrea Gropman; Jan K. Blancato; James C. Mullikin; William A. Gahl; et al. (Human Genetics, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Prefrontal activation may predict working-memory training gain in normal aging and mild cognitive impairment - Anouk Vermeij; Roy P. C. Kessels; Linda Heskamp; Esther M. F. Simons; Paul L. J. Dautzenberg; Jurgen A. H. R. Claassen (Brain Imaging and Behavior, 2017)

Sexual response of male Drosophila to honey bee queen mandibular pheromone: implications for genetic studies of social insects - Justin R. Croft; Tom Liu; Alison L. Camiletti; Anne F. Simon; Graham J. Thompson (Journal of Comparative Physiology A, 2017)

Spatial Distribution and Residency of Green and Loggerhead Sea Turtles Using Coastal Reef Habitats in Southern Mozambique - Jessica L. Williams; Simon J. Pierce; Chris A. Rohner; Mariana M. P. B. Fuentes; Mark Hamann (Frontiers in Marine Science, 2017)

Changes in pathways and vectors of biological invasions in Northwest Europe - Alexandra Zieritz; Belinda Gallardo; Simon J. Baker; J. Robert Britton; Johan L. C. H. van Valkenburg; Hugo Verreycken; David C. Aldridge (Biological Invasions, 2017)

Where Does River Runoff Matter for Coastal Marine Conservation? - Alexa Fredston-Hermann; Christopher J. Brown; Simon Albert; Carissa J. Klein; Sangeeta Mangubhai; Joanna L. Nelson; Lida Teneva; Amelia Wenger; Steven D. Gaines; Benjamin S. Halpern (Frontiers in Marine Science, 2016)

Human centromere repositioning within euchromatin after partial chromosome deletion - Lori L. Sullivan; Kristin A. Maloney; Aaron J. Towers; Simon G. Gregory; Beth A. Sullivan (Chromosome Research, 2016)

Lessons on Climate Sensitivity From Past Climate Changes - Anna S. von der Heydt; Henk A. Dijkstra; Roderik S. W. van de Wal; Rodrigo Caballero; Michel Crucifix; Gavin L. Foster; Matthew Huber; Peter Köhler; Eelco Rohling; Paul J. Valdes; Peter Ashwin; Sebastian Bathiany; et al. (Current Climate Change Reports, 2016)

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Enhancing conservation of A ustralian freshwater ecosystems: identification of freshwater flagship fishes and relevant target audiences - Brendan C Ebner; David L Morgan; Adam Kerezsy; Scott Hardie; Stephen J Beatty; Jamie E Seymour; James A Donaldson; Simon Linke; Stirling Peverell; David Roberts; Thomas Espinoza; Nadine Marshall; et al. (Fish and Fisheries, 2016)
Flagship species, especially mammals and birds, are commonly used to increase awareness of conservation issues in marine and terrestrial ecosystems. However, flagship species oriented programs are often ad hoc with initiatives scarce in the freshwater context. Here, we aim to identify potential flagship candidates that would appeal to a broad cross section of society at a continental scale where freshwater ecosystems are under threat from human impacts. We identified 19 species from a list of 299 Australian freshwater fishes on the basis of body size, trophic guild and threatened species status assuming these characteristics of flagship species are transferable from previous work on terrestrial flagship species. We considered the potential of species to be of international appeal but focused mostly on eight relevant interest groups within Australia. This followed the rationale that public engagement with conservation issues in freshwater systems might be more effective if the link between fish species and the decisions people make were better understood, and we acknowledge the diverging interests of stakeholders. This scoping work contributes towards addressing the challenges of connecting societies to the principles of sharing water resources with ecosystems, and represents the first continental‐scale assessment of its kind.

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Short-interval cortical inhibition and intracortical facilitation during submaximal voluntary contractions changes with fatigue - Sandra K. Hunter; Chris J. McNeil; Jane E. Butler; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2016)

A 2-Substituted 8-Hydroxyquinoline Stimulates Neural Stem Cell Proliferation by Modulating ROS Signalling - Cathryn L. Haigh; Carolin Tumpach; Steven J. Collins; Simon C. Drew (Cell Biochemistry and Biophysics, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

A saturated SNP linkage map for the orange wheat blossom midge resistance gene Sm1 - Mulualem T. Kassa; Sabrina Haas; Edgar Schliephake; Clare Lewis; Frank M. You; Curtis J. Pozniak; Ilona Krämer; Dragan Perovic; Andrew G. Sharpe; Pierre R. Fobert; Michael Koch; Ian L. Wise; et al. (Theoretical and Applied Genetics, 2016)

Land cover change and carbon emissions over 100 years in an A frican biodiversity hotspot - Simon Willcock; Oliver L. Phillips; Philip J. Platts; Ruth D. Swetnam; Andrew Balmford; Neil D. Burgess; Antje Ahrends; Julian Bayliss; Nike Doggart; Kathryn Doody; Eibleis Fanning; Jonathan M. H. Green; et al. (Global Change Biology, 2016)
Agricultural expansion has resulted in both land use and land cover change ( LULCC ) across the tropics. However, the spatial and temporal patterns of such change and their resulting impacts are poorly understood, particularly for the presatellite era. Here, we quantify the LULCC history across the 33.9 million ha watershed of Tanzania's Eastern Arc Mountains, using geo‐referenced and digitized historical land cover maps (dated 1908, 1923, 1949 and 2000). Our time series from this biodiversity hotspot shows that forest and savanna area both declined, by 74% (2.8 million ha) and 10% (2.9 million ha), respectively, between 1908 and 2000. This vegetation was replaced by a fivefold increase in cropland, from 1.2 million ha to 6.7 million ha. This LULCC implies a committed release of 0.9 Pg C (95% CI : 0.4–1.5) across the watershed for the same period, equivalent to 0.3 Mg C ha −1 yr −1 . This is at least threefold higher than previous estimates from global models for the same study area. We then used the LULCC data from before and after protected area creation, as well as from areas where no protection was established, to analyse the effectiveness of legal protection on land cover change despite the underlying spatial variation in protected areas. We found that, between 1949 and 2000, forest expanded within legally protected areas, resulting in carbon uptake of 4.8 (3.8–5.7) Mg C ha −1 , compared to a committed loss of 11.9 (7.2–16.6) Mg C ha −1 within areas lacking such protection. Furthermore, for nine protected areas where LULCC data are available prior to and following establishment, we show that protection reduces deforestation rates by 150% relative to unprotected portions of the watershed. Our results highlight that considerable LULCC occurred prior to the satellite era, thus other data sources are required to better understand long‐term land cover trends in the tropics.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Mesophotic fishes of the Abrolhos Shelf, the largest reef ecosystem in the South Atlantic - T. Simon; H. T. Pinheiro; R. L. Moura; A. Carvalho‐Filho; L. A. Rocha; A. S. Martins; E. Mazzei; R. B. Francini‐Filho; G. M. Amado‐Filho; J.‐C. Joyeux (Journal of Fish Biology, 2016)
Fishes inhabiting rhodolith beds and reefs at mesophotic depths on the Abrolhos Shelf, which encompasses the largest and richest coral reef formation in the South Atlantic Ocean, were assessed through technical diving and remotely operated vehicles ( ROVs ). A total of 74 fish species were recorded, including at least one new species, one new record for the south‐western Atlantic and six new records for the Abrolhos region. Overfishing, mining and port activities are already threatening many endangered and commercially important species recorded on the mesophotic reefs of Abrolhos Shelf, and the establishment of marine protected areas and off‐reserve fisheries regulations are urgently needed.

Decreased integrity of the fronto-temporal fibers of the left inferior occipito-frontal fasciculus associated with auditory verbal hallucinations in schizophrenia - Lena K. L. Oestreich; Simon McCarthy-Jones; Thomas J. Whitford (Brain Imaging and Behavior, 2016)

The microRNA-29 family in cartilage homeostasis and osteoarthritis - Linh T. T. Le; Tracey E. Swingler; Natalie Crowe; Tonia L. Vincent; Matthew J. Barter; Simon T. Donell; Anne M. Delany; Tamas Dalmay; David A. Young; Ian M. Clark (Journal of Molecular Medicine, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Three‐dimensional structure and cyanobacterial activity within a desert biological soil crust - Hagai Raanan; Vincent J. M. N. L. Felde; Stephan Peth; Sylvie Drahorad; Danny Ionescu; Gil Eshkol; Haim Treves; Peter Felix‐Henningsen; Simon M. Berkowicz; Nir Keren; Rainer Horn; Martin Hagemann; et al. (Environmental Microbiology, 2016)
Summary Desert biological soil crusts ( BSC s) are formed by adhesion of soil particles to polysaccharides excreted by filamentous cyanobacteria, the pioneers and main producers in this habitat. Biological soil crust destruction is a central factor leading to land degradation and desertification. We study the effect of BSC structure on cyanobacterial activity. Micro‐scale structural analysis using X ‐ray microtomography revealed a vesiculated layer 1.5–2.5 mm beneath the surface in close proximity to the cyanobacterial location. Light profiles showed attenuation with depth of 1%–5% of surface light within 1 mm but also revealed the presence of ‘light pockets’, coinciding with the vesiculated layer, where the irradiance was 10‐fold higher than adjacent crust parts at the same depth. Maximal photosynthetic activity, examined by O 2 concentration profiles, was observed 1 mm beneath the surface and another peak in association with the ‘light pockets’. Thus, photosynthetic activity may not be visible to currently used remote sensing techniques, suggesting that BSC s' contribution to terrestrial productivity is underestimated. Exposure to irradiance higher than 10% full sunlight diminished chlorophyll fluorescence, whereas O 2 evolution and CO 2 uptake rose, indicating that fluorescence did not reflect cyanobacterial photosynthetic activity. Our data also indicate that although resistant to high illumination, the BSC ‐inhabiting cyanobacteria function as ‘low‐light adapted’ organisms.

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Perceived discrimination and cancer screening behaviors in US Hispanics: the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study - Cristina Valdovinos; Frank J. Penedo; Carmen R. Isasi; Molly Jung; Robert C. Kaplan; Rebeca Espinoza Giacinto; Patricia Gonzalez; Vanessa L. Malcarne; Krista Perreira; Hugo Salgado; Melissa A. Simon; Lisa M. Wruck; et al. (Cancer Causes & Control, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Heritability of telomere length in the Zebra Finch - Els Atema; Ellis Mulder; Hannah L. Dugdale; Michael Briga; Arie J. van Noordwijk; Simon Verhulst (Journal of Ornithology, 2015)

Phylogeography of six codistributed New Zealand cicadas and their relationship to multiple biogeographical boundaries suggest a re‐evaluation of the Taupo Line - Emily A. Ellis; David C. Marshall; Kathy B. R. Hill; Christopher L. Owen; Peter J. J. Kamp; Chris Simon (Journal of Biogeography, 2015)
Aim Comparative biogeographers question the extent to which codistributed species respond similarly to environmental change. Such responses should create similar, appropriately timed patterns of cladogenesis among codistributed taxa compared to evolutionary independence, which may limit the predictions that can be made for unstudied species. Here, we compare phylogeographical patterns across ecologically divergent, codistributed taxa in the light of New Zealand's palaeohistory. Location North Island, New Zealand. Methods Mitochondrial DNA from six codistributed cicada species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta , K. scutellaris and K. dugdalei ) was analysed using phylogenetic methods and molecular dating techniques. We analysed phylogeographical distributions using analysis of molecular variance ( AMOVA ) to determine the significance of hypothesized biogeographical boundaries for clade differentiation and spatial distribution of genetic diversity. Results Five species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta and K. scutellaris ) show various degrees of intraspecific concordance with biogeographical boundaries found in previously studied taxa – the Kauri Line, the Northland Line and the newly identified Cockayne's Line. Clade splits of forest species correlate with the Kauri Line and/or Northland Line, whereas splits of scrub/hill species correlate with Cockayne's Line. Four species ( Kikihia ochrina , K. cutora , K. laneorum and K. cauta ) diversified before the Last Glacial Maximum ( LGM , 20 ka), whereas two species ( K. scutellaris and K. dugdalei ) show only post‐ LGM diversification. Main conclusions Despite species idiosyncrasies, we see the imprint of shared palaeoclimatic/geological events. We distinguish between (1) the importance of biogeographical lines as the demarcation between older genetically diverse and newer genetically depauperate populations, and (2) the importance of lines as biogeographical boundaries between sister clades. We also stress the importance of dating clade splits to ensure consistency with explanations for the biogeographical lines in question. We suggest that the Taupo Line has been overemphasized as a biogeographical boundary, whereas the importance of the mountain axis running north‐east to south‐west (‘Cockayne's Line’) has been overlooked.

A recessive homozygous p.Asp92Gly SDHD mutation causes prenatal cardiomyopathy and a severe mitochondrial complex II deficiency - Charlotte L. Alston; Camilla Ceccatelli Berti; Emma L. Blakely; Monika Oláhová; Langping He; Colin J. McMahon; Simon E. Olpin; Iain P. Hargreaves; Cecilia Nolli; Robert McFarland; Paola Goffrini; Maureen J. O’Sullivan; et al. (Human Genetics, 2015)

Antimicrobial susceptibility of rapidly growing mycobacteria using the rapid colorimetric method - I. B. Ramis; M. Cnockaert; A. von Groll; C. L. Nogueira; S. C. Leão; E. Andre; A. Simon; J. C. Palomino; P. E. A. da Silva; P. Vandamme; A. Martin (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Remote sensing of intertidal habitats predicts West Indian topsnail population expansion but reveals scale-dependent bias - Erin L. Meyer; Nicholas J. Matzke; Simon J. Williams (Journal of Coastal Conservation, 2015)

Exploiting the intrinsic hydrocarbon-degrading microbial capacities in oil tank bottom sludge and waste soil for sludge bioremediation - E. M. Adetutu; C. Bird; K. K. Kadali; A. Bueti; E. Shahsavari; M. Taha; S. Patil; P. J. Sheppard; T. Makadia; K. L. Simons; A. S. Ball (International Journal of Environmental Science and Technology, 2015)

Population dynamics of Thaumastocoris peregrinus in Eucalyptus plantations of South Africa - Ryan L. Nadel; Michael J. Wingfield; Mary C. Scholes; Jeffrey R. Garnas; Simon A. Lawson; Bernard Slippers (Journal of Pest Science, 2015)

Variation in plant diversity in mediterranean‐climate ecosystems: the role of climatic and topographical stability - Richard M. Cowling; Alastair J. Potts; Peter L. Bradshaw; Jonathan Colville; Margarita Arianoutsou; Simon Ferrier; Felix Forest; Nikolaos M. Fyllas; Stephen D. Hopper; Fernando Ojeda; Şerban Procheş; Rhian J. Smith; et al. (Journal of Biogeography, 2015)
Aim Although all five of the major mediterranean‐climate ecosystems ( MCE s) of the world are recognized as loci of high plant species diversity and endemism, they show considerable variation in regional‐scale richness. Here, we assess the role of stable Pleistocene climate and Cenozoic topography in explaining variation in regional richness of the globe's MCE s. We hypothesize that older, more climatically stable MCE s would support more species, because they have had more time for species to accumulate than MCE s that were historically subject to greater topographic upheavals and fluctuating climates. Location South‐western Africa (Cape), south‐western Australia, California, central Chile and the eastern (Greece) and western (Spain) Mediterranean Basin. Methods We estimated plant diversity for each MCE as the intercepts of species–area curves that are homogeneous in slope across all regions. We used two down‐scaled global circulation models of the Last Glacial Maximum ( LGM ) to quantify climate stability by comparing the change in the location of MCE s between the LGM and present. We quantified the Cenozoic topographic stability of each MCE by comparing contemporary topographic profiles with those present in the late Oligocene and the early Pliocene. Results The most diverse MCE s – Cape and Australia – had the highest Cenozoic environmental stability, and the least diverse – Chile and California – had the lowest stability. Main conclusions Variation in plant diversity in MCE s is likely to be a consequence not of differences in diversification rates, but rather the persistence of numerous pre‐Pliocene clades in the more stable MCE s. The extraordinary plant diversity of the Cape is a consequence of the combined effects of both mature and recent radiations, the latter associated with increased habitat heterogeneity produced by mild tectonic uplift in the Neogene.

Species associations structured by environment and land‐use history promote beta‐diversity in a temperate forest - Stephen J. Murphy; Lívia D. Audino; James Whitacre; Jenalle L. Eck; John W. Wenzel; Simon A. Queenborough; Liza S. Comita (Ecology, 2015)
Patterns of diversity and community composition in forests are controlled by a combination of environmental factors, historical events, and stochastic or neutral mechanisms. Each of these processes has been linked to forest community assembly, but their combined contributions to alpha and beta‐diversity in forests has not been well explored. Here we use variance partitioning to analyze ~40 000 individual trees of 49 species, collected within 137 ha of sampling area spread across a 900‐ha temperate deciduous forest reserve in Pennsylvania to ask (1) To what extent is site‐to‐site variation in species richness and community composition of a temperate forest explained by measured environmental gradients and by spatial descriptors (used here to estimate dispersal‐assembly or unmeasured, spatially structured processes)? (2) How does the incorporation of land‐use history information increase the importance attributed to deterministic community assembly? and (3) How do the distributions and abundances of individual species within the community correlate with these factors? Environmental variables (i.e., topography, soils, and distance to stream), spatial descriptors (i.e., spatial eigenvectors derived from Cartesian coordinates), and land‐use history variables (i.e., land‐use type and intensity, forest age, and distance to road), explained about half of the variation in both species richness and community composition. Spatial descriptors explained the most variation, followed by measured environmental variables and then by land‐use history. Individual species revealed variable responses to each of these sets of predictor variables. Several species were associated with stream habitats, and others were strictly delimited across opposing north‐ and south‐facing slopes. Several species were also associated with areas that experienced recent (i.e.,

Risk factors for endometrial cancer in black and white women: a pooled analysis from the epidemiology of endometrial cancer consortium (E2C2) - Michele L. Cote; Tala Alhajj; Julie J. Ruterbusch; Leslie Bernstein; Louise A. Brinton; William J. Blot; Chu Chen; Margery Gass; Sarah Gaussoin; Brian Henderson; Eunjung Lee; Pamela L. Horn-Ross; et al. (Cancer Causes & Control, 2015)

Conclusions of the Worldwide Integrated Assessment on the risks of neonicotinoids and fipronil to biodiversity and ecosystem functioning - J. P. van der Sluijs; V. Amaral-Rogers; L. P. Belzunces; M. F. I. J. Bijleveld van Lexmond; J-M. Bonmatin; M. Chagnon; C. A. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; et al. (Environmental Science and Pollution Research, 2015)

Systemic insecticides (neonicotinoids and fipronil): trends, uses, mode of action and metabolites - N. Simon-Delso; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; M. Chagnon; C. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; et al. (Environmental Science and Pollution Research, 2015)

Effects of neonicotinoids and fipronil on non-target invertebrates - L. W. Pisa; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; C. A. Downs; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; M. McField; C. A. Morrissey; D. A. Noome; et al. (Environmental Science and Pollution Research, 2015)
We assessed the state of knowledge regarding the effects of large-scale pollution with neonicotinoid insecticides and fipronil on non-target invertebrate species of terrestrial, freshwater and marine environments. A large section of the assessment is dedicated to the state of knowledge on sublethal effects on honeybees ( Apis mellifera ) because this important pollinator is the most studied non-target invertebrate species. Lepidoptera (butterflies and moths), Lumbricidae (earthworms), Apoidae sensu lato (bumblebees, solitary bees) and the section “other invertebrates” review available studies on the other terrestrial species. The sections on freshwater and marine species are rather short as little is known so far about the impact of neonicotinoid insecticides and fipronil on the diverse invertebrate fauna of these widely exposed habitats. For terrestrial and aquatic invertebrate species, the known effects of neonicotinoid pesticides and fipronil are described ranging from organismal toxicology and behavioural effects to population-level effects. For earthworms, freshwater and marine species, the relation of findings to regulatory risk assessment is described. Neonicotinoid insecticides exhibit very high toxicity to a wide range of invertebrates, particularly insects, and field-realistic exposure is likely to result in both lethal and a broad range of important sublethal impacts. There is a major knowledge gap regarding impacts on the grand majority of invertebrates, many of which perform essential roles enabling healthy ecosystem functioning. The data on the few non-target species on which field tests have been performed are limited by major flaws in the outdated test protocols. Despite large knowledge gaps and uncertainties, enough knowledge exists to conclude that existing levels of pollution with neonicotinoids and fipronil resulting from presently authorized uses frequently exceed the lowest observed adverse effect concentrations and are thus likely to have large-scale and wide ranging negative biological and ecological impacts on a wide range of non-target invertebrates in terrestrial, aquatic, marine and benthic habitats.

Evidence of land‐sea transfer of the zoonotic pathogen Campylobacter to a wildlife marine sentinel species - Johanna L. Baily; Guillaume Méric; Sion Bayliss; Geoffrey Foster; Simon E. Moss; Eleanor Watson; Ben Pascoe; Jane Mikhail; Romain Pizzi; Robert J. Goldstone; David G. E. Smith; Kim Willoughby; et al. (Molecular Ecology, 2015)
Environmental pollution often accompanies the expansion and urbanization of human populations where sewage and wastewaters commonly have an impact on the marine environments. Here, we explored the potential for faecal bacterial pathogens, of anthropic origin, to spread to marine wildlife in coastal areas. The common zoonotic bacterium Campylobacter was isolated from grey seals ( Halichoerus grypus ), an important sentinel species for environmental pollution, and compared to isolates from wild birds, agricultural sources and clinical samples to characterize possible transmission routes. Campylobacter jejuni was present in half of all grey seal pups sampled (24/50 dead and 46/90 live pups) in the breeding colony on the Isle of May (Scotland), where it was frequently associated with histological evidence of disease. Returning yearling animals (19/19) were negative for C . jejuni suggesting clearance of infection while away from the localized colony infection source. The genomes of 90 isolates from seals were sequenced and characterized using a whole‐genome multilocus sequence typing ( MLST ) approach and compared to 192 published genomes from multiple sources using population genetic approaches and a probabilistic genetic attribution model to infer the source of infection from MLST data. The strong genotype‐host association has enabled the application of source attribution models in epidemiological studies of human campylobacteriosis, and here assignment analyses consistently grouped seal isolates with those from human clinical samples. These findings are consistent with either a common infection source or direct transmission of human campylobacter to grey seals, raising concerns about the spread of human pathogens to wildlife marine sentinel species in coastal areas.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

An assessment of chemical contaminants in sediments from the St. Thomas East End Reserves, St. Thomas, USVI - Anthony S. Pait; S. Ian Hartwell; Andrew L. Mason; Robert A. Warner; Christopher F. G. Jeffrey; Anne M. Hoffman; Dennis A. Apeti; Simon J. Pittman (Environmental Monitoring and Assessment, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Heather Moorland Vegetation and Air Pollution: A Comparison and Synthesis of Three National Gradient Studies - Richard J. Payne; Simon J. M. Caporn; Christopher D. Field; Jacky A. Carroll; Jill L. Edmondson; Andrea Britton; Nancy B. Dise (Water, Air, & Soil Pollution, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Genetic structure of populations of whale sharks among ocean basins and evidence for their historic rise and recent decline - Thomas M. Vignaud; Jeffrey A. Maynard; Raphael Leblois; Mark G. Meekan; Ricardo Vázquez‐Juárez; Dení Ramírez‐Macías; Simon J. Pierce; David Rowat; Michael L. Berumen; Champak Beeravolu; Sandra Baksay; Serge Planes (Molecular Ecology, 2014)
This study presents genetic evidence that whale sharks, Rhincodon typus , are comprised of at least two populations that rarely mix and is the first to document a population expansion. Relatively high genetic structure is found when comparing sharks from the Gulf of Mexico with sharks from the Indo‐Pacific. If mixing occurs between the Indian and Atlantic Oceans, it is not sufficient to counter genetic drift. This suggests whale sharks are not all part of a single global metapopulation. The significant population expansion we found was indicated by both microsatellite and mitochondrial DNA . The expansion may have happened during the Holocene, when tropical species could expand their range due to sea‐level rise, eliminating dispersal barriers and increasing plankton productivity. However, the historic trend of population increase may have reversed recently. Declines in genetic diversity are found for 6 consecutive years at Ningaloo Reef in Australia. The declines in genetic diversity being seen now in Australia may be due to commercial‐scale harvesting of whale sharks and collision with boats in past decades in other countries in the Indo‐Pacific. The study findings have implications for models of population connectivity for whale sharks and advocate for continued focus on effective protection of the world's largest fish at multiple spatial scales.

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Limited genetic structure among broad-scale regions for two commercially harvested, tropical deep-water snappers in New Caledonia - Kim L. Loeun; Sharyn Goldstien; Dianne Gleeson; Simon J. Nicol; Corey J. A. Bradshaw (Fisheries Science, 2014)

Detailed multidisciplinary monitoring reveals pre- and co-eruptive signals at Nyamulagira volcano (North Kivu, Democratic Republic of Congo) - Benoît Smets; Nicolas d’Oreye; François Kervyn; Matthieu Kervyn; Fabien Albino; Santiago R. Arellano; Montfort Bagalwa; Charles Balagizi; Simon A. Carn; Thomas H. Darrah; José Fernández; Bo Galle; et al. (Bulletin of Volcanology, 2014)

Reestablishment of former wintering grounds by New Zealand southern right whales - Emma L. Carroll; William J. Rayment; Alana M. Alexander; C. Scott Baker; Nathalie J. Patenaude; Debbie Steel; Rochelle Constantine; Rosalind Cole; Laura J. Boren; Simon Childerhouse (Marine Mammal Science, 2014)
Historically, the range of the southern right whale ( SRW ) included winter calving grounds around the North and South Islands (mainland) of New Zealand ( NZ ) and in the NZ subantarctic Auckland and Campbell Islands. Due to extensive whaling in the 19th and 20th centuries, no SRW was seen around mainland NZ for nearly four decades (1928–1963). Here we present evidence for the regular use of the mainland NZ wintering ground, presumably from a remnant population that persisted in the NZ subantarctic Auckland and Campbell Islands. SRW s have been sighted every year around mainland NZ since 1988, with 125 sightings during the focus of this work: from 2003 to 2010. There were 28 cow‐calf pairs sighted around mainland NZ from 2003 to 2010, compared with 11 sightings from 1991 to 2002. Furthermore, two females, identified by DNA profiles, were sighted with calves around mainland at 4 yr intervals: the first evidence of female site fidelity to the mainland NZ calving ground. Individual identification from photographs of natural markings and DNA profiles provided information on within‐year movements and residency around the mainland, and further evidence for exchange between the mainland and subantarctic wintering grounds. Despite these promising signs, the distribution of NZ SRW s remains primarily concentrated in the NZ subantarctic.

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Circulating galectin-3 in infections and non-infectious inflammatory diseases - J. Oever; E. J. Giamarellos-Bourboulis; F. L. Veerdonk; F. F. Stelma; A. Simon; M. Janssen; M. Johnson; A. Pachot; B.-J. Kullberg; L. A. B. Joosten; M. G. Netea (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Evidence for covalently bonded chlorine–fullerene formed by ozonation and chlorination at room temperature - Alla L. Alpatova; Melissa J. Baumann; Simon H. Davies; Susan J. Masten (Environmental Chemistry Letters, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Effect of amount and timing of subsurface drip irrigation on corn yield - Simon J. van Donk; James L. Petersen; Don R. Davison (Irrigation Science, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Genome‐wide patterns of divergence and gene flow across a butterfly radiation - Nicola J. Nadeau; Simon H. Martin; Krzysztof M. Kozak; Camilo Salazar; Kanchon K. Dasmahapatra; John W. Davey; Simon W. Baxter; Mark L. Blaxter; James Mallet; Chris D. Jiggins (Molecular Ecology, 2013)
The H eliconius butterflies are a diverse recent radiation comprising multiple levels of divergence with ongoing gene flow between species. The recently sequenced genome of H eliconius melpomene allowed us to investigate the genomic evolution of this group using dense RAD marker sequencing. Phylogenetic analysis of 54 individuals robustly supported reciprocal monophyly of H . melpomene and H eliconius cydno and refuted previous phylogenetic hypotheses that H . melpomene may be paraphylectic with respect to H . cydno . H eliconius timareta also formed a monophyletic clade closely related but distinct from H . cydno with H eliconius heurippa falling within this clade. We find evidence for genetic admixture between sympatric populations of the sister clades H . melpomene and H . cydno/timareta , particularly between H . cydno and H . melpomene from Central America and between H . timareta and H . melpomene from the eastern slopes of the A ndes. Between races, divergence is primarily explained by isolation by distance and there is no detectable genetic population structure between parapatric races, suggesting that hybrid zones between races are not zones of secondary contact. Our results also support previous findings that colour pattern loci are shared between populations and species with similar colour pattern elements. Furthermore, this pattern is almost unique to these genomic regions, with only a very small number of other loci showing significant similarity between populations and species with similar colour patterns.

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Change and variability in sea ice during the 2007–2008 Canadian International Polar Year program - David G. Barber; Matthew G. Asplin; Richard L. Raddatz; Lauren M. Candlish; Scot Nickels; Stephanie Meakin; Klaus P. Hochheim; Jennifer V. Lukovich; Ryan J. Galley; Simon J. Prinsenberg (Climatic Change, 2012)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Genome scans reveal candidate regions involved in the adaptation to host plant in the pea aphid complex - J. Jaquiéry; S. Stoeckel; P. Nouhaud; L. Mieuzet; F. Mahéo; F. Legeai; N. Bernard; A. Bonvoisin; R. Vitalis; J‐C. Simon (Molecular Ecology, 2012)
A major goal in evolutionary biology is to uncover the genetic basis of adaptation. Divergent selection exerted on ecological traits may result in adaptive population differentiation and reproductive isolation and affect differentially the level of genetic divergence along the genome. Genome‐wide scan of large sets of individuals from multiple populations is a powerful approach to identify loci or genomic regions under ecologically divergent selection. Here, we focused on the pea aphid, a species complex of divergent host races, to explore the organization of the genomic divergence associated with host plant adaptation and ecological speciation. We analysed 390 microsatellite markers located at variable distances from predicted genes in replicate samples of sympatric populations of the pea aphid collected on alfalfa, red clover and pea, which correspond to three common host‐adapted races reported in this species complex. Using a method that accounts for the hierarchical structure of our data set, we found a set of 11 outlier loci that show higher genetic differentiation between host races than expected under the null hypothesis of neutral evolution. Two of the outliers are close to olfactory receptor genes and three other nearby genes encoding salivary proteins. The remaining outliers are located in regions with genes of unknown functions, or which functions are unlikely to be involved in interactions with the host plant. This study reveals genetic signatures of divergent selection across the genome and provides an inventory of candidate genes responsible for plant specialization in the pea aphid, thereby setting the stage for future functional studies.

Mineralisation of Weathered Crude Oil by a Hydrocarbonoclastic Consortia in Marine Mesocosms - Krishna K. Kadali; Keryn L. Simons; Petra J. Sheppard; Andrew S. Ball (Water, Air, & Soil Pollution, 2012)

Changes in the choice of colorectal cancer screening tests in primary care settings from 7,845 prospectively collected surveys - Martin C. S. Wong; George K. John; Hoyee W. Hirai; Thomas Y. T. Lam; Arthur K. C. Luk; Jessica Y. L. Ching; Simon S. M. Ng; Francis K. L. Chan; Sian M. Griffiths; Joseph J. Y. Sung (Cancer Causes & Control, 2012)

Paternity assignment and demographic closure in the New Zealand southern right whale - EMMA L. CARROLL; SIMON J. CHILDERHOUSE; MARK CHRISTIE; SHANE LAVERY; NATHALIE PATENAUDE; ALANA ALEXANDER; ROCHELLE CONSTANTINE; DEBBIE STEEL; LAURA BOREN; C. SCOTT BAKER (Molecular Ecology, 2012)
The identification and characterization of reproductively isolated subpopulations or ‘stocks’ are essential for effective conservation and management decisions. This can be difficult in vagile marine species like marine mammals. We used paternity assignment and ‘gametic recapture’ to examine the reproductive autonomy of southern right whales ( Eubalaena australis ) on their New Zealand (NZ) calving grounds. We derived DNA profiles for 34 mother–calf pairs from skin biopsy samples, using sex‐specific markers, 13 microsatellite loci and mtDNA haplotypes. We constructed DNA profiles for 314 adult males, representing 30% of the census male abundance of the NZ stock, previously estimated from genotypic mark‐recapture modelling to be 1085 (95% CL 855, 1416). Under the hypothesis of demographic closure and the assumption of equal reproductive success among males, we predict: (i) the proportion of paternities assigned will reflect the proportion of the male population sampled and (ii) the gametic mark–recapture (GMR) estimate of male abundance will be equivalent to the census male estimate for the NZ stock. Consistent with these predictions, we found that the proportion of assigned paternities equalled the proportion of the census male population size sampled. Using the sample of males as the initial capture, and paternity assignment as the recapture, the GMR estimate of male abundance was 1001 (95% CL 542, 1469), similar to the male census estimate. These findings suggest that right whales returning to the NZ calving ground are reproductively autonomous on a generational timescale, as well as isolated by maternal fidelity on an evolutionary timescale, from others in the Indo‐Pacific region.

Erratum to: The ecotoxicological recovery of Ely Creek and tributaries (Lee County, VA) after remediation of acid mine drainage - Matthew L. Simon; Donald S. Cherry; Rebecca J. Currie; Carl E. Zipper (Environmental Monitoring and Assessment, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

E-Selectin Ligands as Mechanosensitive Receptors on Neutrophils in Health and Disease - S. D. Chase; J. L. Magnani; S. I. Simon (Annals of Biomedical Engineering, 2012)

Mining and validation of pyrosequenced simple sequence repeats (SSRs) from American cranberry (Vaccinium macrocarpon Ait.) - H. Zhu; D. Senalik; B. H. McCown; E. L. Zeldin; J. Speers; J. Hyman; N. Bassil; K. Hummer; P. W. Simon; J. E. Zalapa (Theoretical and Applied Genetics, 2012)

Transforming growth factor beta signaling in adult cardiovascular diseases and repair - Thomas Doetschman; Joey V. Barnett; Raymond B. Runyan; Todd D. Camenisch; Ronald L. Heimark; Henk L. Granzier; Simon J. Conway; Mohamad Azhar (Cell and Tissue Research, 2012)

Yield losses in grain sorghum due to rust infection - Jodie A. White; Malcolm J. Ryley; Doug L. George; Gary A. Kong; Simon C. White (Australasian Plant Pathology, 2012)

Influence of insects and fungal pathogens on individual and population parameters of Cirsium arvense in its native and introduced ranges - Michael G. Cripps; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler; Grant R. Edwards (Biological Invasions, 2011)

Immunologically restricted patients exhibit a pronounced inflammation and inadequate response to hypoxia in fracture hematomas - Paula Hoff; T. Gaber; K. Schmidt-Bleek; U. Sentürk; C. L. Tran; K. Blankenstein; S. Lütkecosmann; J. Bredahl; H. J. Schüler; P. Simon; G. Wassilew; F. Unterhauser; et al. (Immunologic Research, 2011)

Exotic tree species displace indigenous ones on farms at intermediate altitudes around Mount Kenya - Katja Kehlenbeck; Roeland Kindt; Fergus L. Sinclair; Anthony J. Simons; Ramni Jamnadass (Agroforestry Systems, 2011)

Plant leaf roughness analysis by texture classification with generalized Fourier descriptors in a dimensionality reduction context - L. Journaux; J.-C. Simon; M. F. Destain; F. Cointault; J. Miteran; A. Piron (Precision Agriculture, 2011)

Data Requirements for the Reliable Use of Atomic Pair Distribution Functions in Amorphous Pharmaceutical Fingerprinting - Timur Dykhne; Ryan Taylor; Alastair Florence; Simon J. L. Billinge (Pharmaceutical Research, 2011)

Effect of dietary alginic acid on juvenile tilapia (Oreochromis niloticus) intestinal microbial balance, intestinal histology and growth performance - Daniel L. Merrifield; Glenn M. Harper; Sanaa Mustafa; Oliana Carnevali; Simona Picchietti; Simon J. Davies (Cell and Tissue Research, 2011)

Long-interval intracortical inhibition in a human hand muscle - Chris J. McNeil; Peter G. Martin; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2011)

The Kimberlites and related rocks of the Kuruman Kimberlite Province, Kaapvaal Craton, South Africa - Cara L. Donnelly; William L. Griffin; Suzanne Y. O’Reilly; Norman J. Pearson; Simon R. Shee (Contributions to Mineralogy and Petrology, 2011)

Approaches to the total synthesis of biologically active natural products: studies directed towards bryostatins - Anthony P. Green; Simon Hardy; Alan T. L. Lee; Eric J. Thomas (Phytochemistry Reviews, 2010)

Glycemic index, glycemic load, and the risk of pancreatic cancer among postmenopausal women in the women’s health initiative observational study and clinical trial - M. S. Simon; J. M. Shikany; M. L. Neuhouser; T. Rohan; K. Nirmal; Y. Cui; J. Abrams (Cancer Causes & Control, 2010)

Polymorphisms in oxidative stress and inflammation pathway genes, low-dose ionizing radiation, and the risk of breast cancer among US radiologic technologists - Sara J. Schonfeld; Parveen Bhatti; Elizabeth E. Brown; Martha S. Linet; Steven L. Simon; Robert M. Weinstock; Amy A. Hutchinson; Marilyn Stovall; Dale L. Preston; Bruce H. Alexander; Michele M. Doody; Alice J. Sigurdson (Cancer Causes & Control, 2010)

Evaluating the protection of wildlife in parks: the case of African buffalo in Serengeti - K. L. Metzger; A. R. E. Sinclair; Ray Hilborn; J. Grant C. Hopcraft; Simon A. R. Mduma (Biodiversity and Conservation, 2010)

The invasion route for an insect pest species: the tobacco aphid in the New World - F. A. ZEPEDA‐PAULO; J.‐C. SIMON; C. C. RAMÍREZ; E. FUENTES‐CONTRERAS; J. T. MARGARITOPOULOS; A. C. C. WILSON; C. E. SORENSON; L. M. BRIONES; R. AZEVEDO; D. V. OHASHI; C. LACROIX; L. GLAIS; et al. (Molecular Ecology, 2010)
Biological invasions are rapid evolutionary events in which populations are usually subject to a founder event during introduction followed by rapid adaptation to the new environment. Molecular tools and Bayesian approaches have shown their utility in exploring different evolutionary scenarios regarding the invasion routes of introduced species. We examined the situation for the tobacco aphid, Myzus persicae nicotianae , a recently introduced aphid species in Chile. Using seven microsatellite loci and approximate Bayesian computation, we studied populations of the tobacco aphid sampled from several American and European countries, identifying the most likely source populations and tracking the route of introduction to Chile. Our population genetic data are consistent with available historical information, pointing to an introduction route of the tobacco aphid from Europe and/or from other putative populations (e.g. Asia) with subsequent introduction through North America to South America. Evidence of multiple introductions to North America from different genetic pools, with successive loss of genetic diversity from Europe towards North America and a strong bottleneck during the southward introduction to South America, was also found. Additionally, we examined the special case of a widespread multilocus genotype that was found in all American countries examined. This case provides further evidence for the existence of highly successful genotypes or ‘superclones’ in asexually reproducing organisms.

The structure of dopamine induced α-synuclein oligomers - Agata Rekas; Robert B. Knott; Anna Sokolova; Kevin J. Barnham; Keyla A. Perez; Colin L. Masters; Simon C. Drew; Roberto Cappai; Cyril C. Curtain; Chi L. L. Pham (European Biophysics Journal, 2010)

Enemy release does not increase performance of Cirsium arvense in New Zealand - Michael G. Cripps; Grant R. Edwards; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler (Plant Ecology, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

The high value of logged tropical forests: lessons from northern Borneo - Nicholas J. Berry; Oliver L. Phillips; Simon L. Lewis; Jane K. Hill; David P. Edwards; Noel B. Tawatao; Norhayati Ahmad; David Magintan; Chey V. Khen; M. Maryati; Robert C. Ong; Keith C. Hamer (Biodiversity and Conservation, 2010)

Fur seals at Macquarie Island: post-sealing colonisation, trends in abundance and hybridisation of three species - Simon David Goldsworthy; Jane McKenzie; Brad Page; Melanie L. Lancaster; Peter D. Shaughnessy; Louise P. Wynen; Susan A. Robinson; Kristian J. Peters; Alastair M. M. Baylis; Rebecca R. McIntosh (Polar Biology, 2009)

Synthesis, characterization, and reaction pathways for the formation of a GMP adduct of a cytotoxic thiocyanato ruthenium arene complex - Fuyi Wang; Abraha Habtemariam; Erwin P. L. van der Geer; Robert J. Deeth; Robert Gould; Simon Parsons; Peter J. Sadler (JBIC Journal of Biological Inorganic Chemistry, 2009)

Climate and agricultural context shape reproductive mode variation in an aphid crop pest - A. GILABERT; J.‐C. SIMON; L. MIEUZET; F. HALKETT; S. STOECKEL; M. PLANTEGENEST; C.‐A. DEDRYVER (Molecular Ecology, 2009)
In aphids, reproductive mode is generally assumed to be selected for by winter climate. Sexual lineages produce frost‐resistant eggs, conferring an advantage in regions with cold winters, while asexual lineages predominate in regions with mild winters. However, habitat and resource heterogeneities are known to exert a strong influence on sex maintenance and might modulate the effect of climate on aphid reproductive strategies. We carried out a hierarchical sampling in northern France to investigate whether reproductive mode variation of the aphid Rhopalosiphum padi is driven by winter climate conditions, by habitat and resource heterogeneities represented by a range of host plants or by both factors. We confirmed the coexistence in R. padi populations of two genetic clusters associated with distinct reproductive strategies. Asexual lineages predominated, whatever the surveyed year and location. However, we detected a between‐year variation in the local contribution of both clusters, presumably associated with preceding winter severity. No evidence for host‐driven niche differentiation was found in the field on six Poaceae among sexual and asexual lineages. Two dominant multilocus genotypes (∼70% of the sample), having persisted over a 10‐year period, were equally abundant on different plant species and locations, indicating their large ecological tolerance. Our results fit theoretical predictions of the influence of winter climate on the balance between sexual and asexual lineages. They also highlight the importance of current agricultural practices which seem to favour a small number of asexual generalist genotypes and their migration across large areas of monotonous environments.

From captivity to the wild and back: An attempt to release Keiko the killer whale - M. Simon; M. B. Hanson; L. Murrey; J. Tougaard; F. Ugarte (Marine Mammal Science, 2009)

The Effects of l-theanine on Alpha-Band Oscillatory Brain Activity During a Visuo-Spatial Attention Task - Manuel Gomez-Ramirez; Simon P. Kelly; Jennifer L. Montesi; John J. Foxe (Brain Topography, 2009)

Composition and significance of picophytoplankton in Antarctic waters - Simon W. Wright; Akira Ishikawa; Harvey J. Marchant; Andrew T. Davidson; Rick L. van den Enden; Geraldine V. Nash (Polar Biology, 2009)

Seasonal decline in reproductive performance varies with colony size in the fairy martin, Petrochelidon ariel - Michael J. L. Magrath; Peter Santema; Karen M. Bouwman; Dušan M. Brinkhuizen; Simon C. Griffith; Naomi E. Langmore (Behavioral Ecology and Sociobiology, 2009)

Extreme changes to gene expression associated with homoploid hybrid speciation - MATTHEW J. HEGARTY; GARY L. BARKER; ADRIAN C. BRENNAN; KEITH J. EDWARDS; RICHARD J. ABBOTT; SIMON J. HISCOCK (Molecular Ecology, 2009)
Hybridization is an important cause of abrupt speciation. Hybrid speciation without a change in ploidy (homoploid hybrid speciation) is well‐established in plants but has also been reported in animals and fungi. A notable example of recent homoploid hybrid speciation is Senecio squalidus (Oxford ragwort), which originated in the UK in the 18th Century following introduction of hybrid material from a hybrid zone between S. chrysanthemifolius and S. aethnensis on Mount Etna, Sicily. To investigate genetic divergence between these taxa, we used complementary DNA microarrays to compare patterns of floral gene expression. These analyses revealed major differences in gene expression between the parent species and wild and resynthesized S. squalidus . Comparisons of gene expression between S. aethnensis , S. chrysanthemifolius and natural S. squalidus identified genes potentially involved in local environmental adaptation. The analysis also revealed non‐additive patterns of gene expression in the hybrid relative to its progenitors. These expression changes were more dramatic and widespread in resynthesized hybrids than in natural S. squalidus , suggesting that a unique expression pattern may have been fixed during the allopatric divergence of British S. squalidus . We speculate that hybridization‐induced gene‐expression change may provide an immediate source of novel phenotypic variation upon which selection can act to facilitate homoploid hybrid speciation in plants.

Failure of the mite-pathogenic fungus Neozygites tanajoae and the predatory mite Neoseiulus idaeus to control a population of the cassava green mite, Mononychellus tanajoa - Simon L. Elliot; Gilberto J. de Moraes; John D. Mumford (Experimental and Applied Acarology, 2008)

Effects of Methyl Jasmonate and an Endophytic Fungus on Plant Resistance to Insect Herbivores - Lacy Simons; Thomas L. Bultman; T. J. Sullivan (Journal of Chemical Ecology, 2008)

Host range expansion of an introduced insect pest through multiple colonizations of specialized clones - J. PECCOUD; C. C. FIGUEROA; A. X. SILVA; C. C. RAMIREZ; L. MIEUZET; J. BONHOMME; S. STOECKEL; M. PLANTEGENEST; J.‐C. SIMON (Molecular Ecology, 2008)
Asexuality confers demographic advantages to invasive taxa, but generally limits adaptive potential for colonizing of new habitats. Therefore, pre‐existing adaptations and habitat tolerance are essential in the success of asexual invaders. We investigated these key factors of invasiveness by assessing reproductive modes and host‐plant adaptations in the pea aphid, Acyrthosiphon pisum , a pest recently introduced into Chile. The pea aphid encompasses lineages differing in their reproductive mode, ranging from obligatory cyclical parthenogenesis to fully asexual reproduction. This species also shows variation in host use, with distinct biotypes specialized on different species of legumes as well as more polyphagous populations. In central Chile, microsatellite genotyping of pea aphids sampled on five crops and wild legumes revealed three main clonal genotypes, which showed striking associations with particular host plants rather than sampling locations. Phenotypic analyses confirmed their strong host specialization and demonstrated parthenogenesis as their sole reproductive mode. The genetic relatedness of these clonal genotypes with corresponding host‐specialized populations from the Old World indicated that each clone descended from a particular Eurasian biotype, which involved at least three successful introduction events followed by spread on different crops. This study illustrates that multiple introductions of highly specialized clones, rather than local evolution in resource use and/or selection of generalist genotypes, can explain the demographic success of a strictly asexual invader.

Major Sex Pheromone Components of the Australian Gum Leaf Skeletonizer Uraba lugens: (10E,12Z)-Hexadecadien-1-yl Acetate and (10E,12Z)-Hexadecadien-1-ol - Andrew R. Gibb; David M. Suckling; Simon Fielder; Barry Bunn; Lisa E. Jamieson; Michelle L. Larsen; Gimme H. Walter; Darren J. Kriticos (Journal of Chemical Ecology, 2008)

A new mechanism of dominance in hypophosphatasia: the mutated protein can disturb the cell localization of the wild-type protein - A. S. Lia-Baldini; I. Brun-Heath; C. Carrion; B. Simon-Bouy; J. L. Serre; M. E. Nunes; E. Mornet (Human Genetics, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

MicroCT Analysis of Symphyseal Ontogeny in Archaeolemur - Matthew J. Ravosa; Stuart R. Stock; Elwyn L. Simons; Ravinder Kunwar (International Journal of Primatology, 2007)

Piperacillin-tazobactam in pediatric cancer patients younger than 25 months: a retrospective multicenter survey - A. Simon; T. Lehrnbecher; U. Bode; A. H. Groll; L. Tramsen; R. Wieland; E. Molitor; G. Fleischhack; H. J. Laws (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Diagnosis and management of small‐scale fisheries in developing countries - Neil L Andrew; Christophe Béné; Stephen J Hall; Edward H Allison; Simon Heck; Blake D Ratner (Fish and Fisheries, 2007)
Small‐scale fisheries (SSF) make important but undervalued contributions to the economies of some of the world’s poorest countries. They also provide much of the animal protein needed by societies in which food security remains a pressing issue. Assessment and management of these fisheries is usually inadequate or absent and they continue to fall short of their potential as engines for development and social change. In this study, we bring together existing theory and methods to suggest a general scheme for diagnosing and managing SSF. This approach can be adapted to accommodate the diversity of these fisheries in the developing world. Many threats and solutions to the problems that beset SSF come from outside the domain of the fishery. Significant improvements in prospects for fisheries will require major changes in societal priorities and values, with consequent improvements in policy and governance. Changes in development policy and science reflect these imperatives but there remains a need for intra‐sectoral management that builds resilience and reduces vulnerability to those forces beyond the influence of small‐scale fishers.

Lower reproductive success in hybrid fur seal males indicates fitness costs to hybridization - MELANIE L. LANCASTER; COREY J. A. BRADSHAW; SIMON D. GOLDSWORTHY; PAUL SUNNUCKS (Molecular Ecology, 2007)
Hybridization among organisms can potentially contribute to the processes of evolution, but this depends on the fitness of hybrids relative to parental species. A small, recently formed population of fur seals on subantarctic Macquarie Island contains a high proportion of hybrids (17–30%) derived from combinations of three parental species: Antarctic, subantarctic and New Zealand fur seals. Mitochondrial control‐region data (restriction fragment length polymorphisms) and nine microsatellites were used to determine the species composition of breeding adults, and hybrid male fitness was measured by comparing reproductive success (number of genetically inferred paternities) of hybrid and pure‐species territory males over 6 years. No correlations were found between male reproductive success and three genetic measures of outbreeding, but this may be due to a relatively small number of dominant males analysed. Territory males fathered 63% of pups, but hybrid males had lower reproductive success than pure‐species males despite having the same ability to hold territories. A greater proportion of females in hybrid male territories conceived extra‐territorially than those in territories of pure‐species males, and most (70 of 82) mated with conspecifics. This suggests the presence of reproductive isolating mechanisms that promote positive assortative mating and reduce the production of hybrid offspring. Although we found no evidence for male sterility in the population, mechanisms that reduce lifetime reproductive success may act to decrease the frequency of hybrids. Our study has identified a disadvantage of hybridization — reduced reproductive success of hybrid sons — that may be contributing to the persistence of pure lineages at Macquarie Island and the temporal decline in hybridization observed there.

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Olfactory cues, genetic relatedness and female mate choice in the agile antechinus (Antechinus agilis) - Marissa L. Parrott; Simon J. Ward; Peter D. Temple-Smith (Behavioral Ecology and Sociobiology, 2007)

Carotenoid biosynthesis structural genes in carrot (Daucus carota): isolation, sequence-characterization, single nucleotide polymorphism (SNP) markers and genome mapping - B. J. Just; C. A. F. Santos; M. E. N. Fonseca; L. S. Boiteux; B. B. Oloizia; P. W. Simon (Theoretical and Applied Genetics, 2007)

The genetic effective and adult census size of an Australian population of tiger prawns ( Penaeus esculentus ) - JENNIFER R. OVENDEN; DAVID PEEL; RAEWYN STREET; ANTHONY J. COURTNEY; SIMON D. HOYLE; SAMANTHA L. PEEL; HEATHER PODLICH (Molecular Ecology, 2007)
This study compares estimates of the census size of the spawning population with genetic estimates of effective current and long‐term population size for an abundant and commercially important marine invertebrate, the brown tiger prawn ( Penaeus esculentus ). Our aim was to focus on the relationship between genetic effective and census size that may provide a source of information for viability analyses of naturally occurring populations. Samples were taken in 2001, 2002 and 2003 from a population on the east coast of Australia and temporal allelic variation was measured at eight polymorphic microsatellite loci. Moments‐based and maximum‐likelihood estimates of current genetic effective population size ranged from 797 to 1304. The mean long‐term genetic effective population size was 9968. Although small for a large population, the effective population size estimates were above the threshold where genetic diversity is lost at neutral alleles through drift or inbreeding. Simulation studies correctly predicted that under these experimental conditions the genetic estimates would have non‐infinite upper confidence limits and revealed they might be overestimates of the true size. We also show that estimates of mortality and variance in family size may be derived from data on average fecundity, current genetic effective and census spawning population size, assuming effective population size is equivalent to the number of breeders. This work confirms that it is feasible to obtain accurate estimates of current genetic effective population size for abundant Type III species using existing genetic marker technology.

The Ecotoxicological Recovery of Ely Creek and Tributaries (Lee County, Va) After Remediation of Acid Mine Drainage - Matthew L. Simon; Donald S. Cherry; Rebecca J. Currie; Carl E. Zipper (Environmental Monitoring and Assessment, 2006)

The impact of natural and anthropogenic forcings on climate and hydrology since 1550 - Simon F. B. Tett; Richard Betts; Thomas J. Crowley; Jonathan Gregory; Timothy C. Johns; Andy Jones; Timothy J. Osborn; Elisabeth Öström; David L. Roberts; Margaret J. Woodage (Climate Dynamics, 2006)

Identification and characterization of PiORP1, a Petunia oxysterol-binding-protein related protein involved in receptor-kinase mediated signaling in pollen, and analysis of the ORP gene family in Arabidopsis - Andrea L. Skirpan; Peter E. Dowd; Paja Sijacic; Cynthia J. Jaworski; Simon Gilroy; Teh-hui Kao (Plant Molecular Biology, 2006)

Self-selected exercise intensity during household/garden activities and walking in 55 to 65-year-old females - Robert T. Withers; Anthony G. Brooks; Simon M. Gunn; John L. Plummer; Christopher J. Gore; John Cormack (European Journal of Applied Physiology, 2006)

The regional variation of aboveground live biomass in old‐growth Amazonian forests - YADVINDER MALHI; DANIEL WOOD; TIMOTHY R. BAKER; JAMES WRIGHT; OLIVER L. PHILLIPS; THOMAS COCHRANE; PATRICK MEIR; JEROME CHAVE; SAMUEL ALMEIDA; LUZMILLA ARROYO; NIRO HIGUCHI; TIMOTHY J. KILLEEN; et al. (Global Change Biology, 2006)
The biomass of tropical forests plays an important role in the global carbon cycle, both as a dynamic reservoir of carbon, and as a source of carbon dioxide to the atmosphere in areas undergoing deforestation. However, the absolute magnitude and environmental determinants of tropical forest biomass are still poorly understood. Here, we present a new synthesis and interpolation of the basal area and aboveground live biomass of old‐growth lowland tropical forests across South America, based on data from 227 forest plots, many previously unpublished. Forest biomass was analyzed in terms of two uncorrelated factors: basal area and mean wood density. Basal area is strongly affected by local landscape factors, but is relatively invariant at regional scale in moist tropical forests, and declines significantly at the dry periphery of the forest zone. Mean wood density is inversely correlated with forest dynamics, being lower in the dynamic forests of western Amazonia and high in the slow‐growing forests of eastern Amazonia. The combination of these two factors results in biomass being highest in the moderately seasonal, slow growing forests of central Amazonia and the Guyanas (up to 350 Mg dry weight ha −1 ) and declining to 200–250 Mg dry weight ha −1 at the western, southern and eastern margins. Overall, we estimate the total aboveground live biomass of intact Amazonian rainforests (area 5.76 × 10 6 km 2 in 2000) to be 93±23 Pg C, taking into account lianas and small trees. Including dead biomass and belowground biomass would increase this value by approximately 10% and 21%, respectively, but the spatial variation of these additional terms still needs to be quantified.

The Ecotoxicological Recovery of Ely Creek and Tributaries (Lee County, VA) after Remediation of Acid Mine Drainage - Mathew L. Simon; Donald S. Cherry; Rebecca J. Currie; Carl E. Zipper (Environmental Monitoring and Assessment, 2006)

Characterization of a mutant strain of Rhodovulum sulfidophilum lacking the pufA and pufB genes encoding the polypeptides for the light-harvesting complex 1 (B 870) - Laura J. Raiger-Iustman; Norma L. Kerber; Norma L. Pucheu; Marc J. Bornmann; Simon Kohler; Andreas Labahn; Monier Tadros; Gerhart Drews; Augusto F. García (Archives of Microbiology, 2006)

Evidence that Soil Carbon Pool Determines Susceptibility of Semi-Natural Ecosystems to Elevated Nitrogen Leaching - Christopher D. Evans; Brian Reynolds; Alan Jenkins; Rachel C. Helliwell; Christopher J. Curtis; Christine L. Goodale; Robert C. Ferrier; Bridget A. Emmett; Michael G. Pilkington; Simon J. M. Caporn; Jacky A. Carroll; David Norris; et al. (Ecosystems, 2006)

An improved purification procedure for the soluble [NiFe]-hydrogenase of Ralstonia eutropha: new insights into its (in)stability and spectroscopic properties - Eddy van der Linden; Tanja Burgdorf; Antonio L. de Lacey; Thorsten Buhrke; Marcel Scholte; Victor M. Fernandez; Bärbel Friedrich; Simon P. J. Albracht (JBIC Journal of Biological Inorganic Chemistry, 2006)

Evidence for novel loci for late-onset Parkinson’s disease in a genetic isolate from the Netherlands - Aida M. Bertoli-Avella; Marieke C. J. Dekker; Yurii S. Aulchenko; Jeanine J. Houwing-Duistermaat; Erik Simons; Leon Testers; Luba M. Pardo; Tessa A. M. Rademaker; Pieter J. L. M. Snijders; John C. van Swieten; Vincenzo Bonifati; Peter Heutink; et al. (Human Genetics, 2006)

The active site of the [FeFe]-hydrogenase from Desulfovibrio desulfuricans. II. Redox properties, light sensitivity and CO-ligand exchange as observed by infrared spectroscopy - Winfried Roseboom; Antonio L. De Lacey; Victor M. Fernandez; E. Claude Hatchikian; Simon P. J. Albracht (JBIC Journal of Biological Inorganic Chemistry, 2006)

The energy cost of household and garden activities in 55- to 65-year-old males - Simon M. Gunn; Anthony G. Brooks; Robert T. Withers; Christopher J. Gore; John L. Plummer; John Cormack (European Journal of Applied Physiology, 2005)

Development of anonymous cDNA microarrays to study changes to the Senecio floral transcriptome during hybrid speciation - MATTHEW J. HEGARTY; JOANNA M. JONES; IAN D. WILSON; GARY L. BARKER; JANE A. COGHILL; PATRICIA SANCHEZ‐BARACALDO; GUOQING LIU; RICHARD J. A. BUGGS; RICHARD J. ABBOTT; KEITH J. EDWARDS; SIMON J. HISCOCK (Molecular Ecology, 2005)
Interspecific hybridization is an important process through which abrupt speciation can occur. In recent years, genetic changes associated with hybrid speciation have been identified through a variety of techniques, including AFLP/SSR mapping, GISH/FISH and cDNA‐AFLP differential display. However, progress in using microarray technology to analyse whole genome/transcriptome changes associated with hybrid speciation has been limited due to the lack of extensive sequence data for many hybrid species and the difficulties in extrapolating results from commercially available microarrays for model species onto nonmodel hybrid taxa. Increasingly therefore researchers studying nonmodel systems are turning to the development of ‘anonymous’ cDNA microarrays, where the time and cost of producing microarrays is reduced by printing unsequenced cDNA clones, and sequencing only those clones that display interesting expression patterns. Here we describe the creation, testing and preliminary use of anonymous cDNA microarrays to study changes in floral transcriptome associated with allopolyploid speciation in the genus Senecio. We report a comparison of gene expression between the allohexaploid hybrid, Senecio cambrensis , its parental taxa Senecio squalidus (diploid) and Senecio vulgaris (tetraploid), and the intermediate triploid (sterile) hybrid Senecio × baxteri . Anonymous microarray analysis revealed dramatic differences in floral gene expression between these four taxa and demonstrates the power of this technique for studies of the genetic impact of hybridization in nonmodel flowering plants.

A conserved functional role of pectic polymers in stomatal guard cells from a range of plant species - Louise Jones; Jennifer L. Milne; David Ashford; Maureen C. McCann; Simon J. McQueen-Mason (Planta, 2005)

Climate variability and campylobacter infection: an international study - R. Sari Kovats; Sally J. Edwards; Dominique Charron; John Cowden; Rennie M. D’Souza; Kristie L. Ebi; Charmaine Gauci; Peter Gerner-Smidt; Shakoor Hajat; Simon Hales; Gloria Hernández Pezzi; Bohumir Kriz; et al. (International Journal of Biometeorology, 2005)

Admixed sexual and facultatively asexual aphid lineages at mating sites - F. HALKETT; M. PLANTEGENEST; N. PRUNIER‐LETERME; L. MIEUZET; F. DELMOTTE; J. C. SIMON (Molecular Ecology, 2005)
Cyclically parthenogenetic organisms may have facultative asexual counterparts. Such organisms, including aphids, are therefore interesting models for the study of ecological and genetic interactions between lineages differing in reproductive mode. Earlier studies on aphids have revealed major differences in the genetic outcomes of populations that are possibly resulting mostly either from sexual or from asexual reproduction. Besides, notable gene flow between sexual and asexual derivatives has been suspected, which could lead to the emergence of new asexual lineages. The present study examines the interplay between these lineages and is based on analyses of population structure of individuals that may contribute to the pool of sexual reproductive forms in the host alternating aphid Rhopalosiphum padi . Using a Bayesian assignment method, we first show that the sexual forms of R. padi on mating sites encompass two genetically distinct clusters of individuals in the western part of France. The first cluster included unique genotypes of sexual lineages, while the second cluster included facultatively asexual lineages in numerous copies, the reproductive mode of the two clusters being confirmed by reference clones. Sexual reproductive forms produced by sexual and facultatively asexual lineages are thus admixed at mating sites which gives a large opportunity for the two clusters to mate with each other. Nevertheless, this study also highlights, as previously demonstrated, that the two clusters retained high genetic differentiation. Possible explanations for the inferred limited genetic exchanges are advanced in the discussion, but further dedicated investigations are required to solve this paradox.

Differential regulation of caspase-3 by pharmacological and developmental stimuli as demonstrated using humanised caspase-3 mice - L. E. Kerr; J-L. A. Birse-Archbold; A. Simon; N. Logan; F. Scott; G. Carlson; D. W. Nicholson; J. S. Kelly; J. Sharkey (Apoptosis, 2004)

The activation of the [NiFe]-hydrogenase from Allochromatium vinosum. An infrared spectro-electrochemical study - Boris Bleijlevens; Fleur A. van Broekhuizen; Antonio L. De Lacey; Winfried Roseboom; Victor M. Fernandez; Simon P. J. Albracht (JBIC Journal of Biological Inorganic Chemistry, 2004)

Towards a mutant map of the mouse ? new models of neurological, behavioural, deafness, bone, renal and blood disorders - Sohaila Rastan; Tertius Hough; Amy Kierman; Rachel Hardisty; Alexandra Erven; Ian C. Gray; Stepanie Voeling; Adrian Isaacs; Hsun Tsai; Mark Strivens; Rebecca Washbourne; Claire Thornton; et al. (Genetica, 2004)

The gene encoding the ribulose monophosphate pathway enzyme, 3-hexulose-6-phosphate synthase, from Aminomonas aminovorus C2A1 is adjacent to coding sequences that exhibit similarity to histidine biosynthesis enzymes. - Edward J. Taylor; Nicola L. Smith; John Colby; Simon J. Charnock; Gary W. Black (Antonie van Leeuwenhoek, 2004)

Immunocytochemical evidence for an NMDA1 receptor subunit in dissociated cells of Hydra vulgaris - A. A. Scappaticci; R. Jacques; J. E. Carroll; L. A. Hufnagel; G. Kass-Simon (Cell and Tissue Research, 2004)

Variation in wood density determines spatial patterns inAmazonian forest biomass - Timothy R. Baker; Oliver L. Phillips; Yadvinder Malhi; Samuel Almeida; Luzmila Arroyo; Anthony Di Fiore; Terry Erwin; Timothy J. Killeen; Susan G. Laurance; William F. Laurance; Simon L. Lewis; Jon Lloyd; et al. (Global Change Biology, 2004)
Uncertainty in biomass estimates is one of the greatest limitations to models of carbon flux in tropical forests. Previous comparisons of field‐based estimates of the aboveground biomass (AGB) of trees greater than 10 cm diameter within Amazonia have been limited by the paucity of data for western Amazon forests, and the use of site‐specific methods to estimate biomass from inventory data. In addition, the role of regional variation in stand‐level wood specific gravity has not previously been considered. Using data from 56 mature forest plots across Amazonia, we consider the relative roles of species composition (wood specific gravity) and forest structure (basal area) in determining variation in AGB. Mean stand‐level wood specific gravity, on a per stem basis, is 15.8% higher in forests in central and eastern, compared with northwestern Amazonia. This pattern is due to the higher diversity and abundance of taxa with high specific gravity values in central and eastern Amazonia, and the greater diversity and abundance of taxa with low specific gravity values in western Amazonia. For two estimates of AGB derived using different allometric equations, basal area explains 51.7% and 63.4%, and stand‐level specific gravity 45.4% and 29.7%, of the total variation in AGB. The variation in specific gravity is important because it determines the regional scale, spatial pattern of AGB. When weighting by specific gravity is included, central and eastern Amazon forests have significantly higher AGB than stands in northwest or southwest Amazonia. The regional‐scale pattern of species composition therefore defines a broad gradient of AGB across Amazonia.

The above‐ground coarse wood productivity of 104 Neotropical forest plots - Yadvinder Malhi; Timothy R. Baker; Oliver L. Phillips; Samuel Almeida; Esteban Alvarez; Luzmilla Arroyo; Jerome Chave; Claudia I. Czimczik; Anthony Di Fiore; Niro Higuchi; Timothy J. Killeen; Susan G. Laurance; et al. (Global Change Biology, 2004)
The net primary production of tropical forests and its partitioning between long‐lived carbon pools (wood) and shorter‐lived pools (leaves, fine roots) are of considerable importance in the global carbon cycle. However, these terms have only been studied at a handful of field sites, and with no consistent calculation methodology. Here we calculate above‐ground coarse wood carbon productivity for 104 forest plots in lowland New World humid tropical forests, using a consistent calculation methodology that incorporates corrections for spatial variations in tree‐size distributions and wood density, and for census interval length. Mean wood density is found to be lower in more productive forests. We estimate that above‐ground coarse wood productivity varies by more than a factor of three (between 1.5 and 5.5 Mg C ha −1 a −1 ) across the Neotropical plots, with a mean value of 3.1 Mg C ha −1 a −1 . There appear to be no obvious relationships between wood productivity and rainfall, dry season length or sunshine, but there is some hint of increased productivity at lower temperatures. There is, however, also strong evidence for a positive relationship between wood productivity and soil fertility. Fertile soils tend to become more common towards the Andes and at slightly higher than average elevations, so the apparent temperature/productivity relationship is probably not a direct one. Coarse wood productivity accounts for only a fraction of overall tropical forest net primary productivity, but the available data indicate that it is approximately proportional to total above‐ground productivity. We speculate that the large variation in wood productivity is unlikely to directly imply an equivalent variation in gross primary production. Instead a shifting balance in carbon allocation between respiration, wood carbon and fine root production seems the more likely explanation.

Tachykinin substance P signaling involved in diesel exhaust-induced bronchopulmonary neurogenic inflammation in rats - Simon S. Wong; Nina N. Sun; Ingegerd Keith; Chol-Bum Kweon; David E. Foster; James J. Schauer; Mark L. Witten (Archives of Toxicology, 2003)

Hydrocarbon distribution and colony odour homogenisation in Pachycondyla apicalis - V. Soroker; C. Lucas; T. Simon; A. Hefetz; D. Fresneau; J. L. Durand (Insectes Sociaux, 2003)

Polymorphism in Major Urinary Proteins: Molecular Heterogeneity in a Wild Mouse Population - Robert J. Beynon; Christina Veggerby; Caroline E. Payne; Duncan H. L. Robertson; Simon J. Gaskell; Rick E. Humphries; Jane L. Hurst (Journal of Chemical Ecology, 2002)

Vegetative propagation of Prunus africana: effects of rooting medium, auxin concentrations and leaf area - Z. Tchoundjeu; M. L. Avana; R. R. B. Leakey; A. J. Simons; E. Assah; B. Duguma; J. M. Bell (Agroforestry Systems, 2002)

Substantial linkage disequilibrium across the insulin-degrading enzyme locus but no association with late-onset Alzheimer's disease - Richard Abraham; Amanda Myers; Fabienne Wavrant-DeVrieze; Marian L. Hamshere; Hollie V. Thomas; Helen Marshall; Danielle Compton; Gillian Spurlock; Dragana Turic; Bastiaan Hoogendoorn; Jennifer M. Kwon; Ronald C. Petersen; et al. (Human Genetics, 2001)

Enhancement of Chromium Phytoextraction Capacity of Fodder Radish with Picolinic Acid - L. Simon; I. SzegvÁri; J. Prokisch (Environmental Geochemistry and Health, 2001)

Evidence for predominant clones in a cyclically parthenogenetic organism provided by combined demographic and genetic analyses - L. Haack; J.‐C. Simon; J.‐P. Gauthier; M. Plantegenest; C.‐A. Dedryver (Molecular Ecology, 2000)
Aphids are particularly interesting models in the study of genetic and demographic components of plant adaptation because of their breeding system which combines parthenogenesis and sexual reproduction (i.e. cyclical parthenogenesis), and the frequent emergence of host‐adapted races reported in this group. In this paper, patterns of host adaptation were assessed on local populations of the aphid Sitobion avenae by following their demographic and genetic structure in a maize field for two consecutive years. The existence of putative generalist (polyphagous) or specialized (host‐adapted) genotypes was also investigated by comparing the genotypic distribution of this aphid on maize and other cultivated host plants, using five microsatellite loci. Although population dynamics revealed strong variation in aphid abundance during the colonization period on maize, two genotypes identified at seven additional microsatellite loci were predominant and exhibited stable frequencies over cropping season and between years. Based on present and earlier studies, these two prevalent genotypes were shown to survive on different host plants other than maize, to colonize large geographical zones and to persist parthenogenetically for several years. All these data strongly suggest that these two genotypes are asexual generalist clones that could have been favoured by agricultural practices encountered in western Europe. Besides these two clones, a continual replacement of rare genotypes was observed on maize in both years. Hypotheses involving selection via aphid–plant interactions and natural enemies were proposed for explaining the disappearance of these genotypes on maize.

Informatics for mutagenesis: the design of Mutabase—a distributed data recording system for animal husbandry, mutagenesis, and phenotypic analysis - Mark A. Strivens; Rachel L. Selley; Simon J. Greenaway; Mazda Hewitt; Xinhong Liu; Kirstin Battershill; Stefan L. McCormack; Karen A. Pickford; Lucie Vizor; Patrick M. Nolan; A. Jacqueline Hunter; Josephine Peters; et al. (Mammalian Genome, 2000)

Postsealing genetic variation and population structure of two species of fur seal ( Arctocephalus gazella and A. tropicalis ) - Louise P. Wynen; Simon D. Goldsworthy; Christophe Guinet; Marthán N. Bester; Ian L. Boyd; Ian Gjertz; Greg J. G. Hofmeyr; Robert W. G. White; Rob Slade (Molecular Ecology, 2000)
Commercial sealing in the 18th and 19th centuries had a major impact on the Antarctic and subantarctic fur seal populations ( Arctocephalus gazella and A. tropicalis ) in the Southern Ocean. The intensive and unrestricted nature of the industry ensured substantial reductions in population sizes and resulted in both species becoming locally extinct at some sites. However, both species are continuing to recover, through the recolonization of islands across their former range and increasing population size. This study investigated the extent and pattern of genetic variation in each species to examine the hypothesis that higher levels of historic sealing in A. gazella have resulted in a greater loss of genetic variability and population structure compared with A. tropicalis . A 316‐bp section of the mitochondrial control region was sequenced and revealed nucleotide diversities of 3.2% and 4.8% for A. gazella and A. tropicalis , respectively. There was no geographical distribution of lineages observed within either species, although the respective Φ ST values of 0.074 and 0.19 were significantly greater than zero. These data indicate low levels of population structure in A. gazella and relatively high levels in A. tropicalis. Additional samples screened with restriction endonucleases were incorporated, and the distribution of restriction fragment length polymorphism (RFLP) and sequence haplotypes were examined to identify the main source populations of newly recolonized islands. For A. tropicalis , the data suggest that Macquarie Island and Iles Crozet were probably recolonized by females from Marion Island, and to a lesser extent Ile Amsterdam. Although there was less population structure within A. gazella , there were two geographical regions identified: a western region containing the populations of South Georgia and Bouvetøya, which were the probable sources for populations at Marion, the South Shetland and Heard Islands; and an eastern region containing the panmictic populations of Iles Kerguelen and Macquarie Island. The latter region may be a result of a pronounced founder effect, or represent a remnant population that survived sealing at Iles Kerguelen.

RAPD linkage map of the genomic region encompassing the root-knot nematode (Meloidogyne javanica) resistance locus in carrot - L. S. Boiteux; J. G. Belter; P. A. Roberts; P. W. Simon (Theoretical and Applied Genetics, 2000)

Late Middle Pleistocene deposits at Norton Farm on the West Sussex coastal plain, southern England - Martin R. Bates; C. Richard Bates; Philip L. Gibbard; Richard I. Macphail; Frederick J. Owen; Simon A. Parfitt; Richard C. Preece; Mark B. Roberts; J. Eric Robinson; John E. Whittaker; Keith N. Wilkinson (Journal of Quaternary Science, 2000)

Disparate phylogeographic patterns of molecular genetic variation in four closely related South American small cat species - Warren E. Johnson; Jill Pecon Slattery; Eduardo Eizirik; Jae‐Heup Kim; Marilyn Menotti Raymond; Cristian Bonacic; Richard Cambre; Peter Crawshaw; Adauto Nunes; Héctor N. Seuánez; Miguel Angelo Martins Moreira; Kevin L. Seymour; et al. (Molecular Ecology, 1999)
Tissue specimens from four species of Neotropical small cats ( Oncifelis geoffroyi , N = 38; O. guigna , N = 6; Leopardus tigrinus , N = 32; Lynchailurus colocolo , N = 22) collected from throughout their distribution were examined for patterns of DNA sequence variation using three mitochondrial genes, 16S rRNA, ATP8, and NADH‐5. Patterns between and among O. guigna and O. geoffroyi individuals were assessed further from size variation at 20 microsatellite loci. Phylogenetic analyses using mitochondrial DNA sequences revealed monophyletic clustering of the four species, plus evidence of natural hybridization between L. tigrinus and L. colocolo in areas of range overlap and discrete population subdivisions reflecting geographical isolation. Several commonly accepted subspecies partitions were affirmed for L. colocolo , but not for O. geoffroyi . The lack of geographical substructure in O. geoffroyi was recapitulated with the microsatellite data, as was the monophyletic clustering of O. guigna and O. geoffroyi individuals. L. tigrinus forms two phylogeographic clusters which correspond to L.t. oncilla (from Costa Rica) and L.t. guttula (from Brazil) and which have mitochondrial DNA (mtDNA) genetic distance estimates comparable to interspecific values between other ocelot lineage species. Using feline‐specific calibration rates for mitochondrial DNA mutation rates, we estimated that extant lineages of O. guigna diverged 0.4 million years ago (Ma), compared with 1.7 Ma for L. colocolo , 2.0 Ma for O. geoffroyi , and 3.7 Ma for L. tigrinus .

A bovine YAC library containing four- to five-fold genome equivalents - David Hills; Simon Tracey; Julio Masabanda; Ruedi Fries; Leonard C. Schalkwyk; Hans Lehrach; J. Ross Miller; John L. Williams (Mammalian Genome, 1999)

A 5× genome coverage bovine BAC library: production, characterization, and distribution - Baoli Zhu; Judith A. Smith; Simon M. Tracey; Bernard A. Konfortov; Katrin Welzel; Leonard C. Schalkwyk; Hans Lehrach; Sonja Kollers; Julio Masabanda; Johannes Buitkamp; Ruedi Fries; John L. Williams; et al. (Mammalian Genome, 1999)

Adverse drug events in hospitalized patients - P. M. L. A. van den Bemt; A. C. G. Egberts; A. W. Lenderink; J. M. Verzijl; K. A. Simons; W. S. C. J. M. van der Pol; H. G. M. Leufkens (European Journal of Clinical Pharmacology, 1999)

Diffusion metasomatism in silica-undersaturated sapphirine-bearing granulite from Rumdoodle Peak, Framnes Mountains, east Antarctica - Daniel J. Dunkley; Geoffrey L. Clarke; Simon L. Harley (Contributions to Mineralogy and Petrology, 1999)

A Comparison of Aerial and Ground Level Measurements of 137Cs in the Marshall Islands - S. L. Simon; J. C. Graham (Environmental Monitoring and Assessment, 1998)

Influence of exercise duration on serum insulin-like growth factor and its binding proteins in athletes - U. N. Nguyen; F. Mougin; M. L. Simon-Rigaud; J. D. Rouillon; P. Marguet; J. Regnard (European Journal of Applied Physiology, 1998)

Eucalyptus has a functional equivalent of the Arabidopsis floral meristem identity gene LEAFY - Simon G. Southerton; Steven H. Strauss; Mark R. Olive; Rebecca L. Harcourt; Veronique Decroocq; Xiaomei Zhu; Danny J. Llewellyn; W. James Peacock; Elizabeth S. Dennis (Plant Molecular Biology, 1998)

The Henry's Law Constant of Trichloroacetic Acid - Derek J. Bowden; Simon L. Clegg; Peter Brimblecombe (Water, Air, & Soil Pollution, 1998)

Canine X-linked severe combined immunodeficiency - Peter J. Felsburg; Richard L. Somberg; Brian J. Hartnett; Paula S. Henthorn; Simon R. Carding (Immunologic Research, 1998)

Validation of Ground-Based Visible Measurements of Total Ozone by Comparison with Dobson and Brewer Spectrophotometers - M. Van Roozendael; P. Peeters; H. K. Roscoe; H. De Backer; A. E. Jones; L. Bartlett; G. Vaughan; F. Goutail; J.-P. Pommereau; E. Kyro; C. Wahlstrom; G. Braathen; et al. (Journal of Atmospheric Chemistry, 1998)

Protein folding in protein export - Simon J. S. Hardy; Linda L. Randall (Antonie van Leeuwenhoek, 1992)

The toxic effect of deltamethrin on linyphiid and erigonid spiders in connection with ambient temperature, humidity, and predation - J. W. Everts; I. Willemsen; M. Stulp; L. Simons; B. Aukema; J. Kammenga (Archives of Environmental Contamination and Toxicology, 1991)

Quantitative aspects of glucose metabolism by Escherichia coli B/r, grown in the presence of pyrroloquinoline quinone - R. W. J. Hommes; J. A. Simons; J. L. Snoep; P. W. Postma; D. W. Tempest; O. M. Neijssel (Antonie van Leeuwenhoek, 1991)

The effect of the dissolved oxygen concentration and anabolic limitations on the behaviour of Rhizobium ORS571 in chemostat cultures - W. de Vries; H. Stam; J. G. Duys; A. J. M. Ligtenberg; L. H. Simons; A. H. Stouthamer (Antonie van Leeuwenhoek, 1986)

Chemical and biological characterization of volatile components of environmental samples after fractionation by vacuum line cryogenic distillation - Ray L. Hanson; Alan R. Dahl; Simon J. Rothenberg; Janet M. Benson; Antone L. Brooks; John S. Dutcher (Archives of Environmental Contamination and Toxicology, 1985)

Neurovirulence of an herpes simplex type 1 thymidine kinase negative mutant determined by virus biochemical defect and host immune system in mice - Y. J. Gordon; P. L. Simon; J. A. Armstrong (Archives of Virology, 1984)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

Enqute sur la frquence et la signification de l'isolement des entrovirus au cours des gastro-entrites infantiles - P. Lpine; J. Samaille; J. Virat; M. C. Carr; N. Simon-Lavoine (Archives of Virology, 1963)